A novel approach for assessing the genuine thermal efficiency of high-pressure grinding roller (HPGR) crusher based on exergy analysis - Zhengyu Liu; Zhihao Liu; Xiaoming Liu; Bin Yang; Wei Liu; Jiawei Lin; Siqi Zhang; Wenjie Zou; Jun Zhang; Jinrong Ju; Jue Kou; Chunbao Sun; et al. (Minerals Engineering, 2026)

MPP+ disorders Irg1-Itaconate axis to promote M1 polarization of microglia by activating succinate dehydrogenase - Lin-Yu Wang; Yi-Yun Tang; Wei Zou; Ping Zhang; Xiao-Qing Tang; Ping Zhang (Molecular Biology Reports, 2026)

Investigating the shared genetic architecture between inflammatory bowel disease and pancreatitis: a genome-wide cross-trait analysis - Hang-Ming Qi; Ting-Ting Liu; Jia-Yun Chen; Ya-Hui Wang; Xiao-Tong Mao; Yuan-Chen Wang; Jing Jin; Xi Lin; Jianfeng Yang; Wen-Bin Zou; Le Kang; Zhuan Liao (Molecular Genetics and Genomics, 2026)

Hydrogeochemical characteristics, salinization, and irrigation suitability assessment of coastal groundwater in Hainan Island, China - Yongsheng Lin; Shengzhang Zou; Li Lu; Xianyu Wei; Lianjie Fan; Jinhui Liu (Marine Pollution Bulletin, 2026)

Palaeoenvironmental evolution and stage-dependent organic matter enrichment in the Late Permian Longtan Formation, Upper Yangtze Block, South China - Hai-Feng Chen; Xin Jin; Marcello Caggiati; Ting-Cong Ren; Bo Luo; Lin-Hao Fang; Hua-Wen Cao; Yang Liu; Chang-Cheng Huang; Bin Xiao; Zi-Han Ma; Hui-Dong Yu; et al. (Sedimentary Geology, 2026)

Ecological connectivity of phytoplankton community in the Xincun Bay lagoon, Hainan Island - Jian Zou; Yayuan Xiao; Lin Lin; Peng Wu; Teng Wang; Yu Liu; Shannan Xu; Yong Liu (Journal of Marine Systems, 2026)

Mechanistic insights into the migration and transformation of As2O3 by HCl during simulated MSW incineration flue gas cooling - Shuai Li; Hongyun Hu; Peixiong Tan; Chan Zou; Yongda Huang; Yipeng Wang; Zhong Lin; Hong Yao (Fuel, 2026)

Association of structural characteristics with immunostimulatory activity of pectic polysaccharides prepared from Tartary buckwheat sprouts by enzymatic degradation and partial acid hydrolysis - Lin Zhang; Bo Li; Xuan Gao; Mao-Qing Wang; Ya-Nan Cao; Mao-Ling Tan; Yi-Chen Hu; Liang Zou; Dan Li; Yong Deng; Jing-Wei Huang; Ding-Tao Wu (Food Research International, 2026)

Safety, immunogenicity, and broad-spectrum protective efficacy of a naturally attenuated GCRV-II strain against viral and bacterial challenges in grass carp - Dingzhe Zou; Yifei Li; Jie Zhou; Wangqian Xu; Ying Tian; Run Yang; Yujie Gu; Xiangyu Tian; Yucheng Lin; Jiping Zhang; Weiwei Zeng (Fish & Shellfish Immunology, 2026)

Microplastic interaction with Fe-P coupling pathways induced cadmium immobilization in tropical agricultural soils - Ying Yang; Chaoxian Wei; Pan Pan; Bigui Lin; Zhengfu Yue; Yukun Zou; Beibei Liu (Environmental Pollution, 2026)

Seasonal–diurnal nonlinear and interactive associations between built–natural–topographic indicators and land surface temperature in a coastal urban agglomeration - Aifang Weng; Baoyin Li; Yuying Lin; Linsheng Wen; Sunbowen Zhang; Chuanmao Hua; Chengshu Ke; Yilin Zou (Energy and Buildings, 2026)

Tailoring lattice confinement and conductivity of AlF co-doped Li2TiO3 ion sieves for highly selective lithium electrosorption - Ruini Zou; Yaxuan Wang; Ming Gao; Yijiao Chang; Bing Li; Xiao-yan Li; Lin Lin (Desalination, 2026)

Unveiling intricate interplay between Ni and Ce within microenvironment of NiCe/C@NC for electrocatalytic CO2 reduction - Zeyu Zhang; Huangdong Wang; Qian Zhao; Lin Jia; Yan Guo; Zewei Fu; Mengbo Zou; Guixiang Ma; Shangpeng Liu; Fenrong Liu; Shanghong Zeng (Chemical Engineering Journal, 2026)

Durable and efficient 2D/3D perovskite bulk heterojunction solar cells via BA2MAPb2I7 single crystal addition - Zihong Cai; Xin Chen; Zixing Guo; Yafei Wang; Tianqi Niu; Junyu Lin; Shihai Ye; Qianqiu Guan; Jiazhen Xu; Jiale Huang; Tao Zou; Zuoshan Zhang; et al. (Chemical Engineering Journal, 2026)

Exogenous raffinose enhances chilling tolerance in postharvest tomato fruit in relation to the scavenging of ROS, maintenance of energy homeostasis, and cell wall integrity - Weimin Ning; Bingqing Qian; Pan Zou; Yukun Shu; Zhiyuan Wang; Qinlu Zheng; Pan Shu; Yun Zhu; Yuan Qing; Zhong Zhang; Lin Shen (Postharvest Biology and Technology, 2026)

Research on mission planning method for self-propelled buoys under time-varying tidal current disturbances - Kehao Zhang; Mao Zheng; Xiumin Chu; Shigan Ding; Tianyue Zou; Bowen Lin (Ocean Engineering, 2026)

Carbon sink dynamics and resilience thresholds of a volcanic island land–sea system in the Beibu Gulf: Evidence from CMIP6 simulations and sediment records since 1961 - Yitong Lin; Yuanfu Yue; Qunxin He; Qinyi Meng; Xiaoxiao Zou; Shixiong Yang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Eco-efficient upcycling of size-fractionated low-quality river sand via graphene oxide coating for low-carbon cementitious composites - Fufu Zou; Zhehong Zhu; Jianxiong Miao; Huiru Lu; Junlin Lin; Yanming Liu; Yuan Gao (Journal of Environmental Chemical Engineering, 2026)

Local oxophilicity Sm incorporation drives structural alteration of Cu2O/Cu catalyst in CO2 electroreduction - Zihao Wei; Yulin Qin; Mengbo Zou; Lin Jia; Haorun Li; Yuekun Zhang; Jinyu Wang; Zeyu Guo; Hao Wu; Zeyu Zhang; Shanghong Zeng (Journal of Environmental Chemical Engineering, 2026)

Fungal drivers of mycotoxin contamination in wheat: Early warning and plasma-based control - Keyi Zou; Shujuan Chen; Lin Ji; Guoyan Wu; Ke Zhao; Jingxia Fu; Xiumei Yu; Xiaoxue Shan; Likou Zou (Food Research International, 2026)

Unraveling the core microbial succession during the moromi fermentation of cantonese soy sauce: An amplicon sequencing approach - Hongbiao Tang; Mouyong Zou; Xingui Zhu; Ge Tan; Liqiong Guo; Junfang Lin (Food Research International, 2026)

Multiscale mechanisms of antifreeze proteins in regulating frozen rabbit meat quality: A comprehensive study based on SPME-GC-MS, Cryo-SEM, and molecular dynamics - Weihao Wang; Zhi Li; Zhiyan Zhang; Lin Su; Xiao Zou; Lixiu Yan; Qiang Li; Jiamin Zhang; Jie Cheng (Food Control, 2026)

Parameterization of ground ice dynamics in permafrost models: Advances, challenges, and future directions - Yifan Wu; Guojie Hu; Lin Zhao; Zhe Sun; Bowen Zhang; Yao Xiao; Defu Zou; Guangyue Liu; Xiaofan Zhu; Tonghua Wu; Xiaodong Wu; Wenxin Zhang; et al. (Earth-Science Reviews, 2026)

Sustained-release salt reservoir enables durable solid electrolyte interphases for practical micron-sized silicon composite anodes - Kui Lin; Junke Wu; Zhengguang Song; Yuling Yi; Fuxi Peng; Shiwen Wang; Zhimin Zou; Tongbin Lan; Junxiong Wu; Chunhai Jiang (Chemical Engineering Journal, 2026)

Mechanobiological antagonism of integrin β1/β3 gates YAP-driven reactionary dentinogenesis through fluid shear stress sensing - Peiqi Liu; Hui Zhang; Haoyu Wang; Jingning Gou; Lingxiang Lian; Bilun Jin; Yi Guo; Wei Gong; Chenxu Wang; Yijie Wang; Rui Zou; Bo Cheng; et al. (Chemical Engineering Journal, 2026)

Gecko tail regeneration-inspired composite hydrogel scaffolds with “socket-plug” architecture for dynamically programmed repair of infected bone defects - Minglang Zou; Yi Tang; Yongming Wang; Ling Mo; Menghuan Wang; Qing He; Zhenjin Xu; Liu Su; Pengfei Wang; Fang Luo; Da Huang; Jiewei Luo; et al. (Chemical Engineering Journal, 2026)

Reference year methods under climate change: A comprehensive review of evolution, applications, and future directions - Jiwei Zou; Shujie Yan; Jing Kong; Abhishek Gaur; Lin Wang; Da Yan; Zheng Tan (Building and Environment, 2026)

Exogenous organic matter and clay mineral additions regulate microbial-mineral mediated soil organic carbon accumulation in alkaline-calcareous soils - Xi Yang; Donghao Ma; Lin Chen; Ting Yang; Yongqi Zhang; Hongwei Jiang; Nan Zhang; Hongtao Zou; Congzhi Zhang; Guixiang Zhou; Yanfang Zhou; Yu Luo; et al. (Applied Soil Ecology, 2026)

Rhizophagus intraradices differentially promotes growth and phosphorus uptake in Camellia oleifera under low versus adequate phosphorus supply - Wan-Lin Fu; Ying-Ning Zou; Shi-Qi Pu; Fang-Ling Wang; Zhi-Yan Xiao; Jun-Yong Cheng; Mei-Hua Yang; Mashael Daghash Alqahtani; Qiang-Sheng Wu (Rhizosphere, 2026)

Degradation of diclofenac via ascorbic acid-enhanced copper-catalyzed oxidation of sodium percarbonate system: Performance and mechanism - Zhenming Wang; Yajuan Cai; Jianying Wu; Xinyu Lin; Minfeng Wang; Lukai Zhuang; Zhongmin Fang; Guoqing Huang; Jing Zou (Process Safety and Environmental Protection, 2026)

Global design and dynamic analysis of floating offshore wind turbines with actively ballasted concrete floater - Guanfeng Lin; Hongyun Zou; Jing Li; Bing Liu; Zili Zhang (Ocean Engineering, 2026)

C-type lectins in arthropods: Evolutionary diversification and prospects for pathogen defense - Hongyu Li; Jialu Xu; Hairun Li; Jiyuan Wang; Xintong Chen; Yijie Zhang; Mingcheng Liu; Xiaofen Zhang; Yuqing Wang; Yunhuan Zhu; Yuncheng Qian; Yajie Lin; et al. (Journal of Invertebrate Pathology, 2026)

Recent progress on hydrogen production via catalytic Auto-thermal methane Reforming: A focus on catalysts and operational parameters - Jun Wan; Peng Liu; Feiyi Zhou; Huajie Lyu; Teng Hu; Keyu Cheng; Yihong Song; Jiabiao Zou; Xiao Zhang; Saisai Lin; Chenghang Zheng; Xiang Gao (Fuel, 2026)

Ultra-high pressure-assisted enzymatic extraction enhances phenolic release and functional potency in fermented dark tea extracts - Xiaoying Lin; Jun Li; Yuanshan Yu; Dengwen Lei; Tenggen Hu; Manqin Fu; Qiang Xiao; Junying Zou; Ya Gao; Chao Huang; Jing Wen (Food Research International, 2026)

Effects of light-shielding treatment on the quality and flavor of ‘Ziyan’ tea wine during storage: Insights from color, taste, and aroma - Ling Lin; Yinan Wu; Jingwen Yang; Ziyan Zhu; Xue Xia; Yixuan Gao; Yao Zou; Qian Tang; Liqiang Tan; Zhonghua Liu; Wei Xu (Food Chemistry, 2026)

Outdoor light at night exposure and hypertension risk in adults: A longitudinal cohort study from the FLORA project - Shuo Zhang; Xiao-Fan Lu; Muhammad Amjad; Lin-Jing Gong; Na Liu; Hong-Xing Zou; Xiao-Yi Liu; Le-Bing Wang; Yuan-Yuan Fan; Yang-Yang Li; Yi-Ran Chen; Wen-Wen Bao; et al. (Environmental Research, 2026)

Experimental and numerical research on ultimate bearing capacity of steel-concrete-steel composite deep beams with UHPC/ECC considering interfacial bonding - Youzhu Lin; Yazhe Zou; Ming Sun; Jiachuan Yan (Engineering Structures, 2026)

Interaction effect of pollutant degradation and copper transformation in the Cu(II)/PMS system: Overlooked complexation-enhancement role - Jiaxin Miao; Peng Xu; Ruoxi Wu; Lin Deng; Baolin Hou; Jing Zou (Chemical Engineering Journal, 2026)

Built-in electric field-driven d-band engineering in metal sulfide heterojunctions for high-efficiency electro-Fenton degradation of antibiotics - Xiangwei Zou; Yue Wang; Xinyu Wang; Lin Lin; Xiao-yan Li; Chitou Lei; Xiaojun Fan; Weng Ian Ieong; Qinfen Gu; Lianpeng Sun; Chao Yang (Chemical Engineering Journal, 2026)

Electro-driven aerobic biological nitrogen fixation for protein and ammonium production by Azotobacter vinelandii with sucrose as the sole carbon source - Liying Ren; Min Zhu; Chen Qi; Guohua Zou; Xinyue Wang; Wei Lu; Min Lin; Zhengfu Zhou; Yuhua Zhan; Yongliang Yan (Bioresource Technology, 2026)

Microbial-mediated soil carbon accrual under 12-year reduced nitrogen fertilisation and intercropping - Kepan Yang; Yali Liu; Chaoqun Zou; Jianghao Tan; Huiying Lin; Lei Liu; Xiting Zhang; Enqing Hou (Agriculture, Ecosystems & Environment, 2026)

Correction: The dynamic evolution of circulating tumor cells during glecirasib treatment predicts survival and resistance in gastrointestinal tumors with KRASG12C mutation - Lei Jiang; Yiming Luo; Huan Liang; Xujiao Feng; Yan Huang; Yanyan Li; Zhenghang Wang; Ting Xu; Heng Zou; Zhi Li; Lin Shen; Yang Chen; et al. (Human Cell, 2026)

Role of bedding angle in the anisotropic mechanical response of layered sandstone under monotonic and cyclic loading: implications for tunnels in layered rock masses - Kuan Zhang; Wei Wang; Xuelei Duan; Zhinan Lin; Shifan Liu; Lifang Zou (Transportation Geotechnics, 2026)

Urban heat on the move: How functional zoning and shifting populations intensify day–night exposure hotspots - Ruijun Chen; Siyuan Ren; Jiahao Lin; Yukai Zou; Qiuyi Xu; Weirong Zhang; Holly Samuelson (Sustainable Cities and Society, 2026)

Self-cleaning van der Waals lamination for two-dimensional electronics - Chang Liu; Shuimei Ding; Xudong Wang; Guichen Teng; Jinhua Zeng; Ying Zhang; Qianru Zhao; Huiting Wang; Binmin Wu; Shuaiqin Wu; Yan Chen; Tie Lin; et al. (Science Bulletin, 2026)

Large-scale field measurement of a floating offshore wind turbine under realistic sea conditions - Pengxu Zou; Qiang Wang; Wei Lin; Yipin Cheng; Fujing Wang; Xiang Wang; Shilong Sun; Yongshuai Zhu; Baiwen Liu; Yiran Wang; Zheng Dong; Ming Lin (Ocean Engineering, 2026)

PRISM: Turning prediction uncertainty into cost-effective management decisions for cadmium-contaminated rice - Ziqian Zhong; Qihong Zhu; Xinliang Liu; Shufang Pan; Lei Luo; Xin Luo; Hanhua Zhu; Rui Liu; Lin Zou; Daoyou Huang (Journal of Hazardous Materials, 2026)

Anthraquinone‑modulated oxygen disproportionation enables highly selective singlet oxygen generation for pollutant degradation - Yu Luo; Chenqi Lu; Chuang Xiao; Lin Ding; Mengyuan Zhao; Lingling Liu; Longshuai Zhang; Xibao Li; Fang Deng; Xubiao Luo; Jian-Ping Zou (Journal of Environmental Chemical Engineering, 2026)

Functional characterization of STING in large yellow croaker (Larimichthys crocea), a pivotal regulator associated with TRIF, TRAF3, IRF3, and IRF7 in modulating antiviral signaling - Yi Lin Li; Jia Xi Zhang; Jun Chun Tang; Ying Li; Xuan Zhu; Jian Zhong Han; Yong Hua Jiang; Yi Lei Wang; Peng Fei Zou (Fish & Shellfish Immunology, 2026)

Longitudinal trends in serum triclocarban levels from 2008 to 2018: Evidence from the prospective Dongfeng–Tongji cohort study - Caizheng Yu; Jiazhen Zhang; Hong Guo; Lin Liu; Jinglan Ma; Jiao Zou; Zhengyang Xiao; Zhewen Li; Yunqi Luo; Meian He (Environmental Research, 2026)

PM2.5 and constituents exacerbate decline of kidney function: The modification of glucose metabolism - Boxiang Wang; Lijuan Xu; Ren Lin; Hanxiang Cai; Yiman Zou; Yike Tong; Can Li; Feifei Liu (Environmental Research, 2026)

ANN-assisted interfacial engineering of MOFs heterostructures for synergistic CO2 photoreduction and antibiotic elimination - Fan Ye; Zhe Lin; Xu-Chao Xia; Ting Zou; Jin-Yu Dai; Lin Zhang; Xiu-Li Yang; Ming-Hua Xie (Chemical Engineering Journal, 2026)

Dual-functional isoquercitin‑silver nanoparticles alleviate bacterial-induced excessive inflammation of wound infection and sepsis - Guowei Zhong; Qianfeng Xu; Aidi Tong; Fen Zou; Chunyi Tong; Yangjia Zhuo; Jundong Lin; Wenjie Xie; Jianheng Ye; Jianming Lu; Bin Liu; Huichan He; et al. (Chemical Engineering Journal, 2026)

Cover crop mixtures composed of three functional groups enhanced ecosystem multifunctionality in a subtropical citrus orchard - Xinyu Zou; Hailin Zhang; Jiaxin Ren; Huiping Ou; Lin Yang; Xiaojun Shi; Jie Wang (Plant and Soil, 2026)
Aims Cover crops enhance agroecosystem multifunctionality by modulating biodiversity, yet knowledge of their functional diversity remains limited. This study aimed to systematically evaluate the effects of cover crop species richness (SR) and functional group richness (FGR) on ecosystem multifunctionality (EMF) in citrus orchards. Methods This study assessed 33 cover crop planting schemes in citrus orchards in Southwest China, using six species arranged in gradients of SR (1, 2, 3, 4, 6) and FGR (1, 2, 3). Seasonal variations in soil properties, cover crop yield, and weed biomass were measured. Individual ecosystem functions and EMF across SR and FGR gradients were evaluated. The Random Forest Model and Structural Equation Modeling identified key drivers and mechanisms of EMF. Results (1) Cover crop polycultures suppressed weeds, increasing seasonal cover crop yield by 10–30% compared to single-species cover crops. They reduced soil temperature in spring, summer, and autumn while increasing it in winter. (2) SR and FGR exhibited quadratic correlations with EMF. FGR had a stronger influence, maximizing EMF (Mmde = 13.66) at a lower threshold (Tmde = 77%), compared to SR (Mmde = 12.86, Tmde = 84%). (3) Key EMF predictors included cover crop yield, soil alkali-hydrolyzable nitrogen, weed biomass ( p < 0.01), and soil organic matter, temperature, urease activity (0.01 < p < 0.05). SR and FGR directly enhanced EMF via cover crop yield (0.51) and indirectly via reduced weeds biomass (-0.33). Yield and weed biomass further acted through soil properties (temperature: 0.06, organic matter: 0.09, alkali-hydrolyzable nitrogen: 0.26). Conclusions FGR manipulation outperforms SR for enhancing EMF, offering a sustainable citrus orchard management strategy.

Molecular phylogeny and taxonomy of Mus pahari (Rodentia: Muridae) - Qingfang Zou; Lin Gu; Tao Zhang; Chengxin Zhou; Xuming Wang; Tong Zhang; Keji Guo; Shaoying Liu; Shunde Chen (Mammalian Biology, 2026)

Pharmacogenomic screening strategy and indicative screening efficiency for antithyroid drug-induced agranulocytosis in the Southern Han Chinese - Li Ma; Sujie Ke; Peiji Huang; Yao Chen; Qian Lin; Menghua Lin; Guanlian He; Laiyu Zou; Xiaoling Chen; Xiaoying Liu; Libin Liu; Lijing Wang (European Journal of Clinical Pharmacology, 2026)

Correction: Phylogenetic analysis, genetic diversity, and epidemiology of pigeon paramyxovirus type 1 in China - Chuqi Huang; Shaoyu Tu; Wei Sheng; Zhihao Wang; Zhipeng Lin; Jing Qian; Jiahui Zou; Hongbo Zhou (Archives of Virology, 2026)

RHBDD2 Confers Insensitivity of Esophageal Squamous Cell Carcinoma to Cisplatin by Inhibiting Ferroptosis Through the Wnt3a/β-Catenin/FTH1 Axis - Youxiang Ding; Geng Tian; Minjie Zhang; Lin Zou (Cell Biochemistry and Biophysics, 2026)

The influences of light conditions on the quality maintenance of potted Phalaenopsis orchids during simulated transport condition - Shiqing Zou; Wanzhen Dai; Jiamiao Hu; Meixiang Chen; Xining Huang; Natthida Sriboonvorakul; Jim Junhui Huang; Baodong Zheng; Shaoling Lin (Postharvest Biology and Technology, 2026)

Ethylene signaling, pathogenesis-related proteins (PRs) and SlCBF1 collectively regulate Botrytis cinerea resistance in postharvest tomato fruit under low temperature conditions - Pan Shu; Zhiyuan Wang; Bingqing Qian; Zhiyin Yu; Qinlu Zheng; Xin Yao; Hongye Fu; Yuan Qing; Xiaojuan Yin; Pan Zou; Jing Li; Lin Shen (Postharvest Biology and Technology, 2026)

Robust burst bubble recognition in flotation froths via RGB-D imaging and depth-guided feature extraction - Lin Zhao; Zebin Zou; Binbin Dong; Lang Liu; Yongfang Xie; Shiwen Xie (Minerals Engineering, 2026)

Extrusion-shaped PEI@B/MC-M560 adsorbents for direct air capture: Balancing mechanical strength and CO2 adsorption efficiency - Yixuan Lu; Jinsheng Zou; Lingjun Tan; Heijin Chen; Junhao Lin; Linying Huang; Xuehua Shen; Zuotai Zhang; Feng Yan (Journal of Cleaner Production, 2026)

Orchestrating the oriented fibrous architecture in high-moisture soy protein extrudates via Tremella fuciformis stem dietary fiber - Changrong Wang; Jingyi Lin; Zhizhi Yang; Yiming Zou; Mengfan Lin; Yulu Li; Yixin Zheng; Zebin Guo (Food Research International, 2026)

Constructed wetlands with recycled glass pumice as substrate: Application in eel recirculating aquaculture systems - Jinghong He; Jiemei Wang; Jinzhi Zou; Hoi Leong Lee; Yanan Chen; Qiaodan Gan; Rongtai Lin; Junlv Chen; Ding Yuan; Yuhao Zhou (Chemical Engineering Journal, 2026)

ε-poly-l-lysine–grafted nanocellulose prepared by enzymatic oxidation for high-internal-phase Pickering emulsions and nutraceutical delivery - Huangjingyi Chen; Yujun Zou; Chong Tang; Qingyang Lin; Jie Wu; Orlando J. Rojas; Yimin Fan (Carbohydrate Polymers, 2026)

In-situ heterojunction on high-aspect-ratio cellulose nanocrystals for long-range charge transport in e-skin - Chenchen Shen; Weiwei Chen; Lin Guo; Yanrui Zou; Shuan Han; Ning Yu; Lin Gan; Jin Huang (Carbohydrate Polymers, 2026)

In-situ thiosulfate pretreatment enhances anaerobic fermentation of biodegradable plastic wastes into short-chain fatty acids: Degradation performance, microbial synergy and metabolic pathway - Boyi Cheng; Da Zhang; Qingshan Lin; Jinqi Jiang; Wugui Zou; Feixiang Zan; Shuai Zhou; Zongping Wang; Guanghao Chen; Gang Guo (Bioresource Technology, 2026)

Spontaneous plastome mutations in variegated plants occur predominantly in genes related to transcription and photosynthesis - Zhuoqiao Qiu; Boya Yi; Huajing Feng; Qi Zeng; Peishan Zou; Xirong Zheng; Jianzhong Ni; Manmei He; Ruiying Wang; Shuaixi Zhou; Kainan Ma; Shiou Yih Lee; et al. (Planta, 2026)

A regeneration system for Melastoma normale derived from leaf explants: a potential pathway for molecular breeding - Hong Chen; Beiyi Guo; Sixian Zeng; Xinggu Lin; Peishan Zou; Shiou Yih Lee; Guofeng Liu; Seping Dai (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)

Short-term hot spring balneotherapy ameliorates sleep disorders: wrist-worn wearable-assessed sleep improvement associated with neuroimmune, tryptophan metabolic and gut microbiome alterations - Xiao Zhang; Yue Zou; Xiao-qin He; Yi-hang Xu; Hong-xia Li; Fen Yang; Bao-chao Zhang; Lin-xuan Liao; Meng-xi Cao; Rui-xue Wang; Si-fan Hao; Meng-meng Wang; et al. (International Journal of Biometeorology, 2026)

The dynamic evolution of circulating tumor cells during glecirasib treatment predicts survival and resistance in gastrointestinal tumors with KRASG12C mutation - Lei Jiang; Yiming Luo; Huan Liang; Xujiao Feng; Yan Huang; Yanyan Li; Zhenghang Wang; Ting Xu; Heng Zou; Zhi Li; Lin Shen; Yang Chen; et al. (Human Cell, 2026)

Pseudostellaria heterophylla Extract Enhances the Immune Responses in Larimichthys crocea Against Pseudomonas plecoglossicida Infection - Kun Huang Han; Zi Min Li; Li Zhou; Dong Ling Zhang; Ying Li; Zhao Han Sun; Jia Chen; Zhi Deng Lin; Yan Bin Dai; Peng Fei Zou (Fishes, 2026)
Visceral white spot disease caused by Pseudomonas plecoglossicida poses a severe threat to large yellow croaker (Larimichthys crocea) aquaculture. This study investigated the immunomodulatory effects and underlying mechanisms of Pseudostellaria heterophylla extract against P. plecoglossicida infection in L. crocea. Fish were fed a basal diet supplemented with 1% P. heterophylla extract for 30, 45, and 60 days, followed by intraperitoneal injection with 200 μL P. plecoglossicida (1 × 104 CFU/mL). When the control group reached about 50% mortality, transcriptome sequencing of head kidney tissues was performed on the 45 and 60 days post-feeding of the treatment groups to analyze gene expression changes following bacterial infection. Survival rates of the treatment groups were 33.33%, 13.33%, and 20% higher than those of the control group at 30, 45, and 60 days post-feeding, respectively. Transcriptomic analysis revealed time-dependent transcriptional responses: in one group, 45 days post-feeding, 10 differentially expressed genes (DEGs) were identified (2 up-regulated and 8 down-regulated), whereas in another group, 60 days post-feeding, 893 DEGs were detected (417 up-regulated and 476 down-regulated). Functional enrichment analysis (GO, KEGG, and GSEA) demonstrated that DEGs were significantly enriched in immune-related pathways, including Toll-like receptor signaling, chemokine activity, Th1 and Th2 cell differentiation, hematopoietic cell lineage, and cytokine–cytokine receptor interaction. Key immune genes, including chemokines, Toll-like receptors, and T cell regulators, were significantly up-regulated. These findings indicate that P. heterophylla extract enhances both the specific and non-specific immune capabilities of L. crocea in a time-dependent manner, with prolonged supplementation eliciting more robust transcriptional activation of immune defense pathways. This study provides a scientific foundation for developing immunological prevention strategies against P. plecoglossicida infection in aquaculture.

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Experimental performance analysis of inland vessel remote operation: A case study on the Yangtze River - Tianyue Zou; Mao Zheng; Xiumin Chu; Mengxia Li; Shigan Ding; Kehao Zhang; Tuyuan Xu; Bowen Lin; Yougui Yang (Ocean Engineering, 2026)

Corrigendum to “Variations in soil fungal communities: Comparative insights from coniferous and mixed broadleaf-conifer forests” [Pedobiol. - J. Soil Ecol. 107 (2024) 151007] - Dexing Chen; Qiongyi Zhang; Siyu Chen; Yuqing Lin; Yuanming Zhu; Weiwei Sun; Mingjiu Chen; Shuangquan Zou; Xin Qian (Pedobiologia, 2026)

Elevated virulence in TCP-PAI carrying strains indicates the pathogenicity island’s important role in Vibrio mediterranei pathogenicity to bivalves - Xiaohui Zou; Haiyan Zhang; Sheng Liu; Junchao Xu; Zhihua Lin; Qinggang Xue (Journal of Invertebrate Pathology, 2026)

Hierarchically assembled UiO-66@PIL@PP core-shell catalyst: Synergistic integration of catalysis and CO2 enrichment for efficient cycloaddition - Zhenzhu Tang; Qian Zhang; Baowen Lin; Yunliang Yu; Yanbin Zeng; Chao Zou; Guanqun Xie; Xiaoxia Wang (Journal of Environmental Chemical Engineering, 2026)

Disrupting the lepidolite structure via low-temperature (NH4)2SO4 and Na2SO4 roasting: Achieving efficient co-extraction of lithium, rubidium, and cesium from lepidolite - Shuping Cheng; Zhipeng Rao; Jiezhong Zou; Junfeng Zhang; Guobiao Li; Huiquan Li; Ting Lai; Wanhai Xiao; Yong Lin; Tinggang Li; Dong Wang (Journal of Environmental Chemical Engineering, 2026)

Revealing performance and environmental thresholds of mangrove nature-based solutions: A nonlinear blue carbon response framework from coastal Hainan - Kaiyue Wang; Penghua Qiu; Dezhi Wang; Xinqing Zou; Meihuijuan Jiang; Tingting Si; Zhihang Wang; Yi Lin; Yanli Yang; Siang Wan; Yang Li (Journal of Environmental Management, 2026)

Potential structure-immunostimulatory activity relationship of Tartary buckwheat sprout pectic polysaccharides: Influences of molecular mass and esterification degree - Bo Li; Lin Zhang; Ding-Tao Wu; Qin Yuan; Shengpeng Wang; Mao-Ling Tan; Mei-Lin Feng; Yi-Chen Hu; Liang Zou; Zi-Peng Wang; Ya-Nan Cao; Jing-Wei Huang (Food Research International, 2026)

Integrated analysis of dynamic changes in volatile and non-volatile compounds in Chuan Chenpi (Citrus reticulata ‘Dahongpao’) during aging by GC-IMS and UPLC-MS/MS - Jialiang Zou; Huangsheng Zhang; Liang Zhao; Huanhuan Xu; Lin Chen; Hongping Chen; Fu Wang; Yuan Hu; Youping Liu (Food Chemistry, 2026)

New insights into light-dependent pathways and mechanisms of phosphorus removal in hypersaline microalgae-bacteria systems - Meiman Zhang; Shuohui Shi; Weimin Zou; Shuxuan Lin; Anqi Xiao; Jian Zhou (Environmental Research, 2026)

Different land use types around megacities contribute contrasting heavy metal pollution and health risks in soil-leaf vegetable systems - Ling Huang; Wen-Fei Chen; Yue-E Guan; Yan-Ping Pang; Sheng-Gong Yu; Lin Li; Qi Zou; Meng-Qiang Sun; Hang Wei; Zhi-Liang Chen (Environmental Research, 2026)

Melatonin safeguards embryo and blastoid development against oxybenzone toxicity via a mitochondrial-linked NAD+ and glucose metabolic axis - Yuying Xiong; Haiying Zhu; Han Xie; Yunqi Wu; Ruojin Shi; Xueling Zhang; Lin Zhu; Yiwen Wang; Ke Zhong; Lei Li; Yaming Meng; Minyu Xie; et al. (Environmental Pollution, 2026)

Boosting char formation in lignin aerogels via PN synergy: A route to flame retardancy and multifunctional performance - Jia-Hui Wang; Tao Gui; Shuang-Lin Zou; Qing-Hua Wang; Ying-Chun Xu; Rong Tan; Qiang Wang; Ling-Ping Xiao; Run-Cang Sun (Chemical Engineering Journal, 2026)

The chlorination mechanism of arsenic during the arsenopyrite decomposition: experimental and theoretical study - Chan Zou; Rui Liang; Huimin Liu; Zhong Lin; Chunbo Wang (Waste Disposal & Sustainable Energy, 2026)

Comparative Proteomic Insights into Low Molecular Weight Chitosan-Induced Drought Tolerance in Sugarcane - Gui Zhou; Xiao-Xia Liu; Li-Hang Qiu; Cheng-Lin Zou; Yang-Rui Li (Sugar Tech, 2026)

Potential Impact of Macromolecular Structure and Nanoscale Pore on Coal Matrix Subjected to Microwave–LN2 Freeze–Thaw Cycles - Xi Wu; He Li; Huihui Liu; Quanle Zou; Jiexin Lu; Junhui Mou; Baiquan Lin; Wei Yang; Jieyan Cao (Natural Resources Research, 2026)

Characterization of the ctgf Promoter from Nibea coibor and its Response to TGF-β1 During Collagen Synthesis in Swim Bladder Cells - Ailing Zou; Yuying Yuan; Lingling Zhu; Yu Zhang; Lanfei Xiao; Xiaobo Wen; Fan Lin (Marine Biotechnology, 2026)

Acupuncture improves neurological function in ICH rats via suppression of WNK-SPAK-NKCC1 signaling activation - Bai-Wen Zhang; Lei Zheng; Bing-Lin Kuang; Jia Zheng; Xue-Ping Yu; Xiao-Hong Dai; Wei Zou (Journal of Molecular Histology, 2026)

Spatiotemporal evolution and influencing factors of soil erosion sensitivity in the red soil region of Southern China - Jinhuang Lin; Jixing Huang; Weihan Zhu; Yongwu Dai; Yan Huang; Xiaoyan Yan; Fangfang Zou; Youquan Ouyang (Journal of Mountain Science, 2026)

Anomaly analysis and comprehensive evaluation of geochemical exploration for oil and gas in the Lindian area, Northern Songliao Basin - Xiaohui Lin; Fazhun Rong; Kewei Xu; Yu Zou; Wu Li; Yinjie Chen (Geosciences Journal, 2026)

Three-dimensional hierarchical CuCoAl-layered double hydroxide/Ti3C2 Schottky heterojunction for efficient visible-light degradation of ciprofloxacin - Zifei Gao; Ye Liu; Deke Wang; Baoyu Zou; Xingkang Yu; Yu Dong; Qing Li; Juanjuan Ma; Lin Liu; Chao Liu; Zhiwei Tong; Jun Hu (Applied Clay Science, 2026)

Flexible SERS tape: A plasmonic hybrid of AuNPs and layered K2Ti8O17 nanowire network for on-site detection of pesticide residues - Lin Xu; Mingru Cui; Zhongqi Ge; Ruikang Zou; Cong Wang; Pengfei Ni; Xi Huang; Bo Zhong; Lijuan Wang (Analytica Chimica Acta, 2026)

Evaluation of different types of isotope-labelled steroids based on liquid chromatography–mass spectrometry - Yameng Zhao; Luqi Sun; Pengshuai Zhang; Sen Xu; Shenghao Zhu; Lantao Zhang; Mingyang Hu; Jinglan Yu; Zhaocong Shang; Lin Zou; Wen Lei (Isotopes in Environmental and Health Studies, 2026)

Chemical constituents and ferroptosis inhibitory activity of the deep-sea-derived fungus Penicillium citrinum W24 - Cheng-You Lin; Yuan Wang; Tai-Zong Wu; Rong Chao; Zheng-Biao Zou; Li-Sheng Li; Tian-Hua Zhong; Xian-Wen Yang (Natural Product Research, 2026)

Computation-driven discovery of a next-generation canine monoclonal antibody for canine parvovirus therapy - Ying Li; Xiaoyu Zhang; Zhihao Wang; Mingqin Lin; Sheng Wang; Chengguang Zhang; Ling Zhao; Jiahui Zou; Hongbo Zhou (Veterinary Microbiology, 2026)

Powering long haul freight: hydrogen refueling station siting using pipeline infrastructure - Jialu Yang; Danesh Hosseinpanahi; Bo Zou; Jane Lin (Transportation Research Part D: Transport and Environment, 2026)

Ecological impact and risk assessment of tire wear particles: Status, challenges, and future perspectives - Jialin Lin; Gongduan Fan; Chengyu Yang; Jing Luo; Fangqi Song; Xinchi Jiang; Rusen Zou; Kai-qin Xu (Process Safety and Environmental Protection, 2026)

Learning to follow: An end-to-end deep learning approach for vision-based vessel control - Shigan Ding; Mao Zheng; Nan Hai; Xiumin Chu; Bowen Lin; Tianyue Zou; Kehao Zhang; Wubin Hua; Lingyu Fu (Ocean Engineering, 2026)

RDX as the sole nitrogen source affects the nitrogen metabolism in Rhodococcus sp. LMD - Songwei Hu; Mengdi Li; Yaya Huang; Yanchao Li; Songrui Zhang; Wenjia Li; Bing Lin; Jiaxin Zhengchen; Qi Lv; Xuanrui Shen; Huibin Zou; Fengbing Liang; et al. (Journal of Hazardous Materials, 2026)

Hydrochemical Characteristics, Water Quality, and Health Risk Assessment of Groundwater in Zhanjiang Area, Guangdong Province, China - Yongsheng Lin; Jinhui Liu; Shengzhang Zou; Yeyu Yang; Lianjie Fan; Li Lu (Water, Air, & Soil Pollution, 2026)

The vinculin-β-catenin axis promotes bone formation and repair: an essential prerequisite for the anti-osteoporotic efficacy of sclerostin-neutralizing antibody - Sixiong Lin; Chu Tao; Yishu Wang; Jianglong Li; YuJia Shi; Qinnan Yan; Yiming Zhong; Huanqing Gao; Tingxuan Wang; Yibo Wang; Qing Yao; Jianmei Huang; et al. (Science China Life Sciences, 2026)

A machine learning-based model for soil iron oxides estimation using fused hyperspectral and multispectral data - Yongshi Tan; Zhenxi Wei; Yan Xiao; Yulin Huang; Zongxin Li; Shuting Yang; Lin Zou; Lanhui Yang; Yusong Deng (Journal of Soils and Sediments, 2026)

Discovery and engineering of a new BvCas12a nuclease for mammalian genome editing and nucleic acid detection - Xuechun Shen; Lei Huang; Dan Wang; Chen Qi; Baitao Li; Chuan Liu; Ke Chen; Yuanqiang Zou; Liang Xiao; Yuan Jiang; Qiupeng Lin; Hongxia Lan; et al. (Science China Life Sciences, 2026)

Design and verification of a microbial consortium with an anchoring-interface enhancement strategy for efficient PAHs degradation in groundwater - Wang Kai Tong; Jiajun Hu; Chaomeng Dai; Jia Jie Zou; Han Tang; Piao Yi Jiang; Min-tian Gao; Jixiang Li; Xihua Wang; Yalei Zhang; Ken-Lin Chang; Kah Hon Leong; et al. (Water Research, 2026)

Near-surface ground ice map of the Northern Hemisphere - Bingquan Wang; Youhua Ran; Xin Li; Jan Hjort; Olli Karjalainen; Qingbai Wu; Yu Sheng; Huijun Jin; Defu Zou; Lin Zhao; Rui Ma; Ziyong Sun; et al. (Science Bulletin, 2026)

The crucial role of ground ice in slowing permafrost degradation - Guojie Hu; Zhe Sun; Lin Zhao; Deliang Chen; Defu Zou; Chien-Lu Ping; Wenxin Zhang; Yao Xiao; Guangyue Liu; Ren Li; Xiaodong Wu; Yifan Wu; et al. (Science Bulletin, 2026)

Data-driven reduced-order prediction modeling for cylinder vortex-induced vibrations in the subcritical Reynolds number regime - Jingyuan Wang; Li Zou; Guoqing Jin; Zongbing Yu; Maoyue Lin (Ocean Engineering, 2026)

Root traits determine the effects of organic amendments on soil aggregate organic carbon by regulating soil microbial multitrophic networks - Changdong HAN; Lin CHEN; Zhongjun JIA; Hongtao ZOU; Ling MA; Jingwang LI; Congzhi ZHANG; Guixiang ZHOU; Donghao MA; Jiabao ZHANG (Pedosphere, 2026)

Enhancement of MOF loading on fibrous membranes via construction of hierarchical porous structure for efficient uranium adsorption in aqueous solutions - Yiting Lin; Yuhan Zhang; Zhaoxuan Duan; Yufei Zou; Shanshan Li; Zhenbo Cao (Journal of Environmental Chemical Engineering, 2026)

Insights into the copigmentation effect and mechanism of five carbohydrates on thermal and color stability of mulberry anthocyanins - Qian Li; Xuanran Lin; Zhengguang Wang; Dongxu Xing; Fan Liu; Qingyi Wei; Yuxiao Zou (Food Chemistry, 2026)

Synergistic regulation of chalkiness reduction in ratoon season rice by ABA and ascorbic acid: A physiological perspective - Hailong Xu; Bianhong Zhang; Xin Wu; Yijiang Hu; Americ Allison; Bin Qin; Jinying Li; Chaojie Lan; Jingnan Zou; Yazhou Liu; Anqi Li; Qingyang Zhang; et al. (Field Crops Research, 2026)

Efficiency improvement of TOPCon half-cells and modules via laser-assisted edge isolation (LAEI) technology - Xukai Zhao; Zunke Liu; Biao Wu; Yi Liu; Xiaowei Liu; Hongping Jiang; Chaoyan Fang; Chen Lv; Yikun Liu; Shihua Chen; Wenli Yan; Wei Liu; et al. (Chemical Engineering Journal, 2026)

Cation-anion synergistic interactions in ion-regulated cholesteric liquid crystal Hydroxypropyl methylcellulose coatings for lithium metal batteries - Zhanpeng Du; Yun Huang; Fengliang Wang; Lei Zhang; Jing Tao; Jin Bao; Heguo Zeng; Jiajun He; Huihui Li; Chao Zou; Chunmei Feng; Bingshu Guo; et al. (Chemical Engineering Journal, 2026)

Lignin upgrading for sustainable materials and chemicals: From waste to functional bioplastics - Ying-Chun Xu; Shuang-Lin Zou; Qiang Wang; Ling-Ping Xiao (Bioresource Technology, 2026)

Benchmarking and lightweight correction of daily near-surface air temperature products over the Qinghai-Tibetan Plateau - Nan Zhou; Yao Xiao; Lin Zhao; Guojie Hu; Lingxiao Wang; Chong Wang; Ren Li; Guangyue Liu; Defu Zou; Xiangfei Li (Atmospheric Research, 2026)

Prey selection and foraging behavior of Eriocheir sinensis towards three freshwater mollusk species: Mechanisms and ecological implications - Yanming Sui; Aijia Lin; Weiwei Su; Weiyi Zou; Yiyun Zhang; Linlan Lv; Hucheng Jiang (Behavioural Processes, 2026)

Unraveling iron and zinc efficiency in pepper: integration of root architecture, uptake kinetics, and transcriptional regulation - Cheng-Xiang Zhou; Wei Zhang; Bao-Gang Yu; Hao-Feng Yang; Yuan Wang; Kai Sun; Fu-Lin Zhao; Huai-Yu Yang; Prakash Lakshmanan; Xin-Ping Chen; Chun-Qin Zou (Plant and Soil, 2026)

Electromyographic features for quantitative assessment of lower limb spasticity after stroke: a feasibility study - Lin Wu; Benjian Zou; Jiawei Liu; Chao Wang; Samit Chakrabarty; Ping Zhou; Tianzhe Bao; Sheng Quan Xie (Medical & Biological Engineering & Computing, 2026)

Opportunities or challenges? Upgrading of periphery space with the rise of platform urbanism: Live streaming commerce in Yangtze River Delta, China - Lin Zou; Yiwen Zhu; Simin Yan (Applied Geography, 2026)

Exploring the mechanism of flavonoid amination and its potential biological implications from an in-vitro and in-vivo perspective - Pengren Zou; Celia Costas; Rui Lu; Carla Cameselle; Shiye Lin; Fan Zhang; Zhaojun Wei; Paz Otero (Critical Reviews in Food Science and Nutrition, 2026)

Pectin of Olecranon Honey Peach Effects on Intestinal Health and the Mechanisms Involved in Hybrid Grouper (Epinephelus lanceolatus♂ × Epinephelus fuscoguttatus♀) - Jinhui Wu; Xiaoxiao Zhang; Qinguo Song; Feifei Huang; Tinghua Li; Zhendong Qin; Li Lin; Fei Shi; Huifan Liu; Cuiyun Zou (Fishes, 2026)
Water-soluble pectin (WSP) is a soluble dietary fiber with a high esterification degree and certain viscosity and emulsifying properties. It has diverse bioactivities—including antioxidant, anticancer, and anti-inflammatory properties. This study aimed to investigate the in vitro antioxidant mechanisms of water-soluble pectin, and the in vivo effects of intestinal antioxidant capacity and gut microbiota composition in hybrid grouper (Epinephelus lanceolatus♂ × Epinephelus fuscoguttatus♀). In an experiment involving feeding fish with WSP added to the diet, the addition of 600 mg/kg WSP promoted the activities of CAT, SOD, and GSH-Px in the grouper intestinal tract, thereby enhancing the antioxidant properties. At the phylum level, the relative abundance of Actinomycetes and Armatimonadetes decreased significantly. At the genus level, the relative abundance of Vibrio and Subdoligranulum increased significantly. In addition, antioxidant genes, inflammatory factor genes, immune genes, apoptosis genes, and genes of specific transmembrane proteins may participate in the regulation and improvement of the hybrid grouper intestinal tract. (CAT, MnSOD, and GPX), (TNF-α, IL-β, IL-6, and TGF-β), (MHC2, TLR3, KEAP1, and IKK-α), (C3, C8, C9, and P53), and (Claudin-3a, Occludin, ZO-1, and ZO-3) may regulate the intestinal function of hybrid grouper. Therefore, adding an appropriate volume of WSP to the diet is beneficial for the intestinal health of hybrid groupers.

Retraction Note: Tetraspanin 1 inhibits TNFα-induced apoptosis via NF-κB signaling pathway in alveolar epithelial cells - Lawei Yang; Yahong Wang; Zhanchun Pan; Shenglan Gao; Bao’an Zou; Ziying Lin; Dehui Feng; Changmei HuangFu; Gang Liu (Inflammation Research, 2026)

Isolation and biological evaluation of a novel steroid from Sagina japonica (Sw. ex Steud.) Ohwi - Jun-Hong Liu; Qian-Lian Yin; Xue Li; Mei Qing Zhang; Lin Guo Zou; Xin Jian Song; Li Jiang; Chun Hua Liu; Yong Jun Li (Natural Product Research, 2026)

Combinatorial microalgae drive nitrogen conversion and microbiota succession in different trophic biofloc systems, enhancing Litopenaeus vannamei performance under low salinity - Sheng Dong; Fei Huang; Yihong Zheng; Langli Lin; Yuchun Li; Xianghui Zou; Zhangli Hu (Aquaculture, 2026)

Interpretable data-driven modeling of total phosphorus dynamics from 2005 to 2024 in a large shallow lake - Weipeng Lin; Yongqiang Zhou; Ze Ren; Wei Zou; Hongwei Guo; Na Li; Yunlin Zhang; James Elser; R. Iestyn Woolway; Kun Shi; Guangwei Zhu; Boqiang Qin; et al. (Water Research, 2026)

Dynamic interplay between preferential and matrix flows enhances water circulation in rubber agroforestry soil profiles - Xiao-Jin Jiang; Guan-Yuan Ma; Sissou Zakari; Ashutosh Kumar Singh; Haofei Wang; Shi-Yi Wen; Xiai Zhu; Xin Zou; Zi-Qiang Yuan; Youxing Lin (Soil and Tillage Research, 2026)

Hyphosphere metabolic reprogramming in lipids and aromatic amino acids drives differential mycorrhizal growth promotion in trifoliate orange - Hao-Ran Jiang; Wan-Lin Fu; Ci Deng; Ying-Ning Zou; Mashael Daghash Alqahtani; Qiang-Sheng Wu (Rhizosphere, 2026)

Revealing speciation transformation and stabilization mechanisms of associated trace hazardous beryllium and thallium during lithium extraction: Achieving targeted detoxification of lithium slag - Shuping Cheng; Yong Lin; Yanxi Zeng; Guobiao Li; Jiezhong Zou; Zhihan Zhang; Zhi Wang; Tao Qi; Huiquan Li; Wanhai Xiao; Tinggang Li; Dong Wang (Journal of Hazardous Materials, 2026)

Machine learning-driven GC–MS analysis for assessing the contribution of amino acids in the flavor of cheese maturing at high temperature - Xinyue Hao; Junzhe Zou; Jianhua Zeng; Jian He; Baolei Li; Kai Lin; Huaxi Yi; Lanwei Zhang; Pimin Gong (International Journal of Food Microbiology, 2026)

Degassing in middle-crust magma chamber: Evidence from the texture and chemistry of the zonal clinopyroxene from the high magnesium basalt in Ganzhou Basin, Jiangxi, South China - Lin Jia; Guolin Guo; Yan Zhao; Zhaobin Yan; Jianhua Wu; Wenya Yan; Tingting Zou (Geochemistry, 2026)

Prenatal and postpartum residential greenness and behavioral development in early Childhood: Findings from a birth cohort - Wen-Chi Chao; Ming-Lun Zou; Chih-Da Wu; Jian-Pei Huang; Heng-Kien Au; Chen-Li Lin; Shih-Peng Mao; Hsing-Jasmine Chao; Ling-Chu Chien; Hsueh-Wen Hsu; Pilyoung Kim; Yi-Hua Chen (Environmental Research, 2026)

Exposure trends of neonicotinoids from 2008 to 2018 and health risk in a longitudinal study in China - Jiazhen Zhang; Hong Guo; Lin Liu; Jinglan Ma; Jiao Zou; Zhengyang Xiao; Zhewen Li; Yunqi Luo; Caizheng Yu; Meian He (Environmental Research, 2026)

Metabolomics-based investigation of PFOS-induced molecular perturbations across multiple rat organs - Tzu-Hsin Yen; Sheng-Han Lee; Hao-Jan Liang; Zou-Xiao Huang; Chi-Tsung Chen; Christopher Li; Ching-Yu Lin (Environmental Toxicology and Pharmacology, 2026)

Bioengineered functional scaffolds co-loaded with osteonectin and HA-internalizing osteoblasts for boosting bone regeneration - Wei Yang; Qin Zou; Chenxin Wang; Yuankun Ren; Rui Zhang; Mingyue Lin; Xueqi Zhang; Yu Liu; Boyang Wang; Wei Li; Li Jiang; Xiyu Li (Chemical Engineering Journal, 2026)

Development of multifunctional intelligent packaging based on plasma-modified starch and triple-crosslinked anthocyanin nanocomplexes for salmon preservation and freshness monitoring - Fanglei Zou; Miao Yang; Lin Chen; Daoyi Song; Junhua Wu; Wei Wang; Hongying Wang (Chemical Engineering Journal, 2026)

Polycyclic aromatic hydrocarbons-induced suppression of the PPARα/ACAA1 axis drives hepatic steatosis: Integrating epidemiology, network toxicology, and experimental validation - Haonan Cui; Peng Zou; Wang Yang; Shijun He; Jinyuan Shi; Ting Sun; Mengge Wang; Zhiyong Song; Hanni Guan; Tong Wang; Lei Sun; Qing Chen; et al. (Chemico-Biological Interactions, 2026)

High-resolution (30 m) mapping of permafrost distribution in the Genhe River Basin, Greater Khingan Mountains, Northeast China - Xueling Jiao; Lin Zhao; Defu Zou; Lingxiao Wang; Chong Wang; Yuanwei Wang; Guojie Hu; Erji Du; Yao Xiao; Guangyue Liu; Shibo Liu; Yuxin Zhang; et al. (Journal of Mountain Science, 2026)

BACH2 ameliorates cell apoptosis and autophagy as a molecular switch of BCL-2/Beclin-1 complex in myocardial infarction - Xiaolin Wang; Hongyuan Zhang; Xi Liu; Xinjie He; Mengying Cao; Wenhao Wang; Chao Yin; Lin Li; Shijun Wang; Cheng Yang; Pan Gao; Yunzeng Zou (Apoptosis, 2026)

Oligochitosan‐Ameliorated Gut Microbiome and Metabolic Homeostasis in Hybrid Groupers ( Epinephelus lanceolatu ♂ × Epinephelus fuscoguttatus ♀) Infected With Vibrio harveyi - Fei Shi; Lixin Ma; Zhilong Chen; Zhuojin He; Xiaomin Zheng; Cuiyun Zou; Chun Liu; Li Lin (Journal of Fish Diseases, 2026)
Vibrio infections cause enteritis in grouper fish, leading to high mortality and stunted growth, which is a major challenge for aquaculture. Oligochitosans, marine prebiotics with bioactive properties, have proven their potential for growth promotion and immune regulation. However, the impacts of Vibrio harveyi on the gut microbiome of grouper fish and the potential of oligochitosans to modulate these effects remain poorly understood. This study investigates the influence of oligochitosan on the gut morphology, microbiota and metabolic patterns of hybrid grouper following low‐dose infection with V. harveyi . After 8 weeks of feeding, infected groupers exhibited histopathological changes in the intestine that were mitigated by oligochitosan, as evidenced by improved villus height and intestinal wall thickness. Microbiome sequencing revealed that oligochitosan enhanced α‐diversity and shifted bacterial communities, particularly increasing the abundance of Fusobacteriota and Actinobacteriota . Furthermore, the prevalence of Shewanella and Vibrio , which were more abundant in infected groupers, was reduced upon oligochitosan treatment. Metabolomic analysis indicated that lipid metabolism pathways were significantly altered in response to infection and oligochitosan intervention. Overall, oligochitosan modulates the gut microbiome and metabolite profiles, potentially protecting against V. harveyi ‐induced intestinal dysbiosis and metabolic disorders in hybrid groupers.

Advanced technologies of artery-on-a-chip: a review of construction strategies and disease models - Shi-Qi Chang; Li Qiao; Oluwatosin David Abodunrin; Lin Zou; Ning-Ping Huang (Angiogenesis, 2026)

Research on real-time detection method of fish parasites based on the improved YOLO11n - Zhikang Lin; Xin Zhang; Yan Zhang; Juan Zou; Ting Wu; Ling Yang (Aquaculture, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

High sensitive and simultaneous determination of chlortetracycline hydrochloride and tetracycline hydrochloride residues in water using zero-crossing first derivative synchronous fluorescence spectrometry - Qihong Cai; Xiaodan Zheng; Sujun Fang; Qifeng Zou; Hang Zhu; Zhima Yangcuo; Yajuan Zhang; Yong Lin; Chunyan Lian; Shiqi Zhang (Process Safety and Environmental Protection, 2026)

Spatiotemporal evolution and dissipation mechanisms of tidal current turbine wake under different turbulence intensities - Tian Zou; Yajing Gu; Hongwei Liu; Zhiwei Song; Hongyi Lin; Yuquan Zhang (Ocean Engineering, 2026)

A new sponge (Ascospongiae) from the early Cambrian Guanshan Biota - Lin-Jun Zou; Joseph P. Botting; Jie Yang; Xiao-Yu Yang; Wei Li; Qing-Hao Guo; Yu Wang; Chun-Li Li; Xi-Guang Zhang; Ai-Lin Chen (Palaeoworld, 2026)

Constructing Ce–O–C covalent-bridged S-scheme heterojunction via molten-salt transformation of Ce-MOF for photocatalytic overall H2O2 synthesis - Ziying Feng; Pengjia Li; Dou Yang; Jingyi Yu; Yunyun Gui; Shao-Chuan Li; Yuan Lin; Junhua Zou; Lijun Liu (Journal of Environmental Chemical Engineering, 2026)

Dual mechanisms of mineral-microbial interactions in suppressing organic carbon sequestration in calcareous soils - Xi Yang; Donghao Ma; Ting Yang; Yongqi Zhang; Lin Chen; Hongwei Jiang; Bingru Chen; Nan Zhang; Hongtao Zou; Congzhi Zhang; Guixiang Zhou; Yanfang Zhou; et al. (Journal of Environmental Management, 2026)

Water quality and biofilm growth in drinking water distribution systems with the low-dose sodium hypochlorite disinfection after ultrafiltration pretreatment - Yu Zhou; Kangbing Zou; Xiaokai Wang; Zhihong Wang; Wei Song; Xing Du; Dachao Lin (Journal of Environmental Sciences, 2026)

Bacillus and lactic acid bacteria inoculation to transform kitchen waste using Hermetia illucens - Guoyou Deng; Min Yan; Shengzhi Yang; Lin Ji; Xinfeng Han; Xiumei Yu; Ke Zhao; Likou Zou (Journal of Environmental Sciences, 2026)

Effect of oxygen-containing functional groups on selenium removal by the carbonaceous adsorbent from MSW incineration flue gas - Shuaijie Yu; Shuai Li; Hongyun Hu; Linxia Gao; Zhong Lin; Chan Zou; Lu Dong; Yongda Huang; Hong Yao (Fuel, 2026)

Optimizing water and nitrogen management to balance yield and nitrogen loss in mechanically harvested low-stubble ratoon rice - Chaojie Lan; Hailong Xu; Bin Qin; Jinying Li; Bianhong Zhang; Jingnan Zou; Ting Chen; Jiahui Song; Zhihan Chen; Changxun Fang; Zhixing Zhang; Hongfei Chen; et al. (Field Crops Research, 2026)

Two birds with one stone: Constructing confined N-doped carbon catalysts to boost solar-driven interfacial water evaporation and peroxymonosulfate mediating antibiotic wastewater purification - Qi-E Zhang; Lin-Bo Deng; Hui-Qing Lv; Guo-Qing Zhao; Yan Pan; Jin Zou; Meng-Ting He; Xun-Kuan Ye; Jin-Gang Yu; Limin Lu (Environmental Research, 2026)

Evaluation of stability and cooling engineering effectiveness of the Qinghai-Tibet transportation routes: A first comprehensive assessment using space geodetic observations - Lingxiao Wang; Lin Zhao; Shibo Liu; Huayun Zhou; Guojie Hu; Defu Zou; Erji Du; Guangyue Liu; Yao Xiao; Yueli Chen; Jianting Zhao; Wei Chen; et al. (Engineering Geology, 2026)

A targeted therapy for salivary adenoid cystic carcinoma: A homologous bimetal nanoplatform via the cGAS-STING-mediated immunostimulation - Shaofeng Liu; Quan Zheng; Jingju Yin; Yue Huang; Gengsen Zou; Kun Song; Qi Lin; Jinxia You; Yunyang Liao; Bin Shi (Chemical Engineering Journal, 2026)

Scalable fabrication of Ti-based porous transport layers with straight-through pores for proton exchange membrane water electrolyzers - Xuewei Mao; Sihan Mao; Xiao Liang; Yun Liu; Yanhua Zhu; Weibing Lin; Qiannan Wu; Zihao Fan; Zhoubing Xie; Zhenye Kang; Xiaoxin Zou (Chemical Engineering Journal, 2026)

Oral cerium-based nanoplatform conjugated with gold to load anti-miR-301a for pH-transited multi-modal therapy of inflammatory bowel disease - Jiafeng Zou; Qingdong Ji; Xier Pan; Yiting Lin; Xinlin Zhao; Xinyi Chen; Liping Yang; Jing Lu; Shuhui Zheng; Zhuo Zhang; Kun Jiang; Feng Gao (Chemical Engineering Journal, 2026)

Advanced functionalization strategies of chitin and chitosan toward sustainable nanocomposites - Shuang-Lin Zou; Xin-Ran Liu; Jia-Hui Zhang; Ying-Chun Xu; Qiang Wang; Ling-Ping Xiao; Run-Cang Sun (Carbohydrate Polymers, 2026)

Unveiling the choroidal immune landscape revealed interferon-gamma and TNF-alpha as novel therapeutic targets in dry AMD - Lin Ye; Tujing Zhao; Huaping Tian; Runze Li; Zheng Li; Hongjing Li; Ruilin Liao; Junlan Chuan; Haojue Xu; Liang Zou; Chao Qu; Yi Shi; et al. (Science China Life Sciences, 2026)

Coeffects of iron oxides and phosphorus fractions on soil organic carbon stabilization in rubber-based tropical agroforests - Liping Wang; Chaoxian Wei; Bigui Lin; Xiwang Ke; Qinfen Li; Beibei Liu; Yukun Zou (Journal of Soils and Sediments, 2026)

Ocean acidification enhances TiO2 nanoparticle toxicity in Oryzias melastigma: Dominant role of size effects in driving bioaccumulation and hepatotoxicity - Lin Zhu; Li Zou; Mengchen Nie; Bin Xia; Jian Zhao; Qi Sui; Xuemei Sun; Baoshan Xing (Water Research, 2026)

The glutamyl-prolyl-tRNA synthetase 1 inhibitor halofuginone exerts synergistic antitumor effects with bortezomib in colon cancer cells - Han Lin; Ying Yan; Chenyu Qiu; Junqi Wang; Wenying Fu; Chongchong Shu; Yinghua Chen; Chenxin Xu; Shaotang Li; Yiqun Xia; Jundixia Chen; Yunzhi Chen; et al. (Toxicology and Applied Pharmacology, 2026)

Deep permeability architecture of a detachment fault: Constraints from in situ borehole samples in Triassic evaporite-carbonate sequences beneath the frontal Longmen Shan, China - Lin Zhang; Yi Li; Qingbao Duan; Shunjie Deng; Nianfa Yang; Huayao Zou; Jianye Chen; Zonghu Liao (Tectonophysics, 2026)

Spin valve effect in hybrid spin filters with Cr2Ge2Te6 - Xiaoyu Wang; Shuxi Wang; Ying Zhang; Yi Ding; Xueyan Dong; Lin Zou; Shaojie Liu; Miao He; Takashi Taniguchi; Kenji Watanabe; Xuan Pan; Lei Zhang; et al. (Science Bulletin, 2026)

Copper homeostasis: Crosstalk with plant secondary metabolism and stress responses - Muhammad Tanveer Akhtar; Zhaogeng Lu; Shi-xiong Ren; He-lin Zou; Iqra Noor; Biao Jin (Plant Science, 2026)

CFD data-driven CNN-LSTM for fast prediction of instantaneous flow characteristics in hydrocyclones - Dianyu E; Yuhao Zhang; Hongwei Hu; Guangtai Xu; Lin Liu; Jiaxin Cui; Cong Tan; Ruiping Zou; Shibo Kuang (Minerals Engineering, 2026)

Do biodegradable plastic residues pose lower ecological risks to crops than conventional plastic residues? A meta-analytic comparison - Feng Yuan; Teng Wang; Hongyu Chen; Yongcheng Ding; Jianguo Tao; Yue Xue; Linjie Zhang; Haiyan Lin; Baojie Li; Yifei Qiu; Guanghe Fu; Xinqing Zou (Journal of Hazardous Materials, 2026)

Reducing the healthcare carbon footprint through fully self-service artificial intelligence-powered screening: A comparative simulation study utilizing data from Shanghai City and Lixin Town, China - Yingyan Ma; Xiyuan Shi; Lina Lu; Yi Xu; Juzhao Zhang; Tao Yu; Yajun Peng; Enren Ke; Senlin Lin; Ru Guo; Haidong Zou (Journal of Cleaner Production, 2026)

Comparative studies on the peptide release, intestinal flora and metabolites changes of β-lactoglobulin- galactooligosaccharides/maltose conjugates during in vivo digestion - Kai Zhang; Lin Zou; Yan-hong Shao; Zong-cai Tu; Jun Liu (International Dairy Journal, 2026)

Oxy-ethane combustion: Measurements of the laminar burning velocities and kinetic insights into CO2 effects - Qianjin Lin; Bo Wei; Chun Zou; Alexander A. Konnov (Fuel, 2026)

Radioactivity of 14C, OBT, and TFWT in seafood from coastal areas of Zhejiang Province: Assessment of internal exposure to the public - Hong Ren; Kaiwen Tan; Feng Lin; Taotao Zheng; Xiaoxiang Ma; Peng Wang; Shunfei Yu; Hua Zou; Xinyu Gong; Yiyao Cao (Food Control, 2026)

Corrigendum to “Genome-wide identification, characterization, and expression analysis of scavenger receptor genes in orange-spotted grouper (Epinephelus coioides)” [Fish Shellfish Immunol. 167 (2025) 110671] - Feirong Yuan; Jiayao Wu; Siyi Liu; Yaorong Wang; Zhenjiang Zou; Yanhua Huang; Jinhui Wu; Haoran Lin; Shuisheng Li; Yong Zhang; Danqi Lu (Fish & Shellfish Immunology, 2026)

Machine learning-assisted sensor array based on enhanced dual enzyme-like activities of Fe SAzymes modulated via Pluronic surfactant for multi-category perfluoroalkyl intelligent recognition and quantification - Wen-Cai Jiang; Xiao-Mei Li; Jia-Hao Cheng; Li-Yao Xu; Ri-Za He; Gui-Lin Zou; Zhi-Bo Hou; Yan Zhao; Guo-Qi Zhang (Chemical Engineering Journal, 2026)

Exploring the role of VAV2 rare variants in primary open-angle glaucoma: genetic insights and pathophysiological mechanisms - Runze Li; Yuhong Chen; Shanshan Zhang; Lin Ye; Huaping Tian; Zheng Li; Wentao Wang; Hongjing Li; Ruilin Liao; Haojue Xu; Junlan Chuan; Chao Qu; et al. (Science China Life Sciences, 2026)

Unveiling β Subunit-Dependent Gating Defects in CaV2.1 Channelopathies: Investigation of a de novo CACNA1A Variant - Kunpeng Ma; Haiyan Chen; Li Chen; Shuainan Zhao; Huafang Zou; Dongfang Zou; Qi Zeng; Dezhi Cao; Jianyuan Sun; Lin Li; Xuefeng Shen (Neuroscience Bulletin, 2026)

A facile and sensitive protein immune polyacrylamide gel electrophoresis with online fluorescent imaging - Rui Zou; Zixian Yu; Jing Gao; Qiang Zhang; Yiren Cao; Xiaoyi Lin; Yibing Peng; Weiwen Liu; Jianguang Wu; Chengxi Cao (Analytica Chimica Acta, 2026)

Prioritizing alternative halogenated flame retardants in mangrove spiders: high maternal transfer toxicity outweighs low environmental burden - Qiang Xie; Lvyan Tan; Congmo Jin; Wei Wei; Fenglong Jia; Yuping Wu; Haoyu Jiang; Shichun Zou; Baowei Chen; Tiangang Luan; Lihua Yang; Li Lin (Archives of Toxicology, 2026)

Influence of oligochitosan on hepatic immune-metabolic homeostasis in hybrid grouper infected with Vibrio harveyi - Lixin Ma; Zhilong Chen; Zhuojin He; Xiaomin Zheng; Jiawen Lin; Jiayue Yin; Cuiyun Zou; Li Lin; Fei Shi (Aquaculture International, 2026)

Spatial distribution of vegetation type in the Genhe River Basin based on multi-source data - Zhinan Zhou; Chong Wang; Lin Zhao; Defu Zou; Guangyue Liu; Shibo Liu; Lingxiao Wang; Guojie Hu; Zanpin Xing; Erji Du; Yao Xiao; Xueling Jiao (International Journal of Remote Sensing, 2025)

A Novel, Dual-Response Chemosensor Based on Ferrocene Derivative for the Selective Detection of Al3+ Ions : Fluorescence and Electrochemical Signaling - Wenqin Liu; Yanping Liu; Zenghui Li; Santai Zou; Pingnan Wan; Yan Lin (Journal of Fluorescence, 2025)

AFP-GFuse: an antifungal peptide identification model with structural information fusion via multi-graph neural networks and cross-attention mechanism - Xiaomeng Lin; Ruiqi Liu; Aoyun Geng; Junlin Xu; Yajie Meng; Feifei Cui; Leyi Wei; Quan Zou; Zilong Zhang (Molecular Diversity, 2025)

Structure and biological activity of a novel polysaccharide from marine Cladosporium velox SCAU272 - Lingzhen Ye; Ke Xu; Youhong Li; Wenshen Lin; Lingshan Zou; Xiaoyong Zhang; Riming Huang; Jun Liu; Bin Wang (Natural Product Research, 2025)

Large-scale analysis of SARS-CoV-2 genomic data from sewage using eVarEPS reveals that amino acid mutations detected in sewage provide an early warning on population prevalence - Ziquan Lv; Chang Shu; Yulin Fu; Yinghui Li; Shisong Fang; Xiangjie Yao; Qinglan Sun; Kesheng Peng; Jian Lu; Guomei Fan; Dongmei Liu; Jinzhen Tang; et al. (Water Research, 2025)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Contact-induced high energy-dissipation array column for vibration suppression of deep sea mining tower - Shubin ji; Li Zou; Zhe Sun; Xueyu Wang; Maoyue Lin; Cong Wang; Yingjie Wei (Ocean Engineering, 2025)

Interfacial adsorption mechanism of a novel sodium morpholine dithiocarbamate depressant in selective flotation separation from chalcopyrite and molybdenite - Song Zou; Yue Lin; Zhiqiang Huang; Xinyang Yu; Guichun He (Minerals Engineering, 2025)

Comparison and application of machine learning, deep learning, and statistical analysis methods in estuarine saltwater intrusion forecasting - Fang Yang; Huazhi Zou; Qi Tang; Lei Zhu; Wenping Gong; Zhongyuan Lin (Journal of Hydrology, 2025)

Highly selective crystallization of uranium complexes for actinide partitioning in nuclear waste streams - Yarui Li; Guangtao Zhang; Xiaoyuan Zhou; Qing Zou; Jiarui Chen; Yunyi Cui; Peng Lin; Jian Lin (Journal of Environmental Chemical Engineering, 2025)

Functional characterization of the heat shock protein gene hsp78 in regulating carotenoid biosynthesis in the edible-medicinal fungus Cordyceps militaris - Zi-Qing Liang; Yi Zhao; Yong-Zhi Tan; Jie Wang; Yi-Lu Shao; Qian-Wang Zheng; Yuan Zou; Jun-Fang Lin; Mou-Tong Chen; Zhi-Wei Ye (Food Bioscience, 2025)

Genome-wide identification, characterization, and expression analysis of scavenger receptor genes in orange-spotted grouper (Epinephelus coioides) - Feirong Yuan; Jiayao Wu; Siyi Liu; Yaorong Wang; Zhenjiang Zou; Yanhua Huang; Jinhui Wu; Haoran Lin; Shuisheng Li; Yong Zhang; Danqi Lu (Fish & Shellfish Immunology, 2025)

Modulation of hepatic immune-metabolic pathways by oligochitosan in hybrid grouper infected with Edwardsiella ictaluri - Lixin Ma; Zhilong Chen; Zhuojin He; Xiaomin Zheng; Jiajia Li; Cuiyun Zou; Li Lin; Fei Shi (Fish & Shellfish Immunology, 2025)

Reducing lateral earth pressure of expansive soils on retaining walls using EPS geofoam inclusions: Field study and estimation approaches - Weilie Zou; Qi Xiang; Qiuyang Pei; Zhong Han; Yanfeng Zhuang; Yuliang Lin; Hao Zhang; Zhiren Dai; Hongri Zhang (Computers and Geotechnics, 2025)

Fungal mycelial pellet as a biosponge for bacterial immobilization: A novel biocarrier for synergistic adsorption-degradation of PAHs - Jia Jie Zou; Chaomeng Dai; Jiajun Hu; Wang Kai Tong; Hong Cheng Zhang; Min-tian Gao; Yalei Zhang; Zhi Li; Kah Hon Leong; Lang Zhou; Ken-Lin Chang; Swee Pin Yeap (Chemical Engineering Journal, 2025)

Ultra-stable Pd/NaInY catalyst with atom-dispersed indium modification of NaY zeolite for CO direct esterification to dimethyl carbonate - Yi-Jing Feng; Xiao-Yuan Tan; Jian Lin; Wen-Qiang Zou; Jing Sun; Zhong-Ning Xu; Guo-Cong Guo (Chemical Engineering Journal, 2025)

Covalent organic frameworks with synergistic linkages and functional groups boost electrochemiluminescence for sensitive detection of long non-coding RNA - Linlin Song; Lin Cui; Xiaoran Zou; Xueting Cao; Wenqi Chu; Wenjie Gao; Lin Cheng; Bing Sun; Chun-yang Zhang (Chemical Engineering Journal, 2025)

A pH-responsive and nitric oxide-producing nanocarrier for targeted therapy of melanoma - Shuai Cui; Qing Yu; Ziyuan Su; Yiting Han; Sujuan Wang; Xiangyu Zou; Lin An; Nannan Yin; Hao Hong; Dongzhi Yang (Chemical Engineering Journal, 2025)

Boosting hydrogen storage performances of MgH2 by using a Ni-MOF derived Ni/NiO@C composite containing Ni/NiO nanoheterojunctions - Qiuyu Zhang; Yinghui Li; Fengzhan Sun; Xi Lin; Zhigang Hu; Haiyan Yang; Jianxin Zou (Chemical Engineering Journal, 2025)

Effects of gum incorporation on the properties of sodium alginate-based composite hydrogel beads for encapsulating lactic acid bacteria - Ying-Ying Jing; Yun-Cheng Li; Yong-Qi Luo; Long-Hua Zou; Yuan-Mou Tang; Yu-Xi Lin; Fan-Bing Meng (Carbohydrate Polymers, 2025)

Associations Between Dietary Habits, Oral Microbiota, and Dental Caries in Adolescents - Haiyan Yue; Pei Shen; Qiumin Huang; Shuchun Lin; Jie Shen; Yetong Wang; Zhonghan Sun; Xinhe Qi; Yuzhou Jiang; Changzheng Yuan; Duohong Zou; Yan Zheng; et al. (Phenomics, 2025)

Correction: Fbxw8 is involved in the proliferation of human choriocarcinoma JEG-3 cells - Ping Lin; Jiejun Fu; Binjiahui Zhao; Feng Lin; Haifeng Zou; Leiyu Liu; Cheng Zhu; Hongmei Wang; Xiaoguang Yu (Molecular Biology Reports, 2025)

Analysis of the AP2/ERF transcription factor family in Eriobotrya japonica and its role in exogenous melatonin-mediated regulation of salt stress - Ling Zhu; Fuhua Liu; Xin Lin; Tianyu Fu; Lin Zou; Yuanhai Pan; Rong Zou; Yang Zhao; Hanyao Zhang (Functional & Integrative Genomics, 2025)

Comparative study on feeding habits, gonadal development and muscle nutritional value in triploid hybrids derived from blunt snout bream (Megalobrama amblycephala, ♀) × topmouth culter (Culter alburnus, ♂) - Guang-hai Dong; Zheng-nan Liu; Song-lin Chen; Yahui Feng; Jie Chen; Guodong Zheng; Shuming Zou (Aquaculture International, 2025)

Biogeochemical responses to the dynamic processes associated with the Equatorial Undercurrent in the tropical eastern Indian Ocean during April–May - Qinsheng Wei; Huiwu Wang; Yongliang Duan; Junchuan Sun; Teguh Agustiadi; Xiaomeng Duan; Yawen Zou; Lin Liu; Baodong Wang; Weidong Yu (Acta Oceanologica Sinica, 2025)

Seasonal water level fluctuations regulate the source, distribution, and risk of antibiotics in the largest floodplain-lake in China - Xiaolong Huang; Cong Wang; Yiting Chen; Meng Zhang; Muhammad Zaffar Hashmi; Tingting Sun; Borui Zou; Yuanyan Zhang; Jingjing Lin; Zhi Wang (Water Research, 2025)

Influence of parameters on dynamic characteristics of friction-induced self-excited vibration in the ship stern shaft seal - Yuze Yang; Xuebing Zhang; Lin Xue; Donglin Zou; Chunxiao Jiao; Jianghai Xu; Na Ta; Zhushi Rao (Ocean Engineering, 2025)

The distribution characteristics of marine litter in the intertidal zone of Lvhua Island and its impact on the macrobenthic community structure - Kaiyi Wang; Shuhan Wang; Jianing Sun; Qiao Zou; Jiaming Ou; Li Li; Shouyu Zhang; Xueping Lin; Kai Wang (Marine Environmental Research, 2025)

Quantifying the soil water content of the permafrost active layer using InSAR deformation - Erji Du; Lingxiao Wang; Lin Zhao; Huayun Zhou; Shibo Liu; Defu Zou; Guangyue Liu; Yao Xiao; Guojie Hu; Zhibin Li; Junqiang Gao; Chong Wang; et al. (Journal of Hydrology, 2025)

Assessment and prediction of ecological risk caused by anthropogenic activities during the implementation of China's ecological protection redline policy: A case study from the Yangtze River Delta - Jing Liu; Chaoxu Luan; Xiaojuan Xu; Yingying Zhu; Jie Qiu; Renzhi Liu; Naifeng Lin; Changxin Zou; Kun Zhang (Journal of Cleaner Production, 2025)

A safe and high-precision detection method for hydrogen leakage analysis of underground gas storage based on stimulated Raman spectroscopy of micro-nanofiber - Xianjian Zou; Shoulin Jiang; Zixue Luo; Tongtao Wang; Feifan Chen; Jian Ju; Shaoqun Lin; Wei Jin; Jianhua Yin; Chunhe Yang (Fuel, 2025)

Enhancing cyclodextrin glycosyltransferase-mediated potato starch modification via plasma-activated water and twin-screw extrusion treatment - Fanglei Zou; Hongyun Hao; Miao Yang; Chunming Tan; Lin Chen; Junhua Wu; Hongying Wang (Food Chemistry, 2025)

Mechanisms of high yield formation and carbon budget surplus in ratoon rice and its rhizosphere microecological responses - Jinying Li; Hailong Xu; Bin Qin; Bianhong Zhang; Mengying Chen; Peiying Weng; Chunlin Guo; Chaojie Lan; Jingnan Zou; Zhimin Lin; Wenfang Lin; Wenfei Wang; et al. (Field Crops Research, 2025)

Heat exposure and adverse birth outcomes: Modification by residential greenness in a 14-year prospective cohort study in Taiwan - Ming-Lun Zou; Shih-Chun Candice Lung; Chih-Da Wu; Jian-Pei Huang; Heng-Kien Au; Yi-Yong Chen; Hsing-Jasmine Chao; Shih-Peng Mao; Pilyoung Kim; Wen-Yi Lin; Yi-Hua Chen (Environmental Research, 2025)

The reverse osmosis desalination system driven by the marine current turbine under dynamic conditions - Yajing Gu; Tian Zou; He Ren; Hongwei Liu; Yonggang Lin; Zhiwei Song; Kenan Ye (Desalination, 2025)

General strategy for efficient persistent RTP polymer over 3 s: luminophore with a moderate θn-π angle - Danman Guo; Tong Zou; Yiling Miao; Jinzheng Chen; Zhu Chen; Xiangyu Ge; Faxu Lin; Yi Zhang; Zhenguo Chi; Zhiyong Yang; Huahua Huang (Chemical Engineering Journal, 2025)

Platinum-copper nanocubezyme facilitate spinal cord recovery via synchronously alleviating oxidative stress and mitigating BNIP3-mediated mitochondrial dysfunction - Xiangge Liu; Cheng Peng; Huiyi Yang; Jiajun Deng; Ping Wu; Yongchun Xiao; Li Wan; Ke Wang; Guowei Zhang; Hua Yang; Jianyu Zou; Judun Zheng; et al. (Chemical Engineering Journal, 2025)

A hydrogen-based indigenous bacterial and algal biofilm system for enhanced nutrient removal in oxidation ponds - Si Pang; Lin Yang; Min Cai; Xu Zhang; Naxin Cui; Li Zhou; Guoyan Zou (Chemical Engineering Journal, 2025)

Interfacial heat conduction enhancement mechanism between CNTs encapsulated with LCC - Hanying Zou; Yanhui Feng; Lin Qiu (Chemical Engineering Journal, 2025)

Numerical simulation study on the motion characteristics and impact intensity of Wangjiayan landslide - Zhenyu Wang; Gaowei Yue; Haixiao Lin; Chenglu Zou (Bulletin of Engineering Geology and the Environment, 2025)

The effect of construction measures on the seismic performance of a frame-infilled wall with fabricated constructional column - Shucheng Yuan; Haifeng Lin; Haibo Luo; Zhanyuan Zhu; Zuyin Zou; Wei Liang; Zhuoying Wang; Bing Ma; Jinxin Yao; Qichao Zhang; Jiangfeng Dong; Hwa Kian Chai (Bulletin of Earthquake Engineering, 2025)

Hydrogen Production Power Supply with Low Current Ripple Based on Virtual Impedance Technology Suitable for Offshore Wind–Solar–Storage System - Peng Chen; Jiajin Zou; Chunjie Wang; Qiang Fu; Lin Cui; Lishan Ma (Journal of Marine Science and Engineering, 2025)
Hydrogen production from water electrolysis can not only reduce greenhouse gas emissions, but also has abundant raw materials, which is one of the ideal ways to produce hydrogen from new energy. The hydrogen production power supply is the core component of the new energy electrolytic water hydrogen production device, and its characteristics have a significant impact on the efficiency and purity of hydrogen production and the service life of the electrolytic cell. In essence, the DC/DC converter provides the large current required for hydrogen production. For the converter, its input still needs the support of a DC power supply. Given the maturity and technical characteristics of new energy power generation, integrating energy storage into offshore energy systems enables stable power supply. This configuration not only mitigates energy fluctuations from renewable sources but also further reduces electrolysis costs, providing a feasible pathway for large-scale commercialization of green hydrogen production. First, this paper performs a simulation analysis on the wind–solar hybrid energy storage power generation system to demonstrate that the wind–solar–storage system can provide stable power support. It places particular emphasis on the significance of hydrogen production power supply design—this focus stems primarily from the fact that electrolyzers impose specific requirements on high operating current levels and low current ripple, which exert a direct impact on the electrolyzer’s service life, hydrogen production efficiency, and operational safety. To suppress the current ripple induced by high switching frequency and high output current, traditional approaches typically involve increasing the output inductor. However, this method substantially increases the volume and weight of the device, reduces the rate of current change, and ultimately results in a degradation of the system’s dynamic response performance. To this end, this paper focuses on developing a virtual impedance control technology, aiming to reduce the ripple amplitude while avoiding an increase in the filter inductor. Owing to constraints in current experimental conditions, this research temporarily relies on simulation data. Specifically, a programmable power supply is employed to simulate the voltage output of the wind–solar–storage hybrid system, thereby bringing the simulation as close as possible to the actual operating conditions of the wind–solar–storage hydrogen production system. The experimental results demonstrate that the proposed method can effectively suppress the ripple amplitude, maintain high operating efficiency, and ultimately meet the expected research objectives. That makes it particularly suitable as a high-quality power supply for offshore hydrogen production systems that have strict requirements on volume and weight.

Two new alkaloids identified from herb Delphinium trichophorum French, a famous Tibetan drug “Gebu Dilu” - Siyuan Liu; Yuansheng Zou; Zeren Dawa; Fangle Liu; Meiqi Wang; Chenchen Zhu; Chaozhan Lin (Natural Product Research, 2025)

Association of PROP bitter taste sensitivity with anhedonia and emotional eating in the Chinese population - Keying Lin; Yuying Chen; Yue Hua; Jiubo Zhao; Laiquan Zou (Appetite, 2025)

The SDGSAT-1 mission and its role in monitoring SDG indicators - Huadong Guo; Changyong Dou; Dong Liang; Bihong Fu; Hongyu Chen; Ziming Zou; Peng Huang; Xiaoming Li; Fansheng Chen; Chengshan Han; Juanjuan Jing; Tai Hu; et al. (Remote Sensing of Environment, 2025)

Research on the calculation methods for time-domain friction excitation force in mixed lubrication contact between ship shaft and bearings - Chang-Gang Lin; Hao Wang; Can Sima; Yan-Feng Han; Wei-peng Zhang; Ming-Song Zou (Ocean Engineering, 2025)

The impacts of polypropylene microplastics on carbon and nitrogen cycling in coastal wetlands: Field evidence - Feng Yuan; Yue Xue; Zhuoyue Zhang; Jianguo Tao; Yuyang Song; Hongyu Chen; Qihang Liao; Haiyan Lin; Ming Lu; Yongcheng Ding; Teng Wang; Ruize Yang; et al. (Journal of Hazardous Materials, 2025)

Physical protection by soil aggregates drives carbon gains in mangrove restoration: Evidence from coastal aquaculture ponds - Ning Hou; Xiaolei Yin; Weiqi Wang; Xiang Yang; Yuan Li; Yuanchun Zou; Zhaoliang Song; Shaoying Lin; Zhineng Xiao; Rongbin Yin; Fanjiang Zeng; Zhihao Zhang; et al. (Journal of Environmental Management, 2025)

Cu-MOFs nanozyme with POD-like activity for the enrichment, identification, and intelligent colorimetric detection of omethoate - Xueer Lin; Jiahui Zou; Guancheng Zhu; Linfeng Pang; Yuqi Chen; Yanyan Huang (Food Bioscience, 2025)

Dynamic characteristics of a clayey soil under different moisture-temperature cycling conditions - Zhong Han; Lin Zhang; Erxun Wu; Luqiang Ding; Huaiping Feng; Zhiren Dai; Weilie Zou (Engineering Geology, 2025)

Hyperlocal disaster damage assessment using bi-temporal street-view imagery and pre-trained vision models - Yifan Yang; Lei Zou; Bing Zhou; Daoyang Li; Binbin Lin; Joynal Abedin; Mingzheng Yang (Computers, Environment and Urban Systems, 2025)

Molten salt in situ reconstruction realizes ultrafast charge transfer at cobalt-doped-CeO2/CeO2 S-scheme interface for photocatalytic H2O2 production - Yuan Lin; Ziying Feng; Pengjia Li; Shao-Chuan Li; Junhua Zou; Yunyun Gui; Lijun Liu (Chemical Engineering Journal, 2025)

A 3D-printed chitosan-based pH-responsive dual functional scaffold for osteomyelitis: synergistic antibacterial and osteogenic treatment - Mingyue Lin; Yijing Stehle; Li Chen; Mao Yang; Ke Zeng; Chenxin Wang; Rui Zhang; Huanshuo Zhang; Jiehui Yang; Denglang Hu; Min Huang; Yubao Li; et al. (Carbohydrate Polymers, 2025)

Lactiplantibacillus plantarum RS20D Alleviates Male Reproductive Toxicity Induced by Pubertal Exposure to Di-n-butyl Phthalate and Mono-n-butyl Phthalate - Yuan-ting Zhu; Xing-jie Wang; Shu-liang Liu; Jing-hui Lai; Jian-long Li; Qin Li; Kai-di Hu; Ai-ping Liu; Yong Yang; Li He; Shu-juan Chen; Xiao-lin Ao; et al. (Probiotics and Antimicrobial Proteins, 2025)

Redox condition and litter quantity co-determine soil carbon mineralization: Implications for carbon sequestration in restored wetlands - Lei Qin; Chris Freeman; Yuanchun Zou; Lin Wang; Ming Jiang (Applied Soil Ecology, 2025)

Threshold-governed insulating and cooling effects of snow cover on alpine permafrost: evidence from the Qinghai–Tibet Plateau - Yao Xiao; Guojie Hu; Ren Li; Tonghua Wu; Xiaodong Wu; Guangyue Liu; Defu Zou; Zanpin Xing; Jimin Yao; Chong Wang; Lin Zhao (Agricultural and Forest Meteorology, 2025)

Closed-loop recycling of lead iodide precursor from waste organic solvents in the production of perovskite solar cells: Toward sustainable photovoltaics - Qingfang Zou; Zifan Lin; Zhaoyang Li; Guang Hu; Shifa Zhou; Ying Zheng; Liang Huang; Sha Liang; Huabo Duan; Shushan Yuan; Chao Chen; Ling Xu; et al. (Waste Management, 2025)

A next generation probiotic, Bacteroides xylanisolvens - Chunhua Chen; Qixing Nie; Qiongni Lin; Jianqiao Zou; Shaoping Nie (Trends in Food Science & Technology, 2025)

Dimeric citrinins diversity revealed by the deep-sea-derived Penicillium citrinum W23 - Tai-Zong Wu; Zhi-Hui He; Cheng-You Lin; You Li; Zheng-Biao Zou; Chun-Lan Xie; Tian-Hua Zhong; Xian-Wen Yang (Phytochemistry, 2025)

Alternative splicing of OsNPR3 promoted by the bacterial TAL effectors-targeted splicing regulator OsRBP11 antagonizes OsNPR1 function and enhances disease susceptibility in rice - Xiaochen Chen; Xiaohui Yao; Fang Yan; Shaofang Li; Zuo-Dong Wang; Fu-You Yin; Miao Zhou; Zhen Wang; Lina Qin; Baoguo Zhao; Kai Lu; Liyuan Zhang; et al. (Molecular Plant, 2025)

H3K18 lactylation drives the progression of silica nanoparticles-induced pulmonary fibrosis via promoting macrophage M1 polarization - Lili Shi; Lin Zhang; Zhenfang Ma; Zhaohui Hu; Zihan Geng; Hao Liu; Jingyuan Wang; Ke Feng; Yiheng Geng; Yan Liu; Cunhui Zhang; Yujia Xie; et al. (Journal of Hazardous Materials, 2025)

UPLC-ESI-MS/MS-based chemometric approach for investigating the effect of conventional versus modern extraction methods on polyphenols recovery from grape seed wastes - Shengxiong Chen; Yi Yuan; Fan Zhang; Shiye Lin; Pengren Zou; Mohamed A. Farag; Jesus Simal-Gandara; Hui Cao; Jianbo Xiao (Food Chemistry, 2025)

Improving the moving-grid permafrost model to reveal ground deformation and hydrothermal effects caused by permafrost evolution in the source region of the Yangtze river on the Qinghai-Tibet plateau - Zhe Sun; Lin Zhao; Guojie Hu; Shibo Liu; Yongping Qiao; Erji Du; Defu Zou; Guangyue Liu; Lingxiao Wang; Jianting Zhao (Environmental Modelling & Software, 2025)

Urea-engineered magnetic ZnFe2O4/Bi2S3 heterojunction for SPC-activated photocatalytic Fenton-like degradation of sulfadiazine - Junge Xu; Haoying Guo; Dong Wang; Yanfang Li; Yuan Lin; Weihao Yu; Yingmu Wang; Rusen Zou; Xiaoping Gao; Baoling Yuan (Chemical Engineering Journal, 2025)

Activation rate-dependent reconstruction of Co-MOFs for efficient CoOOH conversion in oxygen evolution reaction - Youlei Feng; Jinzhi Jia; Zehua Zou; Youxiu Lin; Xuan Zheng; Wenqiang Lai; Xiaoping Chen; Qingxiang Wang; Cailing Xu (Chemical Engineering Journal, 2025)

Hollow p-n heterostructures with vacancy engineering to enhance Z-scheme photocatalytic CO2 reduction - Zhitao Zou; Yaxin Wang; Tianyi Zhang; Jing Lu; Vladimir Turkevich; Yueqin Yu; Jixiang Xu; Haifeng Lin; Yanyan Li; Lei Wang (Chemical Engineering Journal, 2025)

Scalable synthesis of anatase TiO2 nano-in-micro spheres for hybrid sodium-ion capacitors - Zerui Yan; Sicheng Fan; Xia Zou; Qinyao Jiang; Dafu Tang; Kun Lan; Jiaxin Li; Yingbin Lin; Zhigao Huang; Dong-liang Peng; Qiulong Wei (Chemical Engineering Journal, 2025)

Cellulose nanocrystal-modified hydrogel wearable sensor with self-healing function from dynamic bond and controllable dual hydrogen-bond crosslinking - Ruihuan Gu; Weiwei Chen; Yanrui Zou; Tingting Yang; Zirui Liu; Ning Yu; Jin Huang; Lin Gan (Carbohydrate Polymers, 2025)

Halomonas sp. NEC-1, an ectoine-rich and wide pH tolerant halophilic bacterium isolated from a salt lake of Xizang, China - Yingchao Ma; Zhongshi Sun; Tashilhamo; Yukang Li; Hanying Zou; Yuanliang Zhao; Feiyang Lin; Xuekai Han; Liying Sui; Chi Zhang (Journal of Oceanology and Limnology, 2025)

Anti-disintegration property of red soil treated with building gypsum powder - Yinlei Sun; Zhen Li; Xuan-Chen Lin; Qing-Ru Du; Xi Zou; Xianwei Zhang (Applied Clay Science, 2025)

Evaluating the sustainability potential of perennial rice in southeastern China by comparing yield, environmental impacts and economic benefits - Hailong Xu; Bianhong Zhang; Bin Qin; Jinying Li; Chaojie Lan; Jingnan Zou; Yazhou Liu; Chunlin Guo; Zhimin Lin; Qiaohong Fan; Changxun Fang; Zhixing Zhang; et al. (Agriculture, Ecosystems & Environment, 2025)

Pharmacokinetic study of Vibrio parahaemolyticus phage Фvp140 in Litopenaeus vannamei following oral administration - Di Fang; Laizhuang Jin; Qianhui Song; Xiong Zou; Lei Feng; Letian Li; Hui Zhang; Kun Hu; Mao Lin; Wenhong Fang (Aquaculture, 2025)

Dual-emission fluorescent probe with sequential two-step ESIPT activation mechanism for selective hydrazine detection and multifunctional applications - Hanxun Zou; Guoming Lin; Yuxuan Bao; Jie Liang; Yunyun Li; Lifeng Cai; Han-Ying Wu; Fan Yang; Hang Chen; Xiuchun Lin; Yi-Hong Xiao; Lei Yang; et al. (Journal of Hazardous Materials, 2025)

Distribution of and associations between ARGs and pathogenic bacteria in soils affected by heavy metal contamination in mining areas - Yanbin Du; Yijia Liu; Caihong Yu; Xuesong Hu; Suya Ma; Jiacheng Zou; Ronghua Lin; Yanhua Hou; Menglun Wang; Nan Zhang (Journal of Environmental Chemical Engineering, 2025)

Glycation of β-Lactoglobulin with different lengths sugar chains: Impacts on structure, allergenicity and flavor profile - Wen-mei Chen; Lin Zou; Yan-hong Shao; Zong-cai Tu; Jun Liu (Food Chemistry, 2025)

Cu-doped ZiF-8 and calcined UIO-66-based biomimetic enzyme electrochemical sensor for rapid and sensitive detection of Zearalenone in vegetable oil - Lin Zhiyuan; Kong Fanzhuo; Zhang Yuyang; Kouiti Oussama; Suo Hongbo; Huang Rubing; Zou Bin (Food Chemistry, 2025)

Rheological and tribological properties of skimmed milk gels: The impact of fish collagen peptides-polysaccharides complexes during acidification - Xiaoxuan Zhang; Shijie Wan; Shuojia Liang; Yuanyuan Jiang; Xueke Chen; Yijiao Zou; Cuilan Fang; Xiang Lu; Yun Zhou; Guohua Zhao; Lin Lei (Food Chemistry, 2025)

Elucidating the cleavage patterns of allergenic epitopes of Parvalbumin by L. helveticus fermentation through cell envelope proteinase hydrolysis and computer simulation - Qingwen Liu; Shuai Ma; Hao Wang; Wenye Zhu; Shanyu Peng; Hao Zou; Pingyuan Zhang; Zhenxing Li; Ziye Zhang; Hong Lin (Food Chemistry, 2025)

Self-healing carboxymethyl chitosan hydrogel with anthocyanin for monitoring the spoilage of flesh foods - Fuyuan Ding; Lin Fu; Xiaowei Huang; Jiyong Shi; Megan Povey; Xiaobo Zou (Food Hydrocolloids, 2025)

Advanced materials for combined photodynamic and immunotherapy: Mechanisms and translational opportunities - Suizhi Zou; Kehua Hu; Xiaowan Guo; Lin-Lin Bu; Hui Qiu; Qiuji Wu (Chemical Engineering Journal, 2025)

Incorporating zinc coordination driven nanozyme into chitosan and hyaluronic acid based nanoplatform for scavenging H2S/ROS in managing inflammatory bowel disease - Jiafeng Zou; Wenxing Ding; You Chen; Xier Pan; Xiuzhi Fu; Shulei Zheng; Yiting Lin; Chuanhe Xia; Ying Ma; Xiaochun Zhang; Shuang Wu; Feng Gao (Carbohydrate Polymers, 2025)

The effects of aerosol on the growth of hydrometeors in deep convective clouds - Xinyi Lin; Qian Chen; Zeyong Zou; Ying He; Chunsong Lu; Zhiliang Shu (Atmospheric Research, 2025)

Genomic insights into mechanism underlying virulence variations between Vibrio mediterranei strains different in pathogenicity toward bivalves - Haiyan Zhang; Xiaohui Zou; Jingjie Hu; Sheng Liu; Congling Fan; Wenfang Dai; Zhihua Lin; Qinggang Xue (Aquaculture, 2025)

Bclaf1 mediates super-enhancer-driven activation of POLR2A to enhance chromatin accessibility in nitrosamine-induced esophageal carcinogenesis - Xiangjun Zhou; Xueqiong Zhou; Jun Li; Yingzheng He; Shizhen Qiu; Ye Xu; Zeyu Liu; Yina Yao; Jia Liu; Ying Wen; Sitong Xie; Jialong Chen; et al. (Journal of Hazardous Materials, 2025)

Effects of different soluble dietary fibers on oil encapsulation: Comparison of emulsion and microcapsule properties - Xiaoqiang Zou; Yuechao Pan; Jijie Hu; Kang Zhang; Xiaotian Yang; Janice Adaeze Nwankwo; Xiusheng Guo; Yunzhuoya Lin; Wenxue Liu (Food Chemistry, 2025)

Joint effects of rice straw-derived biochar and microcystin-LR on splenic histopathological injuries, inflammation, and innate immune responses in male zebrafish - Wang Lin; Ling Liao; Ling Ling; Wansheng Zou; Pengling Shi; Suqin Wang; Pinhong Yang; Jifeng Yang (Fish & Shellfish Immunology, 2025)

Current status and research progress of sugarcane stem borers management - Jin-Da Wang; Huan-Tai Lin; Xian-Kun Shang; Hong-Li Shan; Ji-Hu Li; Xue-Hong Pan; Jiong Yin; Cheng-Wu Zou; Bao-Shan Chen; San-Ji Gao (European Journal of Agronomy, 2025)

Predicting long-term urban overheating and their Mitigations from nature based solutions using Machine learning and field measurements - Jiwei Zou; Lin Wang; Senwen Yang; Michael Lacasse; Liangzhu (Leon) Wang (Energy and Buildings, 2025)

Fire ant-inspired bone repair breakthrough: Self-assembly strategy of microspheres driven by physical hydrogen bonding and hydrophobic interactions - Rui Zhang; Yijing Stehle; Li Chen; Ke Zeng; Mingyue Lin; Chenxin Wang; Huanshuo Zhang; Jiehui Yang; Denglang Hu; Min Huang; Mao Yang; Yubao Li; et al. (Chemical Engineering Journal, 2025)

The surface features and internal structure of an integrated open system pingo in the source area of the Yangtze River on the Qinghai-Tibet Plateau - Guangyue Liu; Yao Xiao; Guojie Hu; Tonghua Wu; Xiaodong Wu; Lingxiao Wang; Changwei Xie; Defu Zou; Erji Du; Yonghua Zhao; Yingying Lu; Lin Zhao (CATENA, 2025)

A century of advances in molecular genetics and breeding for sustainable resistance to rice blast disease - Xilai Huang; Wei Yao; Qianru Chen; Jinjun Lin; Jun Huang; Yuying Zou; Chenglong Guo; Bei He; Xiao Yuan; Chengyang Xu; Xionglun Liu; Yinghui Xiao; et al. (Theoretical and Applied Genetics, 2025)

Drying–rewetting cycles determine maize growth by shifting microbial community assembly and coexistence patterns - Ling Ma; Guixiang Zhou; Lin Chen; Zhongjun Jia; Hongtao Zou; Congzhi Zhang; Donghao Ma; Changdong Han; Jiabao Zhang (Plant and Soil, 2025)

A study of frictional instability induced by fluid injection for the granite fracture - Bing Bai; Hang Lin; Hengtao Yang; Yan Zou (Bulletin of Engineering Geology and the Environment, 2025)

Estimation of rice yield using multi-source remote sensing data combined with crop growth model and deep learning algorithm - Jian Lu; Jian Li; Hongkun Fu; Wenlong Zou; Junrui Kang; Haiwei Yu; Xinglei Lin (Agricultural and Forest Meteorology, 2025)

Silencing ribosome biogenesis regulator 1 homolog (RRS1) inhibits angiogenesis and cisplatin resistance of lung cancer cells by activating ferroptosis mediated by p53 pathway - Ling Lin; Ying Zou; Di Zhang (Tissue and Cell, 2025)

Corrigendum to “Isopimaric acid, an ion channel regulator, regulates calcium and oxidative phosphorylation pathways to inhibit breast cancer proliferation and metastasis” [Toxicology and applied Pharmacology, 2023, 462:116415] - Jiacheng Li; Xiaozhen Liu; Lin Chen; Xinping Zhu; Zhihong Yu; Liyao Dong; Xinyun Zhao; Hongling Zou; Qin Wei; Yongcai Feng; Yongqiang Zhu; Kequn Chai; et al. (Toxicology and Applied Pharmacology, 2025)

Numerical study on whipping response in irregular waves with asymmetric slamming for ultra large container ships - Lin Lu; Huilong Ren; Penghao Shan; Hui Li; Jian Zou; Zhiyong Sun (Ocean Engineering, 2025)

Gut microbiota and metabolic functions in herbivorous fish from Xisha coral reefs, China - Xiyue Yang; Yayuan Xiao; Xiaojun Shi; Tuanjie Li; Xiaofei Xiong; Teng Wang; Lin Lin; Yu Liu; Jian Zou; Chunhou Li; Yong Liu; Peng Wu (Marine Environmental Research, 2025)

New insights into the impact of microplastics on nitrogen transformation in urban rivers based on field experiments - Cheng Yang; Yuanyuan Feng; Jinjiang Duan; Nayin Li; Qingping Zou; Peng Lin; Mengli Chen; Jiang Li; Han Zhang (Journal of Environmental Chemical Engineering, 2025)

Designing advanced high-entropy alloy sensors for sensitive low-temperature acetone detection - Boyan Fu; Leyao Bi; Jiahui Lin; Junsheng Wen; Jiaxing Fu; Binglin Zou; Chunjie Wang; Yue Wang (Journal of Environmental Chemical Engineering, 2025)

Characterization of GR-14 peptide from Cordyceps militaris mycelial albumin and its mechanism of heat protection on Lactobacillus fermentum J26 - Ping-Ping Gao; Han-Qing Liu; Qian-Wang Zheng; Zhi-Wei Ye; Li-Qiong Guo; Yuan Zou; Jun-Fang Lin (Food Bioscience, 2025)

Biomimetic enzyme ratiometric electrochemical sensor based on graphene, calcined UIO-66 and thionine for rapid and sensitive detection of zearalenone in vegetable oil - Lin Zhiyuan; Xie Yuzhe; Kong Fanzhuo; Xia Jiaojiao; Suo Hongbo; Huang Rubing; Zou Bin (Food Bioscience, 2025)

Chemical structures, antioxidant capacities, and immunostimulatory activities of pectic polysaccharides from jujube fruits collected from different producing areas - Jing Feng; Xiao Luo; Bo Li; Xiao-Yan Yang; Lin Zhang; Jing-Wei Huang; Yi-Chen Hu; Liang Zou; Ding-Tao Wu (Food Bioscience, 2025)

Enhancing anaerobic digestion of sludge with dual-heteroatom-doped biochar derived from digested sludge: In-situ reuse of anaerobic residues for system self-circulation - Shengye Duan; Junguo He; Yijie Zhong; Lin Li; Xiang Zou; Qiupeng Cai; Ruimiao Zhang; Xinxin Cui; Yuanyi Zhao; Yunlong Liu; Jie Zhang (Environmental Research, 2025)

Ground surface deformation in permafrost region on the Qinghai-Tibet Plateau: A review - Shibo Liu; Lin Zhao; Lingxiao Wang; Lin Liu; Defu Zou; Guojie Hu; Zhe Sun; Yuxin Zhang; Wei Chen; Xueying Wang; Meng Wang; Huayun Zhou; et al. (Earth-Science Reviews, 2025)

Perylene Diimide-Based A-D-A-Type Organic Additives for Efficient and Stable Inverted Perovskite Solar Cells - Shaojian Li; Kai Chen; Haiqian Ling; Desheng Li; Weixu Duan; Zedong Lin; Cong Liu; Xiangwen Guo; Liwei Zhou; Fan Wu; Tao Liu; Bingsuo Zou (Chemical Engineering Journal, 2025)

A dual-dynamic crosslinking network enabled strong, flexible, self-healing, and biodegradable chitosan fiber paper/vitrimer composites for plastic substitution - Xiaoqian Zhang; Leyi Lin; Haonan Zhou; Jie Zou; Wang Zhao; Guowen Zhou; Zepeng Lei; Xiaohui Wang (Carbohydrate Polymers, 2025)

Research on the impact of urban built environments on PM2.5 pollution based on machine learning methods - Xiaoxia Wang; Zhihai Fan; Xiaolong Yue; Qianqian Zhou; Danting Lin; Hong Zou (Atmospheric Pollution Research, 2025)

A novel deacetylase inhibitor KLX suppresses liver fibrosis by deacetylating PPARγ through promoting ubiquitination-mediated HDAC1 degradation - Feng Zhang; Jinglun Song; Han Wu; Keying Lin; Chunlei Wang; Linghua Zeng; Xue Kong; Kunkun Zou; Hongtao Diao; Zhuo Wang; Wei Si; Weitao Jiang; et al. (Science China Life Sciences, 2025)

Fecal metabonomics combined with 16S rRNA gene sequencing to study the mechanisms of cantharidin-induced hepatotoxicity - Lijuan Xiong; Jialu Zou; Kexin Lin; Xiaohong Zhang; Caiying Yan; Yanmei He; Jianyong Zhang (Toxicology Letters, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Low-level exposure to environmental lithium element affects male reproductive outcomes: Results from the MARHCS cohort study in Chongqing, China and in vivo animal experiments - Lihong Wang; Guanghui Zhang; Xi Ling; Mei Wan; Qing Chen; Lei Sun; Huan Yang; Tong Wang; Jinyi Liu; Jia Cao; Lin Ao; Peng Zou (Reproductive Toxicology, 2025)

Power capture and management system of a small-scale marine current turbine for offshore instrument power supply - Yajing Gu; Tian Zou; Hongwei Liu; He Ren; Yonggang Lin (Ocean Engineering, 2025)

Differentiation of Citri Reticulatae Pericarpium varieties via HPLC fingerprinting of polysaccharides combined with machine learning - Min-yong Zhong; Meng-ning Li; Wen-shu Zou; Si-qi Hu; Jiang-nan Luo; Qing-xiang Jiang; Qiu-fang Cao; Long-fei Lin; Zhi-xin Wang; Hui Li; Wen-wen Deng (Food Chemistry, 2025)

Anisotropic deposition of Cu2(OH)3Cl: The critical role of enclosed pit formation heterogeneity - Qihao Lin; Guoqing Chen; Shiwen Zou; Wenlong Zhou; Yufei Zu; Xuesong Fu (Chemical Engineering Journal, 2025)

Metal coordination-based double-network microsphere scaffolds facilitate bone regeneration via oxygen-driven mitochondrial oxidative phosphorylation - Chao Lin; Jialei He; Jiachen Li; Qingsong Zou; Lina Huang; Nuo Chen; Xiaojian Ye; Xiaoxiao Li; Wenguo Cui; Qian Cheng (Chemical Engineering Journal, 2025)

Exosome-loaded methacrylated silk fibroin hydrogel delays intervertebral disc degeneration by DKK2-mediated mitochondrial unfolded protein response - Xiao Lu; Zhidi Lin; Liujingzhou Li; Guangyu Xu; Dachuan Li; Zhaoyang Gong; Jiongdong Wu; Tian Gao; Xingyu Guo; Chenpei Xu; Xinlei Xia; Feizhou Lyu; et al. (Chemical Engineering Journal, 2025)

An anti-miR-301a and zinc coordination driven nanozyme loaded in nanoparticle for oral therapy of inflammatory bowel disease based on colitis microenvironment regulation - Jiafeng Zou; Chuanhe Xia; Min Yao; Xier Pan; Shulei Zheng; Yiting Lin; Xinlin Zhao; Yanwen Wang; Yanzuo Chen; Minbo Lan; Junshan Wang; Feng Gao (Chemical Engineering Journal, 2025)

Outstanding self-healing and plasticity of imine-linked dynamic PDMS with high softness and stability - Fubin Luo; Junyan Sun; Yingbing Zou; Xueyan Yang; Bili Lin; Yixing Feng; Hongzhou Li (Chemical Engineering Journal, 2025)

Effects of iron/aluminum mineral phases on soil organic carbon storage in different clay soils of subtropical acidic forests - Yi Li; Chen-chen Wang; Cui Zou; Yang Zhao; Pei Wei; Yu-ying Liu; Xiao-jun Zhao; Dun-mei Lin; Xian-jin He; Jun-long Huang; Jin-song Guo; Guang-yu Zhu (CATENA, 2025)

Accelerated detection of carbapenem resistance in Klebsiella pneumoniae via single-cell Raman spectroscopy - Jia-Cheng Ding; Li-Ting Dai; Jia-Xin Tang; Hui-Min Zhang; Le-Le Zhai; Chuang-Ye Cai; Zhi-Rou Xiao; Zhe-Mei Chen; Jia-Hui Ling; Meng-Xue Zou; Xi-Wu Cao; Li-Juan Lin; et al. (World Journal of Microbiology and Biotechnology, 2025)

A method for delineating traffic low emission control zone based on deep learning and multi-objective optimization - Shuqi Xue; Hong Zou; Qiang Feng; Xiaoxia Wang; Yuanyuan Liu; Yuanqing Wang; Lin Liu (Environmental Monitoring and Assessment, 2025)

Integrated transcriptomics and metabolomics uncover metabolites and pathways in American bullfrog (Aquarana catesbeiana) response to Elizabethkingia miricola infection - Peikui Yang; Jiawei Lin; Jude Juventus Aweya; Qiongjun Zhao; Yuzhong Zheng; Xianghui Zou; Yanjie Sun; Yaqun Liu; Shixiong Zhan (Aquaculture, 2025)

Patterns and drivers of soil autotrophic nitrification and associated N2O emissions - Shumin Guo; Roland Bol; Zhutao Li; Jie Wu; Haiyan Lin; Xiaomeng Bo; Zhiwei Zhang; Zhaoqiang Han; Jinyang Wang; Jianwen Zou (Soil Biology and Biochemistry, 2025)

Time series prediction of ship maneuvering motion at sea based on higher order dynamic mode decomposition - Chang-Zhe Chen; Zao-Jian Zou; Lu Zou; Jia-Qing Kou; Shi-Jie Lin (Ocean Engineering, 2025)

Long-term conservation tillage changes the diversity, assembly and network stability of soil diazotrophic community - Ling MA; Guixiang ZHOU; Jiabao ZHANG; Zhongjun JIA; Hongtao ZOU; Lin CHEN; Congzhi ZHANG; Donghao MA; Changdong HAN (Pedosphere, 2025)

Interleukin-33 modulates NET formation via an autophagy-dependent manner to promote neutrophilic inflammation in cigarette smoke-exposure asthma - Jing Liu; Peizhi Tao; Beiting Su; Li Zheng; Yusen Lin; Xiaoling Zou; Hailing Yang; Wenbin Wu; Tiantuo Zhang; Hongtao Li (Journal of Hazardous Materials, 2025)

Organic amendments enhance rhizosphere carbon stabilization in macroaggregates of saline-sodic soils by regulating keystone microbial clusters - Changdong Han; Lin Chen; Zhongjun Jia; Hongtao Zou; Ling Ma; Congzhi Zhang; Guixiang Zhou; Donghao Ma; Jiabao Zhang (Journal of Environmental Management, 2025)

Divergent responses of abundant and rare bacterial communities to environmental variables in highly urbanized coastal regions: N-NO2- mediates the community assembly and co-occurrence networks - Shanshan Ma; Lin Zhang; Longjie Zhang; Shuai Zhang; Yiyi Zhu; Jun Wang; Keshu Zou (Journal of Environmental Management, 2025)

Deciphering the promotion and inhibition of bicarbonate fertilization on microalgal activity and nutrient uptake from wastewater - Shuohui Shi; Ying Zhang; Shuxuan Lin; Meiman Zhang; Weiming Zou; Jian Zhou; Yingmu Wang (Journal of Environmental Management, 2025)

Dispersion stabilization of proteins by carrageenan in baked milk: A quantitative separation study - Yimin Wang; Yuanyuan Jiang; Xueke Chen; Yijiao Zou; Lin Lei; Guohua Zhao; Yun Zhou (Food Chemistry, 2025)

Mathematical modelling of mild steel yielding damper with secondary strengthening behavior - Zhipeng Zhai; Chengzhen Lin; Wei Guo; Shuang Zou; Yanhui Liu (Engineering Structures, 2025)

Multifunctional LaCrO3-Gd0.1Ce0.9O1.95 fuel electrode with dual-phase in-situ exsolution for solid oxide cells - Shiming Hu; Shuidan Gu; Liangyou Lin; Lu Zou; Jian Pu; Bo Chi (Chemical Engineering Journal, 2025)

Facile fabrication of redox nanoparticles loaded with exosomal-miRNAs and resveratrol as glycation inhibitor in alleviating the progression and development of diabetic cataract - Xia Chen; Qian Xi; Fei Sun; Lin Zou; Yingxuan Li (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Association between sleep quality and serum biomarkers among long-term hot spring bathers: a cross-sectional study - Fen Yang; Yue Zou; Ying-ying Zhang; Hong-xia Li; Yi-hang Xu; Bao-chao Zhang; Lin-xuan Liao; Meng-xi Cao; Rui-xue Wang; Yuan Yuan; Yun Zhou; Da-yong Zeng; et al. (International Journal of Biometeorology, 2025)

A special lycopene ε-cyclase from Chromochloris zofingiensis ATCC 30412 with multiple catalytic functions - Xing Meng; Xi Li; Ruijuan Ma; Wenjin Lin; Yiping Zou; Baobei Wang; Shih-Hsin Ho; Jianfeng Chen; Youping Xie (Algal Research, 2025)

Rhizosphere microecological mechanism of carbon sequestration and its emission mitigation in rice ratooning - Jinying Li; Bin Qin; Chaojie Lan; Hailong Xu; Jingnan Zou; Bianhong Zhang; Changxun Fang; Zhixing Zhang; Hongfei Chen; Wenxiong Lin (Agriculture, Ecosystems & Environment, 2025)

Dietary retinoic acid improved the growth, lipid metabolism and immune status in Macrobrachium rosenbergii - Qin-Cheng Huang; Li Wang; Zhi-Min Gu; Cui Liu; Tian-Tian Ye; Jun-Jun Yan; Ji-Lun Meng; Yu-Tong Zheng; Xian-Ping Ge; Zhi-Deng Lin; Guo-Yuan Zou (Frontiers in Marine Science, 2025)
The effect of dietary retinoic acid (RA) on the growth, lipid deposition, oxidation resistance, immunity, hepatopancreatic and intestinal health of Macrobrachium rosenbergii was evaluated. A total of 1200 prawns (0.22 ± 0.00 g) were divided into six groups and fed their corresponding feed containing 4, 132, 296, 562, 1206 or 2562 mg/kg dietary RA. The weight gain rate, specific growth rate and final body weight of the prawns changed linearly and quadratically, with the maximum observed in those fed 296 mg/kg dietary RA. Increasing dietary RA linearly and quadratically raised the RA content in the whole body. Compared to the prawns fed 4 mg/kg dietary RA, there was significantly lower lipid deposition in the muscle, hepatopancreas and whole body of prawns fed 296 mg/kg dietary RA. Prawns fed 296 mg/kg dietary RA had lower triglyceride (TG) content in the hepatopancreas with upregulated gene expression of retinoid X receptor ( RXR ), diacylglycerol acyltransferase 1 ( dgat1 ) and carnitine palmitoyltransferase 1 ( cpt1 ). Additionally, 296 mg/kg dietary RA increased the protein expression of RXR, CAMKKβ and phospho-AMPK. A dietary RA level of 296 mg/kg could decrease oxidative stress by upregulating the expression of peroxiredoxin 5 ( prx5 ) and improve immunity by upregulating expression of toll - like receptor 2 ( toll2 ), myeloid differentiation factor 88 (myd88 ) and dosal in the hepatopancreas. The intestinal health related genes ( crustin 2 / 3 / 4 , anti-lipopolysaccharide factor 1 / 7 , prx5 , peritrophin-1 , myosin light chain kinase , claudin , myd88 and dosal ) and morphological structure were also positively affected by dietary RA. Furthermore, dietary RA could relieve the immune responses induced by lipopolysaccharide, thus leading to lower transcription of antimicrobial peptides. In summary, dietary RA could improve the growth, lipid utilisation, antioxidant capacity and immunity of M . rosenbergii . To avoid the negative effects of excessive addition and obtain optimal growth, a diet containing 296 mg/kg dietary RA was suggested by the present study.

Extraction, rapid preparation and neuroprotective effect of texasin, a main active constituent from Caragana jubata (Pall.) Poir. - Zi-Yang Xu; Qi-Jun Dai; Yu-Fan Huang; Bo-Lin Zou; Xin Lu; Jian-Bin Wang; Han-Qing Pang; Wen-Jun Xu; Liang Liu (Natural Product Research, 2025)

The Combined Effects of Cadmium and Microplastic Mixtures on the Digestion, Energy Metabolism, Oxidative Stress Regulation, Immune Function, and Metabolomes in the Pearl Oyster (Pinctada fucata martensii) - Jiaying Yao; Zixin Gao; Zhixiang Wang; Zhanbo Ge; Yujing Lin; Luomin Huang; Jiaen Liu; Heqi Zou; Chuangye Yang; Robert Mkuye; Yuewen Deng (Fishes, 2025)
The accumulation of cadmium (Cd) and microplastics (MPs) can have major deleterious effects on the health of marine ecosystems and organisms, including the pearl oyster Pinctada fucata martensii. Here, we characterized the effects of Cd and MPs on key biochemical parameters of P. f. martensii via an experiment with various treatments. Pearl oysters were exposed to either only Cd (5 or 50 μg/L), only MPs (5 mg/L), or both Cd and MPs for 2 d, and this was followed by a 5-day recovery period. Measurements of the activities of lipase, amylase, protease, T-ATPase, catalase, glutathione peroxidase, acid phosphatase, and alkaline phosphatase enzymes, as well as the malondialdehyde content in the hepatopancreas, were made at various time points during the experiment. Metabolomics analysis of the gills was also performed. Significant interactions between time and treatment on lipase, protease, and catalase activities were observed. However, no significant effect of time–treatment interactions on amylase and T-ATPase activities was observed. Enzyme activities varied among groups both during the exposure period (6 to 48 h) and the recovery period. The malondialdehyde content was also increased throughout the experiment. Pathway analysis indicated that the purine metabolism, glycerophospholipid metabolism, nucleotide metabolism, arachidonic acid metabolism, neuroactive ligand–receptor interaction, and linoleic acid metabolism pathways were the most commonly affected under different treatments. The findings of our study revealed the differential effects of exposure time and treatment on enzyme activities and metabolites and their respective pathways. Our findings enhance our understanding of the biochemical responses of the pearl oyster P. f. martensii to environmental stressors, particularly Cd and MPs.

NAT10 primes a post-transcriptional repertoire essential for the maintenance of spermatogonial homeostasis - Xiaoli Zhu; Caoling Xu; Xue Jiang; Jiaqi Zou; Wenqing Li; Xuemei Xing; Xiaoxiao Gao; Jiao Lei; Fei Meng; Xin Wang; Yuzhang Zhu; Yu Cheng; et al. (Science Bulletin, 2025)

Retrieval of 1 km surface soil moisture from Sentinel-1 over bare soil and grassland on the Qinghai-Tibetan Plateau - Zanpin Xing; Lin Zhao; Lei Fan; Gabrielle De Lannoy; Xiaojing Bai; Xiangzhuo Liu; Jian Peng; Frédéric Frappart; Kun Yang; Xin Li; Zhilan Zhou; Xiaojun Li; et al. (Remote Sensing of Environment, 2025)

Study on hydrocarbon retention and expulsion of kerogen based on centrifugal swelling method - Tian Liang; Feng Zhu; Zhao-Wen Zhan; Xiao-Hui Lin; Yan-Rong Zou; Ping’an Peng (Organic Geochemistry, 2025)

Phosphorus removal and recovery from livestock wastewater by using modified zirconium‑lanthanum magnetite - Rubina Altaf; Dejia Liu; Neemat Jaafarzadeh; Jing Zou; Yuguang Zhou; Baile Wu; Xiaochang Lin; Dezhao Liu (Journal of Water Process Engineering, 2025)

Explainable aeration prediction using deep learning with interpretability analysis - Xingkai Zou; Shenglan Wang; Wenjie Mai; Xiaohui Yi; Mi Lin; Chao Zhang; Zhenguo Chen; Mingzhi Huang (Journal of Water Process Engineering, 2025)

Appraisal of potential toxic elements pollution, sources apportionment, and health risks in groundwater from a coastal area of SE China - Denghui Wei; Shiming Yang; Lin Zou; Juan Antonio Torres-Martínez; Yanhong Zheng; Qili Hu; Yunhui Zhang (Journal of Environmental Management, 2025)

Strong thermospheric response to the almost undetectable substorm on May 29, 2023 - Yongliang Zhang; Qian Wu; Wenbin Wang; Larry Paxton; Robert Schaefer; Dong Lin; Lying Qian; Haonan Wu; Kun Wu; Ying Zou; Martin Connors (Journal of Atmospheric and Solar-Terrestrial Physics, 2025)

Nondestructive detection of pungent and numbing compounds in spicy hotpot seasoning with hyperspectral imaging and machine learning - Di Zhang; Xu Chen; Zitao Lin; Minmin Lu; Wenhao Yang; Xiaoxia Sun; Maurizio Battino; Jiyong Shi; Xiaode Huang; Bolin Shi; Xiaobo Zou (Food Chemistry, 2025)

Establishment and application of a high-performance liquid chromatography-mass spectrometry method for analysis of 15 bisphenols and halogenated phenols in tea - Zifan Hu; Weiyang Sun; Jiaqi Guo; Xuan Wang; Li Yong; Lin Ren; Dejian Feng; Xiaoli Zou (Food Chemistry, 2025)

Exploring the mechanism of flavonoids modification by dimerization strategies and their potential to enhance biological activity - Pengren Zou; Paz Otero; Juan C. Mejuto; Jesus Simal-Gandara; Jianbo Xiao; Carla Cameselle; Shengxiong Chen; Shiye Lin; Hui Cao (Food Chemistry, 2025)

The effects of oil type on the properties of oil-water interfaces and W1/O/W2 double emulsions stabilized by Pleurotus geesteranus protein particles - Tinghui Pei; Bo Lin; Juntong Li; Qianwang Zheng; Zhiwei Ye; Liqiong Guo; Junfang Lin; Yuan Zou (Food Hydrocolloids, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

From food to hard carbon: Citric acid enhanced biomass-derived anodes for high-performance sodium storage - Hao Zhong; Qianhong Huang; Mingyan Zou; Fengtian Li; Yiqing Liu; Yuhong Luo; Guozheng Ma; Yongbo Wu; Xiaoming Lin; Lei Hu (Chemical Engineering Journal, 2025)

Enhancing hydrogen sorption kinetics of Ti-based hydrogen storage alloy tanks through an optimized bulk-powder combination strategy - Liansen Bian; Longfei Shao; Bolun Wang; Jiaqi Zhang; Yinghui Li; Zhigang Hu; Jianxin Zou; Kemin Zhang; Xi Lin (Chemical Engineering Journal, 2025)

Study on the performance of electric double-layer capacitors based on lignocellulose gel polymer electrolytes with different pH values for Zn2+-lignocellulose coordination mechanism - Yanzhou Wang; Yun Huang; Xu Wang; Jin Bao; Chao Zou; Xichang Wang; Yunhe Zhang; Changjian Zhang; Zhongwei Zhao; Xing Li; Mingshan Wang; Yuanhua Lin; et al. (Chemical Engineering Journal, 2025)

Conservation tillage regulates the influence of drought on multitrophic network complexity and improves soil multifunctionality - Ling Ma; Guixiang Zhou; Lin Chen; Zhongjun Jia; Hongtao Zou; Congzhi Zhang; Donghao Ma; Changdong Han; Jiabao Zhang (Applied Soil Ecology, 2025)

Negative regulation of hippo-mediated antiviral response targeted WSSV in Penaeus vannamei - Hong Shi; Wenyang Lin; Yibin He; Jie Ren; Yiwen Jian; Zhihao Huang; Caozhi Huang; Chenchen Zou; Lingwei Ruan (Aquaculture, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Prediction of global structural responses for an ultra-large container ship under long-crested irregular waves using generalized modes and artificial neural networks - Ruixiang Liu; Hui Li; Muk Chen Ong; Jian Zou; Lin Lu (Ocean Engineering, 2025)

Research on inland ship hydrodynamic modeling and parameter identification based on CFD - Shigan Ding; Mao Zheng; Sasan Tavakoli; Songlong Li; Jiafeng Lan; Bowen Lin; Tianyue Zou; Mingyang Zhang (Ocean Engineering, 2025)

Efficient synthesis of isoamyl acetate in deep eutectic solvent utilizing in-situ aqueous phase immobilized lipase biocatalyst - Yuyang Zhang; Qiujie Wang; Zhiyuan Lin; Jiaojiao Xia; Hongbo Suo; Rubing Huang; Bin Zou (Food Bioscience, 2025)

Lactiplantibacillus plantarum A72 inoculation enhances Citrus juice quality: A systematic analysis of the strain's fermentation properties, antioxidant capacities, and transcriptome pathways - Qi Wu; Sibo Zou; Xu Yan; Ying Yue; Sufang Zhang; Chaofan Ji; Yingxi Chen; Yiwei Dai; Xinping Lin (Food Bioscience, 2025)

In-situ reconstruction of active bismuth for enhanced CO2 electroreduction to formate - Chenchen Weng; Cheng Wang; Yang Song; Yu-Xiao Zhang; Kang Zou; Hongwu Chen; Xue Yang; Wei Lin (Chemical Engineering Journal, 2025)

Stem cells vesicles-loaded type I pro-photosensitizer for synergetic oxygen-independent phototheranostics and microenvironment regulation in infected diabetic wounds - Qin Zeng; Ying Zhang; Judun Zheng; Jingyan Lin; Ning Li; Minghai Zhao; Xu Chen; Xipeng Li; Meijiao Zhao; Jialin Huang; Qiulin Xie; Ronghua Yang; et al. (Chemical Engineering Journal, 2025)

Ligand engineering boosts catalase-like activity of gold nanoclusters for cascade reactions combined with glucose oxidase in ZIF-8 matrix - Yi-Shu Wang; Chen Dong; Li Zou; Lin Zhao; Jian-Hua Qin; Hui-Lin Mo (Analytica Chimica Acta, 2025)

Freshness Prediction of Silver Carp Using Sub-Layer Equivalent Circuit Parameters in Electrochemical Impedance Spectroscopy - Jian Sun; Ruiting Xia; Feng Lin; Kai Wu; Jinfu Chen; Gangshan Wu; Wei Pan; Tingting Zou (Journal of Aquatic Food Product Technology, 2025)

Enhancing porcine oocyte quality and embryo development through natural antioxidants - Zheng Feng; Jia Song; Chenghong Lin; Siyu Wu; Yu Wang; Qingyuan Hui; Yinting Pan; Yiman Zou; Chaofeng Zeng; Jinbiao Guo; Yangli Pei (Theriogenology, 2025)

Sophflarines B−E, four distinctive matrine alkaloids from Sophora flavescens with potential neuroprotective activities - Ding Luo; Qian Xie; He Tian; Xin-Kai Zheng; Jia-Wen Zou; Yue-Hao Huang; Yan-Jun Chen; Chun-Lin Fan; Li-Jun Hu; Jian-Xin Chen; Hao Wang; Guo-Cai Wang; et al. (Phytochemistry, 2025)

LC–MS coupled with diagnostic ion strategy facilitated the discovery of 5-methylcoumarin meroterpenoids from Gerbera piloselloides - Shi-lin Chen; Ha Gao; Chen-xu Zhao; Tao Zhang; Zhong-mei Zou (Phytochemistry, 2025)

Recent progress on triterpenoid derivatives and their anticancer potential - Zi-Xuan Zhao; Qiong-Yu Zou; Ying-Hong Ma; Susan L. Morris‐Natschke; Xiang-Yuan Li; Lin-Chun Shi; Guo-Xu Ma; Xu‐Dong Xu; Mei‐Hua Yang; Zi-Jian Zhao; Yuan-Xiang Li; Jing Xue; et al. (Phytochemistry, 2025)

Grazing increases the complexity of networks and ecological stochastic processes of mycorrhizal fungi - Jiqiong Zhou; Pengsen Wang; Li Wei; Jianguo Zhang; Xuxu Li; Nan Huang; Gang Liu; Kun Zou; Rui Fan; Lin Liu; Xiao Ma; Ting Huang; et al. (Journal of Environmental Management, 2025)

Inoculation of thermophilic bacteria from giant panda feces into cattle manure reduces gas emissions and decreases resistance gene prevalence in short-term composting - Jingxia Fu; Shujuan Chen; Yulan Tan; Keyi Zou; Xiumei Yu; Lin Ji; Jianmin Zhang; Xingning Xiao; Wen Wang; Ke Zhao; Likou Zou (Journal of Environmental Management, 2025)

In-situ aqueous phase encapsulation immobilized lipase assisted by acidic ionic liquids for the synthesis of isoamyl acetate - Yuyang Zhang; Xin Gu; Zhiyuan Lin; Hongbo Suo; Jiaojiao Xia; Bin Zou (Food Bioscience, 2025)

Phosphine oxide functionalized porous aromatic frameworks enabled wireless bionic olfactory system with preconcentration capability for trace ammonia monitoring - Shuai Zhao; Hongyang Jin; Zihao Chen; Yonglai Zhang; Xiaoqin Zou; Lin Xu; Shaolei Wang; Zhenglei Yu; Zhiyong Chang (Chemical Engineering Journal, 2025)

Solar interfacial evaporation hydrogel with distributed packaging of phase change materials for continuous desalination - Qian Chen; He Zhang; Lie Zou; Rui Yang; Guangyong Zeng; Pengcheng Lin; Liu Yang; Mingming Zheng; Xiaoke Li (Chemical Engineering Journal, 2025)

Mitochondria-targeted delivery of zinc-coordinated resveratrol nanoparticles rescues the osteogenic potential of periodontal ligament stem cells compromised by inflammation for periodontal wound healing - Yu-Jie Tan; Xuan Li; Wen-Jie Zhang; Yu-Meng Cao; Jie-Kang Zou; Lin Jing; Dian Gan; Yu-Zhe Chen; Mei Xu; Ying An; Fa-Ming Chen; Xiao-Tao He; et al. (Chemical Engineering Journal, 2025)

Enhancing electromechanical conversion and motion-monitoring application of pore-oriented cellulose nanocrystal/agarose aerogel modified with flexible heterojunction structures - Weiwei Chen; Lin Gan; Jie Xiong; Ga Liu; Tingting Yang; Yanrui Zou; Zhicheng Zhang; Jin Huang (Carbohydrate Polymers, 2025)

The beneficial potential of protein hydrolysates as prebiotic for probiotics and its biological activity: a review - Ping-Ping Gao; Han-Qing Liu; Zhi-Wei Ye; Qian-Wang Zheng; Yuan Zou; Tao Wei; Li-Qiong Guo; Jun-Fang Lin (Critical Reviews in Food Science and Nutrition, 2024)

Oligochitosan Mitigates Vibrio harveyi Infection in Hybrid Groupers (Epinephelus lanceolatus ♂ × Epinephelus fuscoguttatus ♀) by Modulating Immune Responses and Disease-Related Pathways - Fei Shi; Lixin Ma; Zhilong Chen; Hao Zhao; Cuiyun Zou; Li Lin; Zhendong Qin (Fishes, 2024)
Vibrio harveyi is an important pathogen causing enteritis in hybrid groupers. However, its effects on the intestinal microbiota and the regulatory effects of oligochitosan on Vibrio-infected groupers are unclear. In this study, we investigated the effects of infection with V. harveyi and oligochitosan administration on the growth performance, immune responses, and intestinal transcriptome profiles of hybrid groupers during a 60-day rearing period. Growth parameters were reduced in Vibrio-infected groupers, while oligochitosan improved the body weight. Biochemical analysis showed reduced antioxidant enzyme activity and increased lipid peroxidation in Vibrio-infected groupers, which were consequently improved by oligochitosan. Transcriptome analysis was used to identify differentially expressed genes in the disease-related and immune system pathways that significantly accumulated in the treatment groups. An evaluation of the immune response showed a significant down-regulation of proinflammatory cytokines, antioxidant genes, and tight-junction proteins in Vibrio-infected groupers, which was partially restored by oligochitosan. Additionally, intestinal apoptosis, indicated by TUNEL signaling, was observed to significantly increase in Vibrio-infected groupers and was subsequently alleviated by oligochitosan supplementation. These results demonstrate the detrimental effects of V. harveyi infection on the growth and immune function of hybrid groupers and the potential of oligochitosan to attenuate these effects.

A comprehensive review of microplastic aging: Laboratory simulations, physicochemical properties, adsorption mechanisms, and environmental impacts - Yu Gao; Wei Gao; Yuzhi Liu; Donglei Zou; Yuan Li; Yingzi Lin; Jun Zhao (Science of The Total Environment, 2024)

Process and mechanism analysis of typical permafrost area surface deformation at two sites along the Qinghai-Tibet highway based on long-term leveling observation - Shibo Liu; Lin Zhao; Lingxiao Wang; Defu Zou; Guojie Hu; Zhe Sun; Huayun Zhou; Yongping Qiao (Science of The Total Environment, 2024)

Outdoor light at night is a modifiable environmental factor for metabolic syndrome: The 33 Communities Chinese Health Study (33CCHS) - Li-Wen Hu; Yan-Chen Gong; Hong-Xing Zou; Le-Bing Wang; Yanan Sun; Alejandro Godinez; Han-Yu Yang; Si-Han Wu; Shuo Zhang; Wen-Zhong Huang; Zhao-Huan Gui; Li-Zi Lin; et al. (Science of The Total Environment, 2024)

Numerical analysis of FPSO mooring dynamic tension and its fatigue damage under a simplified coupled method considering structural elastic deformation - Chunlei Liu; Hui Li; Ruixiang Liu; Jian Zou; Baoli Deng; Lin Lu (Ocean Engineering, 2024)

Mechanical modulation wave energy harvesting for self-powered marine environment monitoring - Hong-Xiang Zou; Wen-Zhuo Zhou; Chang-Sheng Su; Ding-Hua Guo; Lin-Chuan Zhao; Qiu-Hua Gao; Ke-Xiang Wei (Ocean Engineering, 2024)

High-resolution 3D hydrodynamic modeling and comprehensive assessment of tidal current energy resources - Tian Zou; Yajing Gu; Hongwei Liu; Yonggang Lin; Liyuan Zhang; Yuquan Zhang (Ocean Engineering, 2024)

Late Cenozoic deformation of the northeastern Pamir and the west Kunlun Mountains: Insights from anisotropy of magnetic fabrics and sedimentary analysis - Xinwei Chen; Hanlin Chen; Xiubin Lin; Xiaogan Cheng; Chao Chen; Johannes Rembe; Hao Zou (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Ultrasonic technology for predicting beef thawing degree and endpoint - Hongzhou Chen; Qing Sun; Lilei Xuan; Zitao Lin; Zeyu Yang; Xiaowei Huang; Zhihua Li; Wenjian Gao; Jun Ren; Jiyong Shi; Xiaobo Zou (Journal of Food Engineering, 2024)

Emerging antibiotic and heavy metal resistance in spore-forming bacteria from pig manure, manure slurry and fertilized soil - Min Yan; Wen Wang; Lei Jin; Guoyou Deng; Xinfeng Han; Xiumei Yu; Junni Tang; Xiangan Han; Menggen Ma; Lin Ji; Ke Zhao; Likou Zou (Journal of Environmental Management, 2024)

Lignanamides: A comprehensive review of chemical constituents, biological activities, extraction methods and synthetic pathway - Jing Sun; Li-Tao Tong; Peng-Fei Tu; Lin-Lin Chen; Xin Xu; Ya Song; Xin-Xin Yang; Zi-Bin Guo; Xiang Zou; Chen-Xin Sun; Yan Mi; Bei Fan; et al. (Food Chemistry, 2024)

Composite enzymatic hydrolysis for producing Harlikar apple juice with increased dietary fiber content and antioxidant capacity - Xiaoqiang Zou; Jijie Hu; Yuechao Pan; Kang Zhang; Jianghui Lu; Xiusheng Guo; Yunzhuoya Lin; Wenxue Liu (Food Bioscience, 2024)

Enhanced mass scattering efficiencies of background dust aerosols over East Asia following the passage of dust plumes - Chenguang Tang; Yingjing Lin; Pengfei Tian; Jinsen Shi; Tao Deng; Xuejiao Deng; Yu Zou; Lei Zhang (Atmospheric Environment, 2024)

Relationship between interannual variability of the north edge of the East Asian summer monsoon and extreme precipitation in North China - Yuanyuan Zou; Yunting Qiao; Ailan Lin; Ruidan Chen (Atmospheric Research, 2024)

Efficient transformation of CO2 into α-alkylidene cyclic carbonates over Cu0/Cu+ derived from CuAl layered double hydroxide/reduced graphene oxide hybrid - Zheng Wang; Yue Qiu; Baoyu Zou; Deke Wang; Zifei Gao; Xuanheng Zhang; Juanjuan Ma; Lin Liu; Chao Liu; Zhiwei Tong (Applied Clay Science, 2024)

Molecular epidemiology of herpangina in the subcenter of Beijing, China: a surveillance study during 2021-2022 - Wan-Xue Zhang; Lin Zou; Yan Cui; Yiguo Zhou; Shan-Shan Zhang; Han Yang; Susu Ding; Qin-Yi Ma; Lu Xi; Ran-Ran Zheng; Juan Du; Jianming Zhang; et al. (Archives of Virology, 2024)

Effects of mitochondria on postmortem meat quality: characteristic, isolation, energy metabolism, apoptosis and oxygen consumption - Bo Zou; Fei Jia; Lin Ji; Xingmin Li; Ruitong Dai (Critical Reviews in Food Science and Nutrition, 2024)

The effect of paeoniflorin on the rewarding effect of methamphetamine and the associated cognitive impairment in mice - Xin-shuang Gong; Hai-xing Wang; Xiang-dong Yang; Zhao-ying Yu; Shu-jun Lin; Zhi-ting Zou; Jia-nan Lv; Li-yin Qian; Yu-er Ruan; Zi-zhen Si; Yi Zhou; Yu Liu (Metabolic Brain Disease, 2024)

Immune regulation by fermented milk products: the role of the proteolytic system of lactic acid bacteria in the release of immunomodulatory peptides - Hao Zou; Hao Wang; Ziye Zhang; Hong Lin; Zhenxing Li (Critical Reviews in Food Science and Nutrition, 2024)

Pure water and resource recovery from municipal wastewater using high-rate activated sludge, reverse osmosis, and mainstream anammox: A pilot scale study - Haoran Zhao; Yu Zhou; Lianpei Zou; Chihao Lin; Jianyong Liu; Yu-You Li (Water Research, 2024)

Meteorological effects of ventilation corridor in central urban areas: A case study of Wuhan - Xuesong Li; Kai Lin; Dan Cheng; Han Zou; Yulong Shu; Zhiguo Jin; Jiabei Zhu (Sustainable Cities and Society, 2024)

KMT2D deficiency leads to cellular developmental disorders and enhancer dysregulation in neural-crest-containing brain organoids - Ziyun Shan; Yingying Zhao; Xiuyu Chen; Guodong Zhan; Junju Huang; Xuejie Yang; Chongshen Xu; Ning Guo; Zhi Xiong; Fang Wu; Yujian Liu; He Liu; et al. (Science Bulletin, 2024)

Variations in soil fungal communities: Comparative insights from coniferous and mixed broadleaf-conifer forests - Dexing Chen; Qiongyi Zhang; Siyu Chen; Yuqing Lin; Yuanming Zhu; Weiwei Sun; Mingjiu Chen; Shuangquan Zou; Xin Qian (Pedobiologia, 2024)

Modeling virus-stimulated proliferation of CD4 + T-cell, cell-to-cell transmission and viral loss in HIV infection dynamics - Jiawei Deng; Hongying Shu; Lin Wang; Xingfu Zou (Mathematical Biosciences, 2024)

Nitrogen-doped cobalt oxide via atmospheric modulation activates PMS for rapid degradation of organic pollutants: Role of nitrogen fraction on sulfapyridine elimination - Lingxiao Zou; Kai Yang; Yihui Hu; Xingyu Guo; Xiaojing Li; Yuancai Lv; Yifan Liu; Xiaoxia Ye; Chunxiang Lin; Minghua Liu (Journal of Water Process Engineering, 2024)

Improving peanut growth and cadmium phytoextraction capacity by inoculating Bacillus megaterium and Trichoderma harzianum - Jie Xiong; Dongsheng Zou; Jianguo Kang; Yingying Mo; Lin Li; Likun Zhan; Qingdan Wu; Zhihua Xiao (Journal of Environmental Management, 2024)

Structures, gelatinization properties and enzyme hydrolyses of starches from transparent and floury grains of rices subjected to field natural extreme high temperature - Laiquan Shi; Zihan Zou; Chen Zhu; Hao Wang; Lingshang Lin; Juan Wang; Cunxu Wei (Food Chemistry, 2024)

Ginkgo biloba leaf polysaccharide-stabled selenium nanozyme as an efficient glutathione peroxidase mimic for the preservation of bananas and cherry tomatoes - Jiahui Zou; Huimin Zhong; Cong Jiang; Guancheng Zhu; Xueer Lin; Yanyan Huang (Food Chemistry, 2024)

Electrospun film polyvinyl alcohol/chitosan loaded with cinnamon essential oil and inhibitory effects on polyphenol oxidase and dominant spoilage bacteria from Pacific white shrimp - Minzhen Zhang; Lin Wang; Xiaoyu Zou; Ru Song (Food Hydrocolloids, 2024)

Synergistic effects of metallic IrCo for promoted nitrate reduction in industrial-relevant wastewater level - Yu Tang; Pan Ran; Linjun Zhong; Haohong Liao; Qing Tong; Weixin Zou; Lin Dong (Chemical Engineering Journal, 2024)

Using magnesium hydride as the future dual-mode propellant for spacecraft: A simulation investigation - Xi Lin; Ze Zhang; Lianshen Bian; Longfei Shao; Yinglong Kang; Keming Zhang; Jianxin Zou (Chemical Engineering Journal, 2024)

3D printing technologies in water Treatment: Applications, Challenges, and emerging trends - Yun-fei Zhang; Jin-ze Li; Yue Zou; Yan-lin Liu; Lei Li; Jian-hui Xu; Dan Li; Qiang-qiang Rong; Jian-ying Li; Yi-xin Geng; Jia-wei Lai (Chemical Engineering Journal, 2024)

Large variability in permafrost degradation over the Northern Hemisphere - Guojie Hu; Lin Zhao; Defu Zou; Xiaodong Wu; Ren Li; Xiaofan Zhu; Youqi Su; Tonghua Wu; Yifan Wu; Jie Ni (CATENA, 2024)

Single-atom oxide-decorated AuNPs for universal enhancement in SERS detection of pesticide residues - Qi Zhang; Binbin Chen; Qingbian Ma; Zunlong Fang; Shu Li; Xiaoyu He; Yufeng Wang; Xiaohua Qi; Qian Chen; Ting Cai; Lin Zhang; Mingqiang Zou; et al. (Analytica Chimica Acta, 2024)

Generation of canine neutralizing antibodies against canine parvovirus by single B cell antibody technology - Zhihao Wang; Pengfei Shi; Sheng Wang; Zhipeng Lin; Zhichen Wang; Chengguang Zhang; Ling Zhao; Sizhu Suolang; Jiahui Zou; Hongbo Zhou (Archives of Virology, 2024)

Correction to: A rho-type GTPase activating protein affects the growth and development of Cordyceps cicadae - Xueqian Li; Yu Zou; Neeraj Shrivastava; Jiandong Bao; Fu-Cheng Lin; Hongkai Wang (Archives of Microbiology, 2024)

Application of Fluorescent Composite Materials as a Sustained Release System in Treatment of Polycystic Ovary Syndrome - Lin Wang; Liangshan Mu; Yao Ye; Jun Xu; Xutong Zou (Journal of Fluorescence, 2024)

Ensuring Clinical Excellence: The Mindray SAL9000 Biochemical Immunoassay System - Zhenzhen Zou; Honghui Tang; Erya Xiao; Yu Zhou; Xuebei Yin; Zhen Hu; Yang Cai; Qingzhen Han; Lin Wang (Cell Biochemistry and Biophysics, 2024)

Dynamic Response Prediction Model for Jack-Up Platform Pile Legs Based on Random Forest Algorithm - Xiaohui Cui; Hui Liu; Xiang Lin; Jiahe Zou; Yu Wang; Bo Zhou (Journal of Marine Science and Engineering, 2024)
Jack-up offshore platforms are widely used in many fields, and it is of great importance to quickly and accurately predict the dynamic response of platform pile leg structures in real time. The current analytical techniques are founded upon numerical modelling of the platform structure. Although these methods can be used to accurately analyze the dynamic response of the platform, they require a large quantity of computational resources and cannot meet the requirements of real-time prediction. A predictive model for the dynamic response of the pile leg of a jack-up platform based on the random forest algorithm is proposed. Firstly, a pile leg dynamic response database is established based on high-fidelity numerical model simulation calculations. The data are subjected to cleaning and dimensional reduction in order to facilitate the training of the random forest model. Cross-checking and Bayesian optimization algorithms are used for the selection of random forest parameters. The results show that the prediction model is capable of outputting response results for new environmental load inputs within a few milliseconds, and the prediction results remain highly accurate and perform well at extreme values.

Heat acclimation alleviates the heat stress-induced impairment of vascular endothelial cells - Jirui Wen; Zhengdong Lin; Juan Cheng; Can Li; Ling Wang; Yuhao Zou; Xuehong Wan; Jifeng Liu; Jiang Wu (Tissue and Cell, 2024)

Two-stage double deep Q-network algorithm considering external non-dominant set for multi-objective dynamic flexible job shop scheduling problems - Lei Yue; Kai Peng; Linshan Ding; Jabir Mumtaz; Libin Lin; Tao Zou (Swarm and Evolutionary Computation, 2024)

An emerging quaternary semiconductor nanoribbon with gate-tunable anisotropic conductance - Shaolong Jiang; Fuchen Hou; Shengfeng Zeng; Yubo Zhang; Erding Zhao; Yilin Sun; Liyun Zhao; Cheng Zhang; Mengyuan Jia; Jun-Feng Dai; Mingyuan Huang; Qing Zhang; et al. (Science Bulletin, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Novel method for reducing NDMA formation from daminozide during ozonation: Performances and mechanisms - Linfang Li; Qing Lin; Xiaobin Liao; Tianze Liu; Huan Qi; Qingsong Li; Menglan Gao; Jing Zou; Zhenming Zhou; Mingzhi Huang; Zhimin Yang (Journal of Cleaner Production, 2024)

Numerical investigation of the oxy-fuel combustion in the fluidized bed using macroscopic model supported by CFD-DDPM - Lu Dong; Liang Wang; Huaizhou Wen; Zhong Lin; Zhiyi Yao; Chan Zou; Hongpeng Xu; Hongyun Hu; Hong Yao (Journal of Environmental Chemical Engineering, 2024)

Insight into simultaneously sludge dewatering and antiviral drugs removal by integrated particle electrodes assisted electrochemical oxidation - Haixiang Yu; Yiyang He; Hong Tao; Haiping Yuan; Feiyan Wu; Rusen Zou; Suyun Xu; Lin Gu (Journal of Environmental Chemical Engineering, 2024)

Hygrothermal resilience of typical lightweight steel-framed wall assemblies in hot-humid areas under future climate uncertainty - Qiaosheng Zhan; Sihan Xue; Shi Yin; Zhenghao Lin; Yukai Zou; Yiqiang Xiao (Energy and Buildings, 2024)

Ordered 2D/3D CoNi-LDH/FeSe electrode for efficient and durable seawater oxidation - Yue Shi; Jiejie Bai; Aixin Ma; Zhitao Zou; Yanru Liu; Haifeng Lin; Dehong Chen; Ruiyong Zhang; Jianping Lai; Lei Wang (Chemical Engineering Journal, 2024)

Magneto-elastic for wireless intraocular pressure monitoring - Yu Lin; Shengxin Xiang; Wenjun Zou; Xiaohua Chen; Feixiang Gao; Yi Liu; Yijie Sun; Ping Chen; Quanxi Zhang; Xuelian Han; Baoping Wang; Yong Yao; et al. (Chemical Engineering Journal, 2024)

Overlooked role of protocatechuic acid in enhancing the selective elimination of sulfonamide antibiotics in Fe(III)/peroxymonosulfate process under actually neutral pH conditions - Sheng Li; Jing Zou; Jianying Wu; Jinbin Lin; Zhijie Wu; Chenyu Tang; Linfeng He; Xiaobin Liao; Jun Ma (Chemical Engineering Journal, 2024)

Joint regulation of the soil organic carbon accumulation by mineral protection and microbial properties following conservation practices - Changdong Han; Lin Chen; Zhongjun Jia; Hongtao Zou; Ling Ma; Biao Feng; Jingwang Li; Guixiang Zhou; Congzhi Zhang; Donghao Ma; Jiabao Zhang (CATENA, 2024)

Current status of molecular rice breeding for durable and broad-spectrum resistance to major diseases and insect pests - Xiaoyan Cheng; Guohua Zhou; Wei Chen; Lin Tan; Qishi Long; Fusheng Cui; Lei Tan; Guoxing Zou; Yong Tan (Theoretical and Applied Genetics, 2024)
In the past century, there have been great achievements in identifying resistance ( R ) genes and quantitative trait loci (QTLs) as well as revealing the corresponding molecular mechanisms for resistance in rice to major diseases and insect pests. The introgression of R genes to develop resistant rice cultivars has become the most effective and eco-friendly method to control pathogens/insects at present. However, little attention has been paid to durable and broad-spectrum resistance, which determines the real applicability of R genes. Here, we summarize all the R genes and QTLs conferring durable and broad-spectrum resistance in rice to fungal blast, bacterial leaf blight (BLB), and the brown planthopper (BPH) in molecular breeding. We discuss the molecular mechanisms and feasible methods of improving durable and broad-spectrum resistance to blast, BLB, and BPH. We will particularly focus on pyramiding multiple R genes or QTLs as the most useful method to improve durability and broaden the disease/insect spectrum in practical breeding regardless of its uncertainty. We believe that this review provides useful information for scientists and breeders in rice breeding for multiple stress resistance in the future.

Phenotypic and genetic effect of carotid intima-media thickness on the risk of stroke - Wenqiang Zhang; Jingwei Zhu; Xuan Wu; Tianle Feng; Wei Liao; Xuan Li; Jianci Chen; Li Zhang; Chenghan Xiao; Huijie Cui; Chao Yang; Peijing Yan; et al. (Human Genetics, 2024)

Hydrochemical insights, water quality, and human health risk assessment of groundwater in a coastal area of southeastern China - Yanhong Zheng; Denghui Wei; Jie Gan; Lin Zou; Rilong Zhu; Yunhui Zhang (Environmental Monitoring and Assessment, 2024)

Phylogenetic analysis, genetic diversity, and epidemiology of pigeon paramyxovirus type 1 in China - Chuqi Huang; Shaoyu Tu; Wei Sheng; Zhihao Wang; Zhipeng Lin; Jing Qian; Jiahui Zou; Hongbo Zhou (Archives of Virology, 2024)

When river meets ocean: distribution and conversion of suspended organic particles in a Sundarbans mangrove river-estuary system, Bangladesh - Xiaochun Zou; Yunhai Li; Liang Wang; Mohammad Kawser Ahmed; Keliang Chen; Jianwei Wu; Yonghang Xu; Yunpeng Lin; Baohong Chen; Kankan Wu; Jinwen Liu (Acta Oceanologica Sinica, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Experimental study of ignition process caused by poor electrical contact of connecter - Chaoying Li; Zehua Yang; Wenbin Yao; Kaiyu Zou; Haidong Liu; Jin Lin; Shouxiang Lu (Process Safety and Environmental Protection, 2024)

Impacts of salinity stress induced by ballast water discharge on the ecosystem of shanghai port, China - Chenyang Duan; Lei Hu; Xiangbin Lin; Junzeng Xue; Jin Zou; Huixian Wu (Marine Environmental Research, 2024)

Glutathione‑iron hybrid nanozyme-based colorimetric sensor for specific and stable detection of thiram pesticide on fruit juices - Xu Yan; Ruiqi Zou; Qiqi Lin; Yuan Ma; Aixin Li; Xun Sun; Geyu Lu; Hongxia Li (Food Chemistry, 2024)

Association between outdoor light at night exposure and executive function in Chinese children - Han-Yu Yang; Si-Han Wu; Shuo Zhang; Hong-Xing Zou; Le-Bing Wang; Li-Zi Lin; Zhao-Huan Gui; Xiao-Wen Zeng; Bo-Yi Yang; Ru-Qing Liu; Guang-Hui Dong; Li-Wen Hu (Environmental Research, 2024)

Unified stress–strain calculation model for UHPC-filled stainless-steel tubular columns with various cross-sectional shapes under axial compression - Zhuang Zhao; Yang Wei; Xingxing Zou; Dongdong Chen; Yu Lin; Kaiqi Zheng (Engineering Structures, 2024)

Characterization of novel anthocyanins film @ carbon quantum dot nanofiber intelligent active double-layer film, physicochemical properties and fresh-keeping monitoring in Ictalurus punctatus fish - Wen Qin; Linhong Zou; Yuhan Hou; Zhijun Wu; Douglas A Loy; Derong Lin (Chemical Engineering Journal, 2024)

An injectable COL6-crosslinked HA-DTPH hydrogel promotes spinal tract-like structure organization during spinal cord regeneration - Jia-Hui Sun; Zhou Fang; Zhiling Li; Ting-Ting Zheng; Sheng Liu; Jixiang Zhu; Wensheng Lin; Li-Kang Zhang; Aihua Yin; Aiguo Xuan; Jian-Long Zou (Chemical Engineering Journal, 2024)

Cation-vacancy-rich NiFe2O4 nanoparticles embedded in Ni3Se2 nanosheets as an advanced catalyst for oxygen evolution reaction - Baoxin Wu; Zijie Zhang; Yan Hu; Jia Liu; Xiaohong Zou; Qing Zhang; Kejun Yan; Shibo Xi; Guanxiong Wang; Xiao Zhang; Lin Zeng; Liang An (Chemical Engineering Journal, 2024)

A short linear glucan nanocomposite hydrogel formed by in situ self-assembly with highly elastic, fatigue-resistant and self-recovery - Jinling Zou; Zhiwei Lin; Linjie Zhan; Yang Qin; Qingjie Sun; Na Ji; Fengwei Xie (Carbohydrate Polymers, 2024)

Progressive Freezing-Melting Method for Removal Boron from Simulated Seawater - Yihong Zou; Yan Zhang; Chen Zhao; Rui Mei; Lin Lin; Chunbo Liu; Yucan Liu; Yepeng Tian; Futian Chen (Water, Air, & Soil Pollution, 2024)

Sleep onset time as a mediator in the association between screen exposure and aging: a cross-sectional study - Senlin Lin; Meng Gao; Juzhao Zhang; Yuting Wu; Tao Yu; Yajun Peng; Yingnan Jia; Haidong Zou; Lina Lu; Deshang Li; Yingyan Ma (GeroScience, 2024)
Excessive screen exposure has become a significant health concern. This study investigates the impact of screen time on aging in middle-aged and elderly populations. Healthy working adults over 45 years old in Shanghai, China, underwent general and ocular examinations. Questionnaires collected demographics, medical history, and screen exposure details. Aging was assessed using the retinal age gap, defined as the difference between the retinal age predicted by deep learning algorithms based on fundus images and chronological age. Pathway analysis tested the mediation effect of sleep duration and onset time on the relationship between screen usage and retinal age gap. The retinal age gap increased with longer screen exposure, from 0.49 ± 3.51 years in the lowest tertile to 5.13 ± 4.96 years in the highest tertile (Jonckheere-Terpstra test, p < 0.001). Each additional hour of screen exposure accelerated the retinal age gap by 0.087 years (95% CI, 0.027, 0.148, p = 0.005) in the fully adjusted linear model. Sleep onset time mediated the impact of screen usage on the retinal age gap (indirect effect, β = 0.11; 95% CI 0.04–0.24). The impact of screen usage in a light-off environment on the retinal age gap was fully mediated by sleep onset time (indirect effect, β = 0.22; 95% CI 0.07–0.38), with the proportion being 100%. Our study identified a correlation between excessive screen time and a wider retinal age gap in middle-aged and elderly individuals, likely due to delayed sleep onset. To mitigate the adverse effects on the retina and aging, it is important to limit screen usage and avoid screens before bedtime.

Relating the carbon sources to denitrifying community in full-scale wastewater treatment plants - Jinling Chen; Xia Tang; Xuewei Wu; Biping Li; Xia Tang; Xueran Lin; Pengfei Li; Hang Chen; Fu Huang; Xuhan Deng; Xiaojing Xie; Chaohai Wei; et al. (Chemosphere, 2024)

Protocatechuic acid enhanced the selective degradation of sulfonamide antibiotics in Fe(III)/peracetic acid process under actually neutral pH conditions - Sheng Li; Jing Zou; Jianying Wu; Jinbin Lin; Chenyu Tang; Shiyi Yang; Lingxin Chen; Qingsong Li; Panpan Wang; Jun Ma (Water Research, 2024)

Deciphering spatial-temporal dynamics of flood exposure in the United States, - Joynal Abedin; Lei Zou; Mingzheng Yang; Robert Rohli; Debayan Mandal; Yi Qiang; Humaira Akter; Bing Zhou; Binbin Lin; Heng Cai (Sustainable Cities and Society, 2024)

The composition of soil fungal communities is more dependent on biocrust type than on shrub cover in the Mu Us Desert - Lin Xu; Chaonan Li; Wenjun Xiong; YongPing Kou; Ping Zou; Bingjie Jiao; Minjie Yao; Junming Wang; Bingchang Zhang; Xiangzhen Li (Fungal Ecology, 2024)

Anti-obesity effects of the high molecular weight Cordyceps militaris polysaccharide CMP40 in high-fat diet mice - Yingyin Wu; Yifeng Zhang; Shishi Huang; Weifan Xie; Genan Huang; Yuan Zou; Zhiwei Ye; Tao Wei; Junfang Lin; Qianwang Zheng (Food Bioscience, 2024)

Potential of Cordyceps militaris protein hydrolysates as prebiotic and thermo-protectants of Lactobacillus fermentum J26 - Ping-Ping Gao; Han-Qing Liu; Qian-Wang Zheng; Yuan Zou; Zhi-Wei Ye; Tao Wei; Li-Qiong Guo; Jun-Fang Lin (Food Bioscience, 2024)

Hydrogen peroxide enhanced Cu(II)/peroxymonosulfate system for naproxen degradation in natural water matrix and simultaneously reduced the formation potential of halogenated by-products - Jianying Wu; Jing Zou; Sheng Li; Chenyu Tang; Zhijie Wu; Linfeng He; Jinbin Lin; Qingsong Li; Jun Ma (Chemical Engineering Journal, 2024)

Tough and elastic hydrogel thermocells for heat energy utilization - Xiaolin Lyu; Ziqing Lin; Chunzhi Huang; Xinyue Zhang; Yang Lu; Zhong-Zhen Luo; Piaopiao Zhou; Zhigang Zou (Chemical Engineering Journal, 2024)

Quantitative trait locus analysis of gray leaf spot resistance in the maize IBM Syn10 DH population - Lina Cui; Mingfei Sun; Lin Zhang; Hongjie Zhu; Qianqian Kong; Ling Dong; Xianjun Liu; Xing Zeng; Yanjie Sun; Haiyan Zhang; Luyao Duan; Wenyi Li; et al. (Theoretical and Applied Genetics, 2024)

A recombinase polymerase amplification–SYBR Green I assay for the rapid and visual detection of Brucella - Jiang Chang; Nan Wang; Jun-Peng Zhan; Shi-Jun Zhang; De-Ying Zou; Feng Li; Ying Zhang; Yan-Song Li; Pan Hu; Shi-Ying Lu; Zeng-Shan Liu; Hong-Lin Ren (Folia Microbiologica, 2024)

A rho-type GTPase activating protein affects the growth and development of Cordyceps cicadae - Xueqian Li; Yu Zou; Neeraj Shrivastava; Jiandong Bao; Fu-Cheng Lin; Hongkai Wang (Archives of Microbiology, 2024)

IFNγ modulates the innate immune response via Toll-like receptors in green-spotted pufferfish (Tetraodon nigroviridis) - Wenjie Lai; Qinxi Dai; Zhenjiang Zou; Ziyi Wu; Ting Wang; Xue Yu; Yakang Song; Jingpeng Hou; Yuyou Lu; Dingrui Liu; Haoran Lin; Yong Zhang; et al. (Aquaculture International, 2024)

Can habitual tea drinking be an effective approach against age-related neurodegenerative cognitive disorders: A systematic review and meta-analysis of epidemiological evidence - Wei Quan; Yong Lin; Huiyu Zou; Maiquan Li; Jie Luo; Zhiyong He; Jie Chen; Zhonghua Liu (Critical Reviews in Food Science and Nutrition, 2024)

Intelligent DNA-based hydrogels: An outstanding programable and biocompatible material for food applications - Guo Li; Hao Huang; Liang Zou; Xiaochen Zhang; Xingyu Lin; Miral Javed; Xingcai Zhang; Yanqun Xu; Rong Ai; Zisheng Luo; Dong Li (Trends in Food Science & Technology, 2024)

Niche convergence and biogeographic history shape elevational tree community assembly in a subtropical mountain forest - Liang-Liang Ma; Sebastian Seibold; Marc W. Cadotte; Jia-Yun Zou; Jie Song; Zhi-Qiong Mo; Shao-Lin Tan; Lin-Jiang Ye; Wei Zheng; Kevin S. Burgess; Zhi-Fa Chen; De-Tuan Liu; et al. (Science of The Total Environment, 2024)

Structure of the eastern Arabian Sea upper water column in the middle Miocene: Implications for the development of the South Asian monsoon - Shixian Zou; Guanyu Lin; Anran Chen; Yueli Huang; Jeroen Groeneveld; Stephan Steinke; Liviu Giosan (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Study on the swelling of macromolecular geological organic matter with hydrocarbons and heteroatomic compounds - Tian Liang; Xiao-Hui Lin; Yan-Rong Zou; Zhao-Wen Zhan; Shuang Yu; Chang-Chun Pan; Ping’an Peng (Organic Geochemistry, 2024)

Hydrophobic nanosheet silicalite-1 zeolite for iodine and methyl iodide capture - Qian Zhao; Xin Li; Guangyuan Chen; Zeru Wang; Chuan Tan; Cheng Liu; Hao Zou; Jing Ma; Lin Zhu; Tao Duan (Journal of Hazardous Materials, 2024)

Adapting to diversified garlic-maize rotation systems by adjusting nitrogen application: Assessing crop yield, nitrogen utilization, and nitrogen footprint - Dan Liu; Qin Mo; Wei Zhang; Wei Lin; Wenjing Li; Maksat Batyrbek; Ruixia Ding; Hui Li; Baoping Yang; Yufeng Zou; Li Wang; Yantai Gan; et al. (Journal of Cleaner Production, 2024)

Review of formation mechanisms and quality regulation of chewiness in staple foods: Rice, noodles, potatoes and bread - Guifang Huang; David Julian McClements; Kuang He; Zipei Zhang; Ziqiang Lin; Zhenlin Xu; Yidong Zou; Zhengyu Jin; Long Chen (Food Research International, 2024)

Monitoring of soil heavy metals based on hyperspectral remote sensing: A review - Yulong Wang; Bin Zou; Liyuan Chai; Zhang Lin; Huihui Feng; Yuqi Tang; Rongcai Tian; Yulong Tu; Bo Zhang; Haijing Zou (Earth-Science Reviews, 2024)

Narrow bandgap Sn-Pb perovskite solar cells with high operational stability modulated by imidazoline derivative - Feilin Zou; Chenghao Duan; Zhuojia Lin; Zheng Zhang; Shuang Xu; Chang Chen; Jianwei Chen; Jiong Li; Shibing Zou; Liming Ding; Hongze Luo; Keyou Yan (Chemical Engineering Journal, 2024)

Tough and biodegradable C-lignin cross-linked polyvinyl alcohol supramolecular composite films with closed-looping recyclability - Tao Gui; Ling-Ping Xiao; Shuang-Lin Zou; Yue Zhang; Xu Fu; Chang-Hao Liu; Run-Cang Sun (Chemical Engineering Journal, 2024)

Immune-enhancing activity of compound polysaccharide on the inactivated influenza vaccine - Yang Zhang; Depeng Wang; Daotong Tan; Anqi Zou; Zhe Wang; Hao Gong; Yu Yang; Lishan Sun; Xiaoliang Lin; Ming Liang; Yi Yu; Xiaoxi He; et al. (Carbohydrate Polymers, 2024)

Effects of fertilization applications on soil aggregate organic carbon content and assessment of their influencing factors: A meta-analysis - Xi Yang; Yiwen Bao; Bowen Li; Ruixue Wang; Chao Sun; Donghao Ma; Lin Chen; Hongtao Zou; Jiabao Zhang (CATENA, 2024)

Erratum to: Cholesterol homeostasis regulated by ABCA1 is critical for retinal ganglion cell survival - Jialiang Yang; Yuhong Chen; Tongdan Zou; Bai Xue; Fang Yang; Xiangzhou Wang; Yibo Huo; Boyun Yan; Yuxia Xu; Shiyu He; Yi Yin; Jing Wang; et al. (Science China Life Sciences, 2024)

Recombinase polymerase amplification combined with Pyrococcus furiosus Argonaute for fast Salmonella spp. testing in food safety - Liyun Lin; Qiulan Luo; Liejun Li; Yuzhong Zheng; Huagui Wei; Jiayu Liao; Yaqun Liu; Mouquan Liu; Zhonghe Wang; Wanling Lin; Xianghui Zou; Hui Zhu; et al. (International Journal of Food Microbiology, 2024)

Cross-cultural adaptation, validation and reliability analysis of child food neophobia scale among Pakistani preschoolers - Muhammad Jamal Khan; Almab Zainab; Syed Ubaid Ullah Shah; Muhammad Bilal Khan; Minchan Wu; Jiaqi Huo; Hanshuang Zou; Qian Lin (Food Quality and Preference, 2024)

Combination of virtual screening, machine learning, molecular dynamics simulations and sensory evaluation to discover novel umami peptides from fermented Atlantic cod - Hao Zou; Hao Wang; Jinlong Zhao; Hua Feng; Shanyu Peng; Qingwen Liu; Zhihui Qin; Ziye Zhang; Hong Lin; Zhenxing Li (Food Bioscience, 2024)

Fabrication and characterization of W1/O/W2 double emulsions stabilized with Pleurotus geesteranus protein particles via one-step emulsification - Manhong Jin; Chuwen Li; Menghuan Ma; Qianwang Zheng; Liqiong Guo; Junfang Lin; Zhiwei Ye; Yuan Zou (Food Hydrocolloids, 2024)

Identification of toll-like receptor family and the immune function of new Sptlr-6 gene of Scylla paramamosain - Bohao Peng; Jiaming Lin; Haifu Wan; Pengfei Zou; Ziping Zhang; Yilei Wang (Fish & Shellfish Immunology, 2024)

DNA-AuNP encoders array Integrating a multi-modal coupled analysis approach for noninvasive precision screening of myocardial function injury disease in children - Haixia Zou; Wei Ye; Jienan Shen; Yahong Chen; Guangpei Qi; Lingzhi Ye; Lin Yang; Junjie Yuan; Yi Zeng; Hui Yang; Guangli Ren; Xiangmeng Qu (Chemical Engineering Journal, 2024)

Structural engineering of magnetite nanozymes for enhanced chemodynamic cancer therapy - Yong Qian; Jinglu Zou; Jiahui Zhang; Xingyu Wang; Xiangfu Meng; Yefeng Lin; Wenchu Lin; Miqin Zhang; Hui Wang (Chemical Engineering Journal, 2024)

Sophisticated construction of single-atom cobalt catalyst based on microbial hyphae for high-performance hydrogenation - Junhua Kuang; Minghao Gong; Gaofeng Chen; Li Peng; Chen Zou; Zhiqing Peng; Weiming Chen; Yin Li; Yuting Zhang; Tianwei Xue; Chuang Li; Yangyang Dong; et al. (Chemical Engineering Journal, 2024)

High-performance ceramic coatings for additive manufacturing biofunctional titanium alloy by regulating precipitation orientation - Yamei Mao; Qinyang Zhao; Jihua Geng; Weifeng Qian; Haiyan Zou; Tao Gong; Yongnan Chen; Guangrui Gao; Lin Wang; Yongqing Zhao (Chemical Engineering Journal, 2024)

Chemical constituents of the deep-sea-derived fungus Trichoderma simmonsii ZEN3 and their chemotaxonomic significance - Li-Fang Liu; Yuan Wang; Rong Chao; Lin Xu; Zheng-Biao Zou; Kai Zhang; Ming-Min Xie; Xian-Qiang Chen; Cheng-Hai Gao; Xian-Wen Yang (Biochemical Systematics and Ecology, 2024)

Sugarcane ScOPR1 gene enhances plant disease resistance through the modulation of hormonal signaling pathways - Wenhui Zou; Tingting Sun; Yao Chen; Dongjiao Wang; Chuihuai You; Shoujian Zang; Peixia Lin; Qibin Wu; Yachun Su; Youxiong Que (Plant Cell Reports, 2024)

Salinity decline promotes growth and harmful blooms of a toxic alga by diverting carbon flow - Xinguo Shi; Yazhen Zou; Yingjiao Zhang; Guangmao Ding; Yuchun Xiao; Senjie Lin; Jianfeng Chen (Global Change Biology, 2024)
Global climate change intensifies the water cycle and makes freshest waters become fresher and vice‐versa. But how this change impacts phytoplankton in coastal, particularly harmful algal blooms (HABs), remains poorly understood. Here, we monitored a coastal bay for a decade and found a significant correlation between salinity decline and the increase of Karenia mikimotoi blooms. To examine the physiological linkage between salinity decreases and K. mikimotoi blooms, we compare chemical, physiological and multi‐omic profiles of this species in laboratory cultures under high (33) and low (25) salinities. Under low salinity, photosynthetic efficiency and capacity as well as growth rate and cellular protein content were significantly higher than that under high salinity. More strikingly, the omics data show that low salinity activated the glyoxylate shunt to bypass the decarboxylation reaction in the tricarboxylic acid cycle, hence redirecting carbon from CO 2 release to biosynthesis. Furthermore, the enhanced glyoxylate cycle could promote hydrogen peroxide metabolism, consistent with the detected decrease in reactive oxygen species. These findings suggest that salinity declines can reprogram metabolism to enhance cell proliferation, thus promoting bloom formation in HAB species like K. mikimotoi , which has important ecological implications for future climate‐driven salinity declines in the coastal ocean with respect to HAB outbreaks.

Status and Challenges of Marine Current Turbines: A Global Review - Yajing Gu; Tian Zou; Hongwei Liu; Yonggang Lin; He Ren; Qingjun Li (Journal of Marine Science and Engineering, 2024)
Over the past few decades, marine current energy utilization has transitioned from conceptual demonstrations to industrial-scale prototypes. This progression now approaches a crucial phase emphasizing the need for industrialization and commercialization. This paper provides an in-depth examination of the developmental status of large-scale marine current turbines and arrays, underscoring the promising prospects for marine current energy systems. Despite the significant advancements, the deployment of these systems has revealed several challenges, including blade design optimization, transmission system selection, and the establishment of appropriate test sites. Addressing these issues is essential for technological maturity and economic feasibility, which will foster the next wave of innovation in marine energy systems. Furthermore, the paper offers various perspectives for future applications.

Identification of SNPs and candidate genes associate with growth performance in all-female mandarin fish (Siniperca chuatsi) by a genome-wide association study - Dingrui Liu; Jin Zhang; Zhenjiang Zou; Chen Long; Jiaqi Lin; Junyan Zeng; Jingpeng Hou; Linqiang Han; Yanlin Jiang; Shuisheng Li; Yong Zhang (Aquaculture, 2024)

Tunnel linings inspection using Bayesian-Optimized (BO) calibration of multiple Line-Scan Cameras (LSCs) and a Laser Range Finder (LRF) - Lin Zou; Yuchun Huang; Yanan Li; Yuxi Chen (Tunnelling and Underground Space Technology, 2024)

Graphitic carbon nitride nanosheets mitigate cadmium toxicity in L. by promoting cadmium retention in root and improving photosynthetic performance - Kai Xu; Yunyu Guo; Chenghua Xing; Ronglong Fu; Bin Zou; Rongchuan Liu; Luyi Cai; Jianfang Yan; Xi-Lin Wu; Miaozhen Cai (Journal of Environmental Sciences, 2024)

Experimental and modeling study of ignition delay times of n-C5H12 and C3H6 under O2/CO2 atmospheres - Chao Peng; Chun Zou; Jiaxin Ren; Qianjin Lin; Wenxiang Xia; Lingfeng Dai; Jiacheng Liu; Wenyu Li (Fuel, 2024)

Rapid determination of geographical authenticity and pungency intensity of the red Sichuan pepper (Zanthoxylum bungeanum) using differential pulse voltammetry and machine learning algorithms - Di Zhang; Zitao Lin; Lilei Xuan; Minmin Lu; Bolin Shi; Jiyong Shi; Fatao He; Maurizio Battino; Lei Zhao; Xiaobo Zou (Food Chemistry, 2024)

Regulation of photoassimilate transportation and nitrogen uptake to decrease greenhouse gas emissions in ratooning rice with higher economic return by optimized nitrogen supplies - Jingnan Zou; Hailong Xu; Chaojie Lan; Bin Qin; Jinying Li; Witness Joseph Nyimbo; Hongmei Lin; Ziqin Pang; Nyumah Fallah; Chunlin Guo; Changxun Fang; Zhixing Zhang; et al. (Field Crops Research, 2024)

Impacts of large-scale suspended mussel farm on seston depletion - Wei Zhong; Jun Lin; Qingping Zou; Hidekatsu Yamazaki; Wei Yang; Guanlin Yang (Estuarine, Coastal and Shelf Science, 2024)

Rhythmic mild photothermal therapy enhancing anti-PD-L1 response for oral squamous cell carcinoma immunotherapy - Tao Liu; Shilin Guo; Dongyao Zhang; Diya Xie; Xinyu Zhang; Lin Chen; Yanyi Wang; Huihui Zou; Linzhong Yang; Meng Zhou; Xin Tong; Jianchuan Ran; et al. (Chemical Engineering Journal, 2024)

Highly efficient bioregeneration of high temperature-pyrolyzed biochar after trichloroethylene adsorption through biodegradation of Dehalococcoides - Xuqing Zou; Yizhou Feng; Min Hu; Daohui Lin; Kun Yang; Wenhao Wu (Chemical Engineering Journal, 2024)

Post-disaster spatial reconstruction from the perspective of a rural settlement niche in the upper reaches of the Minjiang River - Yanguo Liu; Li Wang; Qiang Zou; Jingji Li; Yafeng Lu; Lin Li; Binni Xu; Lihui Wang (Journal of Mountain Science, 2024)

On the brink of explosion? Identifying the source and potential spread of introduced Zosterops white-eyes in North America - Devon A. DeRaad; Marlon E. Cobos; Natalie R. Hofmeister; Lucas H. DeCicco; Madhvi X. Venkatraman; Isao Nishiumi; Bailey McKay; Fa-Sheng Zou; Kazuto Kawakami; Chang-Hoe Kim; Ruey-Shing Lin; Cheng-Te Yao; et al. (Biological Invasions, 2024)

Cytotoxic flavonoids from the leaves of Callicarpa nudiflora hook - Jin-Lin Zhang; Yin Xiao; Lu Zhou; Shao-Yang Yin; Jia-Yin Long; Hong-Lin Xiang; Xi-Feng Sheng; Hui Zou (Natural Product Research, 2024)

Mechanism of peroxymonosulfate activation by nanoparticle Co@N–C: Experimental investigation and theoretical calculation - Mu Li; Lin Lin; Wei Zhang; Yubin Zou; Jiahui Hu; Yin Li; Bing Li; Feiyun Sun; Xiao-yan Li (Chemosphere, 2024)

Plant and microbial response in constructed wetland treating tetracycline antibiotic polluted water: Evaluating the effects of microplastic size and concentration - Weiliang Pan; Yi Zhou; Huimin Xie; Lin Liang; Guoyuan Zou; Lianfeng Du; Xuan Guo (Chemosphere, 2024)

Co-foliar application of zinc and nano-silicon to rice helps in reducing cadmium exposure risk: Investigations through in-vitro digestion with human cell line bioavailability assay - Qiang Lin; Yasir Hamid; Honhang Wang; Min Lu; Xuerui Cao; Tong Zou; Zhiqin Chen; Bilal Hussain; Ying Feng; Tingqiang Li; Zhenli He; Xiaoe Yang (Journal of Hazardous Materials, 2024)

Trace Co(II) triggers peracetic acid activation in phosphate buffer: New insights into the oxidative species responsible for ciprofloxacin removal - Feifei Liu; Yubin Zou; Hebin Liang; Jiahui Hu; Yin Li; Lin Lin; Xiaoyan Li; Bing Li (Journal of Hazardous Materials, 2024)

Metal-phenolic nanocatalyst rewires metabolic vulnerability for catalytically amplified ferroptosis - Yang Zhu; Xuegang Niu; Tiantian Wu; Junjie Cheng; Jianhua Zou; Yuanbo Pan; Yu Tian; Wei Huang; Chengyu Ding; Yuanxiang Lin; Dezhi Kang; Xiaoyuan Chen (Chemical Engineering Journal, 2024)

Environmental exposure to per- and polyfluoroalkyl substances mixture and asthma in adolescents - Yi-Fan Wang; Li Li; Xu Wang; Ya-Nan Yun; Xue-Lin Wang; En-Yang He; Ming-Kun Song; Xue-Hong Xia; Ying-Xue Zou (International Archives of Occupational and Environmental Health, 2024)

Lightweight Underwater Object Detection Algorithm for Embedded Deployment Using Higher-Order Information and Image Enhancement - Changhong Liu; Jiawen Wen; Jinshan Huang; Weiren Lin; Bochun Wu; Ning Xie; Tao Zou (Journal of Marine Science and Engineering, 2024)
Underwater object detection is crucial in marine exploration, presenting a challenging problem in computer vision due to factors like light attenuation, scattering, and background interference. Existing underwater object detection models face challenges such as low robustness, extensive computation of model parameters, and a high false detection rate. To address these challenges, this paper proposes a lightweight underwater object detection method integrating deep learning and image enhancement. Firstly, FUnIE-GAN is employed to perform data enhancement to restore the authentic colors of underwater images, and subsequently, the restored images are fed into an enhanced object detection network named YOLOv7-GN proposed in this paper. Secondly, a lightweight higher-order attention layer aggregation network (ACC3-ELAN) is designed to improve the fusion perception of higher-order features in the backbone network. Moreover, the head network is enhanced by leveraging the interaction of multi-scale higher-order information, additionally fusing higher-order semantic information from features at different scales. To further streamline the entire network, we also introduce the AC-ELAN-t module, which is derived from pruning based on ACC3-ELAN. Finally, the algorithm undergoes practical testing on a biomimetic sea flatworm underwater robot. The experimental results on the DUO dataset show that our proposed method improves the performance of object detection in underwater environments. It provides a valuable reference for realizing object detection in underwater embedded devices with great practical potential.

Effects of medium- and long-term high-salinity environments on free amino acid content and related genes of Sinonovacula constricta - Jie Zhu; Hongqiang Xu; Zihao Zou; Hanhan Yao; Zhihua Lin; Yinghui Dong (Frontiers in Marine Science, 2024)
Introduction The razor clam, Sinonvacula constricta, one of the important mariculture bivalves in China, has unique flavor and wide salinity adaptability. The unique flavor mainly depends on the content of free amino acids and other umami substances in vivo. However, the flavor divergence of razor clam caused by the variable salinity breeding environment, while the mechanisms remain unclear. Methods Here, the razor clams were cultured in high salinity (30 ppt) and normal salinity (20 ppt) for eight weeks, and the effects of salinity on free amino acids and related genes expression in S. constricta were investigated by transcriptomics and metabolomics method. Results The results showed the free amino acid content under high salinity environment was significantly higher than normal salinity environment through the duration of the experiment (P < 0.05). The combination of transcriptomic and metabolomic data also indicated that high salinity environment resulted in enhanced metabolism of free amino acids. Furthermore, eight genes such as RALDH2, ACOX1, ALDH-E2 were potentially important for enhancing free amino acids metabolism under high salinity environment. Discussion This study preliminarily explained the regulation processes of high salinity environment on the metabolism of free amino acids in razor clams, providing a reference for the flavor regulation mechanism.

Long-term biogas slurry application increases microbial necromass but not plant lignin contribution to soil organic carbon in paddy soils as regulated by fungal community - Zhaoming Chen; Jinchuan Ma; Junwei Ma; Jing Ye; Qiaogang Yu; Ping Zou; Wanchun Sun; Hui Lin; Feng Wang; Xinlin Zhao; Qiang Wang (Waste Management, 2024)

Prediction of molecular-specific mutagenic alerts and related mechanisms of chemicals by a convolutional neural network (CNN) model based on SMILES split - Chao Chen; Zhengliang Huang; Xuyan Zou; Sheng Li; Di Zhang; Shou-Lin Wang (Science of The Total Environment, 2024)

Long-term conservation tillage enhances microbial carbon use efficiency by altering multitrophic interactions in soil - Ling Ma; Guixiang Zhou; Jiabao Zhang; Zhongjun Jia; Hongtao Zou; Lin Chen; Congzhi Zhang; Donghao Ma; Changdong Han; Yan Duan (Science of The Total Environment, 2024)

Influence of propulsion shafting longitudinal vibration on the excitation force and vortex dynamics characteristics of pump-jet propulsor - Donglin Zou; Lin Xue; Qiang Lin; Jianghai Xu; Xinguo Dong; Na Ta; Zhushi Rao (Ocean Engineering, 2024)

Sedimentary controls of shale heterogeneity: A case study of Wufeng–Longmaxi shales in the south Sichuan Basin, China - Sichen Lin; Haihua Zhu; Shuyou Shi; Zhen Zou; Xi Zhang; Tingshan Zhang; Xiuru Ye; Lei Chen; Fuyuan Zhang (Journal of Asian Earth Sciences, 2024)

A quantitative model to estimate major oxide abundances on the Moon based on in situ reflectance spectral data of Chang'e missions - Zhenxing Zhao; Yazhou Yang; Xing Wu; Yang Liu; Feng Zhang; Rui Xu; Zhiping He; Yangting Lin; Yongliao Zou (Icarus, 2024)

Physical drivers of Noctiluca scintillans (Dinophyceae) blooms outbreak in the northern Taiwan Strait: A numerical study - Zhonghao Lin; Peng Zhan; Jianping Li; Jun Sasaki; Zhongfeng Qiu; Chun Chen; Shuangyan Zou; Xiaotong Yang; Haifeng Gu (Harmful Algae, 2024)

Sediment provenance changes in the southwestern Okhotsk Sea since MIS 5 and their implications for sediment transport dynamics - Anqi Wang; Zhengquan Yao; Xuefa Shi; Kunshan Wang; Yanguang Liu; Jianjun Zou; Yuriy Vasilenko; Fengdeng Shi; Zhi Dong; Xiaojing Wang; Aimei Zhu; Zhengfan Lin; et al. (Global and Planetary Change, 2024)

A Potential Source of Bias in Group-Level EEG Microstate Analysis - Michael Murphy; Jun Wang; Chenguang Jiang; Lei A. Wang; Nataliia Kozhemiako; Yining Wang; Jun Wang; Chenguang Jiang; Guanchen Gai; Kai Zou; Zhe Wang; Xiaoman Yu; et al. (Brain Topography, 2024)

Fluorescence detecting glycopeptide antibiotics via a dynamic molecular switch - Xiaomei Zou; Yanting Lin; Shihui Zhang; Tao Deng; Ximing Xu; Yingchun Zhou; Zhihui Liu; Weiguo Lu; Qingzhong Hu; Chaozhan Lin; Chenchen Zhu; Fang Liu (Analytica Chimica Acta, 2024)

An Improved VO Method for Collision Avoidance of Ships in Open Sea - Mao Zheng; Kehao Zhang; Bing Han; Bowen Lin; Haiming Zhou; Shigan Ding; Tianyue Zou; Yougui Yang (Journal of Marine Science and Engineering, 2024)
In order to effectively deal with collisions in various encounter situations in open water environments, a ship collision avoidance model was established, and multiple constraints were introduced into the velocity obstacle method, a method to determine the ship domain by calculating the safe distance of approach was proposed. At the same time, the ship collision avoidance model based on the ship domain is analyzed, and the relative velocity set of the collision cone is obtained by solving the common tangent line within the ellipse. The timing of starting collision avoidance is determined by calculating the ship collision risk, and a method for ending collision avoidance is proposed. Finally, by comparing the simulation experiments of the improved algorithm with those of the traditional algorithm and the actual ship experiment results of manual ship maneuvering, it is shown that the method can effectively avoid collisions based on safe encounter distances that comply with navigation experience in different encounter situations. At the same time, it has better performance in collision avoidance behavior. It has certain feasibility and practical applicability.

Salt intrusion dynamics in a well-mixed sub-estuary connected to a partially to well-mixed main estuary - Zhongyuan Lin; Guang Zhang; Huazhi Zou; Wenping Gong (Ocean Science, 2024)
Salt intrusion in estuaries has been exacerbated by climate change and human activities. Previous studies have primarily focused on salt intrusion in the mainstem of estuaries, whereas those in sub-estuaries (those that branch off their main estuaries) have received less attention. During an extended La Niña event from 2021 to 2022, a sub-estuary (the East River estuary) alongside the Pearl River estuary, China, experienced severe salt intrusions, posing a threat to the freshwater supply in the surrounding area. Observations revealed that maximum salinities in the main estuary typically preceded spring tides, exhibiting significant asymmetry in salinity rise and fall over a fortnightly timescale. In contrast, in the upstream region of the sub-estuary, the variation in salinity was in phase with that of the tidal range, and the rise and fall of the salinity were more symmetrical. Inspired by these observations, we employed idealized numerical models and analytical solutions to investigate the underlying physics behind these behaviors. It was discovered that under normal dry conditions (with a river discharge of 1500 m3 s−1 at the head of the main estuary), the river–tide interaction and change in horizontal dispersion accounted for the in-phase relationship between the salinity and tidal range in the upstream region of the sub-estuary. Under extremely dry conditions (i.e., a river discharge of 500 m3 s−1 at the head of the main estuary), salinity variations were in phase with those of the tidal range in the middle as well as the upstream region of the sub-estuary. The variation in salinity in the main estuary along with those in salt dispersion and freshwater influx inside the sub-estuary collectively influenced salinity variation in the well-mixed sub-estuary. These findings have important implications for water resource management and salt intrusion prevention in the catchment area.

Human-influenced changes in pollution status and potential risk of sediment heavy metals in Xincun Bay, a typical lagoon of Hainan, China - Zhe Hao; Jian Qian; Fangqin Zheng; Bo Lin; Min Xu; Weihua Feng; Xinqing Zou (Marine Pollution Bulletin, 2024)

Foliar application of plant growth regulators for enhancing heavy metal phytoextraction efficiency by Sedum alfredii Hance in contaminated soils: Lab to field experiments - Zhiqin Chen; Qizhen Liu; Shijun Zhang; Yasir Hamid; Jiapan Lian; Xiwei Huang; Tong Zou; Qiang Lin; Ying Feng; Zhenli He; Xiaoe Yang (Science of The Total Environment, 2024)

Undescribed matrine-type alkaloids from Sophora alopecuroides with anti-inflammatory activity - Ding Luo; Jia-Wen Zou; Jing-Hao Wang; He Tian; Hua-Yan Xie; Tian-Xi Zhu; Hui-Hui Zhu; Lu-Ming Deng; Chun-Lin Fan; Hao Wang; Guo-Cai Wang; Yu-Bo Zhang (Phytochemistry, 2024)

Transcriptome analysis reveals dysfunction of the endoplasmic reticulum protein processing in the sonic muscle of small yellow croaker (Larimichthys polyactis) following noise exposure - Xuguang Zhang; Xianming Tang; Jianan Xu; Yueping Zheng; Jun Lin; Huafeng Zou (Marine Environmental Research, 2024)

Effects of yeast screened from traditional fermented milk on commercial fermented milk as adjunct flavor culture - Hai-yan Kang; Xiao-lin Ao; Qing Tang; Hongli Li; Yang Fan; Ai-ping Liu; Li-kou Zou; Shu-liang Liu; Yong Yang; Ning Zhao; Jian-long Li (Food Bioscience, 2024)

Slow-release fertilizer deep placement increased rice yield and reduced the ecological and environmental impact in Southeast China: A life-cycle perspective - Chaojie Lan; Jingnan Zou; Jinying Li; Hailong Xu; Weiwei Lin; Peiying Weng; Changxun Fang; Zhixing Zhang; Hongfei Chen; Wenxiong Lin (Field Crops Research, 2024)

Diversity and composition of microbial communities in Jinsha earthen site under different degree of deterioration - Jing Li; Yanqiu He; Changjie He; Lin Xiao; Ning Wang; Luman Jiang; Juncheng Chen; Ke Liu; Qiang Chen; Yunfu Gu; Menggen Ma; Xiumei Yu; et al. (Environmental Research, 2024)

Machine learning-based estimation and mitigation of nitric oxide emissions from Chinese vegetable fields - Zhaoqiang Han; Yi Leng; Zhirong Sun; Haiyan Lin; Jinyang Wang; Jianwen Zou (Environmental Pollution, 2024)

Perturbation of IP3R-dependent endoplasmic reticulum calcium homeostasis by PPARδ-activated metabolic stress leads to mouse spermatocyte apoptosis: A direct mechanism for perfluorooctane sulfonic acid-induced spermatogenic disorders - Wang Yang; Xi Ling; Shijun He; Haonan Cui; Lihong Wang; Zeyu Yang; Huihui An; Peng Zou; Qing Chen; Lei Sun; Huan Yang; Jinyi Liu; et al. (Environmental Pollution, 2024)

Warming and wetting-induced soil acidification triggers methanotrophic diversity loss and species turnover in an alpine ecosystem - Chaonan Li; Changting Wang; Ping Zou; Lin Xu; Haijun Liao; Nan Lan; Li Lei; Wenjun Xiong; Weidong Kong; Junming Wang; Xiangzhen Li (CATENA, 2024)

Novel cytochrome P450s for various hydroxylation of steroids from filamentous fungi - Guojuan Yi; Hanlu Zou; Tao Long; Tolbert Osire; Lin Wang; Xiaoyun Wei; Mengfei Long; Zhiming Rao; Guojian Liao (Bioresource Technology, 2024)

Oncogenic lncRNA FAM215A promotes the malignant cell phenotypes of acute myeloid leukemia (AML) cell lines - Lin Li; Liuyan Xin; Xiang Yang; Zhengrong Zou (Journal of Molecular Histology, 2024)

Variations in Blood Copper and Possible Mechanisms During Pregnancy - Lihua Guan; Yifei Wang; Liling Lin; Yutong Zou; Ling Qiu (Biological Trace Element Research, 2024)

Dual-emissive europium doped UiO-66-based ratiometric light-up biosensor for highly sensitive detection of histidinemia biomarker - Li Li; Lin-Lin Zhang; Jin Zou; Jiamin Zou; Lu-Ying Duan; Yansha Gao; Guanwei Peng; Xigen Huang; Limin Lu (Analytica Chimica Acta, 2024)

Ferroptosis: underlying mechanisms and involvement in neurodegenerative diseases - Yi Wang; HongJing Li; QianXiong He; Rong Zou; JinRui Cai; Lin Zhang (Apoptosis, 2024)

Boron removal in seawater desalination by progressive freezing-melting - Rui Mei; Tongguo Zhao; Yan Zhang; Hao Lin; Chen Zhao; Lin Lin; Yihong Zou; Yucan Liu (Environmental Science and Pollution Research, 2024)

High value-added application of natural forest product α- pinene: design, synthesis and 3D-QSAR study of novel α- campholenic aldehyde-based 4-methyl-1,2,4-triazole-thioether compounds with significant herbicidal activity - Baoyu Li; Xianlong Yin; Bo Cen; Wengui Duan; Guishan Lin; Xiaoyu Wang; Renxuan Zou (Natural Product Research, 2024)

Influence of Emission-Control Areas on the Eco-Shipbuilding Industry: A Perspective of the Synthetic Control Method - Lang Xu; Zeyuan Zou; Lin Liu; Guangnian Xiao (Journal of Marine Science and Engineering, 2024)
Annex VI of the International Convention for the Prevention of Pollution from Ships (MARPOL Convention), adopted in October 2008, was dedicated to addressing environmental issues caused by ships, especially in ports, inland waterways, and some sea areas with concentrated routes and high navigational density. This study utilizes a regional-level ship dataset to assess the influences of emission-control areas (ECAs) on the ecological shipbuilding industry by fitting the policy utility through the synthetic control method and testing robustness via the difference-in-differences method. The outcomes of this study show that the cumulative new orders for eco-designed ships in China, The Netherlands, Republic of Korea, the UK, and the USA increased by 3401, 81, 234, 549, and −1435, respectively, after the implementation of ECAs. Compared to the implementation of ECAs, the increases were about 32%, 20%, 41%, 66%, and −83%, respectively.

Effective photocatalytic inactivation of Microcystis aeruginosa by Ag3VO4/BiVO4 heterojunction under visible light - Gongduan Fan; Qiuan Lin; Jiuhong Lin; Mingqian Xia; Shoubin Chen; Jing Luo; Jianyong Zou; Zhanglin Hong; Kaiqin Xu (Chemosphere, 2024)

Phosphorylation regulation of Lv-β-catenin of Litopenaeus vannamei by an immediate early protein WSV083 to reduce cell adhesion - Wenhao Wu; Chenchen Zou; Hong Shi; Chuanqi Wang; Wenyang Lin; Yueling Zhang; Yibin He; Lingwei Ruan (Aquaculture, 2024)

Soil protists are more resilient to the combined effect of microplastics and heavy metals than bacterial communities - Lu Ma; Lin Zhang; Siyi Zhang; Min Zhou; Wei Huang; Xinyue Zou; Zhili He; Longfei Shu (Science of The Total Environment, 2024)

Use of a new Tibetan Plateau network for permafrost to characterize satellite-based products errors: An application to soil moisture and freeze/thaw - Jingyao Zheng; Tianjie Zhao; Haishen Lü; Defu Zou; Nemesio Rodriguez-Fernandez; Arnaud Mialon; Philippe Richaume; Jianshe Xiao; Jun Ma; Lei Fan; Peilin Song; Yonghua Zhu; et al. (Remote Sensing of Environment, 2024)

Lignan glucosides from Gentiana macrophylla with potential anti-arthritis and hepatoprotective activities - Pei-Qi Huang; Kai-Wen Kang; Dan-Yu Huang; Chun-Lin Zhao; Hao Zheng; Yong-Xin Luo; Yan Wen; Ming-Feng Zou; Dong-Li Li; Ri-Hui Wu; Yun-Cai Tian; Yong Tian; et al. (Phytochemistry, 2024)

Effects of high-concentration influent suspended solids on aerobic granulation in sequencing batch reactors treating real textile wastewater - Jianrui Lin; Hangtian He; Jinte Zou; Yongyuan Yang; Jun Li (Journal of Water Process Engineering, 2024)

Bacteria-driven copper redox reaction coupled electron transfer from Cr(VI) to Cr(III): A new and alternate mechanism of Cr(VI) bioreduction - Xiaoye Min; Kejing Zhang; Jianxin Chen; Liyuan Chai; Zhang Lin; Long Zou; Weizao Liu; Chunlian Ding; Yan Shi (Journal of Hazardous Materials, 2024)

Simulated in vitro gastrointestinal digestion of β-lactoglobulin treated by ultrasound: Detection of peptides profile and the antioxidant activity - Yan-hong Shao; Lin Zou; Zi-hao Xiong; Ling-xia Su; Zong-cai Tu; Jun Liu (Food Research International, 2024)

Boosting the charge transport and stability of metal halide perovskite with boron nitride nanosheets for X-ray detection and imaging - Fang Yao; Zhenglin Jia; Junqi Dong; Ruiming Li; Yujie Yang; Haitao Tang; Wusheng Zou; Jiangbin Zhao; Yong Liu; Zhu Wang; Gaokui He; Qianqian Lin (Chemical Engineering Journal, 2024)

Isolation and identification of Chlorella sorokiniana HDMA-16 and its cultivation potential in flax retting wastewater - Meiqi Wang; Jing Xu; Jialin Zou; Hongzhi Ling; Jingping Ge; Yimeng Lin; Wenxiang Ping (Algal Research, 2024)

Preparation and characterization of EI-Co/Zr@AC and the mechanisms underlying its removal for atrazine in aqueous solution - Xiaolong Yang; Danxia Liu; Huijun He; Jianmei Zou; Dunqiu Wang; Lin Zhang; Yiyan Tang (Environmental Science and Pollution Research, 2023)

Discovery of the large-scale Eocene Xiwu Pb–Zn–Ag deposit in the Tethyan Himalaya: Geochronology, geochemistry, and C–H–O–S–Pb–Sr–Nd isotopes - Hua-Wen Cao; Qiu-Ming Pei; Xiao Yu; M. Santosh; Guang-Ming Li; Lin-Kui Zhang; Hao Zou; Lei Dong; Ke Gao; Zuo-Wen Dai; Jin-Biao Ai; Shuang-Shuang Lan; et al. (Gondwana Research, 2023)

Effect of protein-glutaminase on the texture, rheology, microstructure and sensory properties of skimmed set-type yoghurt - Jiajing Wu; Tian Dai; Rongyu Lin; Jinjin Niu; Zhen Li; Zhongyi Chang; Caifeng Jia; Chunjing Zou; Deming Jiang; Mingfei Jin; Jing Huang; Hongliang Gao (Food Chemistry, 2023)

Transcriptome analysis of the effects of maternal fructose exposure during gestation and lactation on the cytoskeleton of offspring hippocampus - Yongyong Zhong; Yuchen Zou; Lin Cheng; Qing Guo; Yidan Chang; Wei Wei (Food Bioscience, 2023)

Prediction of resilience and cohesion of deep-fried tofu by ultrasonic detection and LightGBM regression - Lilei Xuan; Zitao Lin; Jing Liang; Xiaowei Huang; Zhihua Li; Xinai Zhang; Xiaobo Zou; Jiyong Shi (Food Control, 2023)

3D binder-free nanoarchitecture design of porous silicon/graphene fibers for ultrastable lithium storage - Yongbiao Mu; Ruijie Zhang; Bu-ke Wu; Ming Yang; Youqi Chu; Qing Zhang; Lingfeng Zou; Xianbin Wei; Zifan Liao; Haixiang Ren; Yiju Li; Lin Zeng (Chemical Engineering Journal, 2023)

Mixed B-site driven [InBr4]− tetrahedral efficient blue emission - Tongzhou Li; Tao Huang; Qilin Wei; Wenchao Lin; Xiaoyan Lu; Xiaodong Shen; Shichao Zhou; Weizheng Liang; Bingsuo Zou (Chemical Engineering Journal, 2023)

A Comparative Analysis of Three Rutaceae Species Reveals the Multilayered Mechanisms of Citrus in Response to Huanglongbing Disease - Yunuo Liu; Liting Dong; Danlu Ran; Shuai Wang; Rongrong Qu; Lin Zheng; Aihong Peng; Yongrui He; Shanchun Chen; Xiuping Zou (Journal of Plant Growth Regulation, 2023)

Impacts of climate change on herpetofauna diversity in the Qinghai‐Tibetan Plateau - Alex Plimo Karuno; Xue Mi; Youhua Chen; Da‐Hu Zou; Wei Gao; Bao‐Lin Zhang; Wei Xu; Jie‐Qiong Jin; Wen‐Jing Shen; Song Huang; Wei‐Wei Zhou; Jing Che (Conservation Biology, 2023)
Although numerous studies on the impacts of climate change on biodiversity have been published, only a handful are focused on the intraspecific level or consider population‐level models (separate models per population). We endeavored to fill this knowledge gap relative to the Qinghai‐Tibetan plateau (QTP) by combining species distribution modeling (SDMs) with population genetics (i.e., population‐level models) and phylogenetic methods (i.e., phylogenetic tree reconstruction and phylogenetic diversity analyses). We applied our models to 11 endemic and widely distributed herpetofauna species inhabiting high elevations in the QTP. We aimed to determine the influence of environmental heterogeneity on species’ responses to climate change, the magnitude of climate‐change impacts on intraspecific diversity, and the relationship between species range loss and intraspecific diversity losses under 2 shared socioeconomic pathways (SSP245 and SSP585) and 3 future periods (2050s, 2070s, and 2090s). The effects of global climatic change were more pronounced at the intraspecific level (22% of haplotypes lost and 36% of populations lost) than the morphospecies level in the SSP585 climate change scenario. Maintenance of genetic diversity was in general determined by a combination of factors including range changes, species genetic structure, and the part of the range predicted to be lost. This is owing to the fact that the loss and survival of populations were observed in species irrespective of the predicted range changes (contraction or expansion). In the southeast (mountainous regions), climate change had less of an effect on range size (>100% in 3 species) than in central and northern QTP plateau regions (range size

Study on Vibration Attenuation Performance of Pump-Jet Propulsor Duct with an Axial Slot Structure - Lin Ke; Jinming Ye; Xiaoyu Zou (Journal of Marine Science and Engineering, 2023)
To reduce the structural vibration of the duct structure in pump-jet propulsors (PJPs) and lower the induced vibration noise, this study learned from the “processor box” in an aero-engine and set a certain number of axial slots in the PJP. First, using finite element analysis, both dry and wet modes of the PJP ducts with and without an axial slot structure were simulated for analysis. Next, with the two-way fluid–solid coupling calculation method, the vibration performances of the PJP ducts with and without axial slots were contrasted and studied. The differences in calculation results under different duct structures were compared from three aspects—the vibration displacement, velocity, and acceleration of the duct and mesh nodes. According to the present results, after the addition of axial slots, the vibration displacement, the vibration velocity, and the vibration acceleration can be significantly reduced, especially in the back segment of the duct. Meanwhile, it can be concluded that it is quite important to select vibration acceleration for structural analysis in evaluating the PJP vibration. This study can provide a reference for further designs of low-noise PJPs.

Efficient activation of peroxymonosulfate by CoMg2Mn-LDO for the degradation of orange Ⅱ: The important synergy of Mg - Shulin Zuo; Lin Zhao; Xiaoyan Zou; Yunqi Wu; Lilin Wang; Ling Luo; Yan He; Yanzong Zhang (Chemosphere, 2023)

Some Type III effectors of Ralstonia solanacearum may suppress host RNA silencing for function - Ping Qiu; Yixing Xu; Lihong Chen; Wenzhong Lin; Huasong Zou; Zujian Wu; Zhenguo Du (Physiological and Molecular Plant Pathology, 2023)

Numerical method for whipping response of ultra large container ships under asymmetric slamming in regular waves - Lin Lu; Huilong Ren; Hui Li; Jian Zou; Sangui Chen; Ruixiang Liu (Ocean Engineering, 2023)

Propeller-shaft-hull coupling acoustic radiation characteristics induced by friction self-excitation of the stern bearing - Chang-Gang Lin; Ming-Song Zou; Li-Bo Qi; Can Sima; Ji-Long Chu (Ocean Engineering, 2023)

Polyphenols modulate microalgae metabolism with a particular increment in lipid accumulation - Li-Gong Zou; Dan-Lin Zheng; Yi-Tong Yao; Fu-Fang Wen; Da-Wei Li; Yu-Feng Yang; Wei-Dong Yang; Srinivasan Balamurugan; Hang Fai Kwok; Hong-Ye Li (Fuel, 2023)

Analysis of the spatial-temporal evolution of Green and low carbon utilization efficiency of agricultural land in China and its influencing factors under the goal of carbon neutralization - Jun Fu; Rui Ding; Yu-qi Zhu; Lin-yu Du; Si-wei Shen; Li-na Peng; Jian Zou; Yu-xuan Hong; Juan Liang; Ke-xin Wang; Wen-qian Xiao (Environmental Research, 2023)

Emissions from international airport and its impact on air quality: A case study of beijing daxing international airport (PKX), China - Ya-nan Wang; Chao Zou; Tian-ge Fang; Nai-xiu Sun; Xiao-yu Liang; Lin Wu; Hong-jun Mao (Environmental Pollution, 2023)

Study on the deformation and cracking characteristics of bamboo fiber reinforced concrete anti-slide pile considering the aspect ratio, fiber dosage and its coupling effect with rebars - Lin Li; Cong Yang; Wenli Shu; Haiyan Xu; Yusheng Zeng; Zhanyuan Zhu; Zuyin Zou; Shaomin Jia (Engineering Structures, 2023)

Soil depths and developmental stages of biological soil crusts are more important than shrub cover in structuring prokaryotic communities - Lin Xu; Yongping Kou; Wenjun Xiong; Chaonan Li; Ping Zou; Bingjie Jiao; Zhenfeng Xu; Bo Tan; Minjie Yao; Bingchang Zhang; Xiangzhen Li (CATENA, 2023)

Response of topsoil Fe-bound organic carbon pool and microbial community to Spartina alterniflora invasion in coastal wetlands - Meifen Lin; Yu Chen; Liwen Cheng; Yi Zheng; Weiqi Wang; Jordi Sardans; Zhaoliang Song; Georg Guggenberger; Yuanchun Zou; Xueli Ding; Akash Tariq; Fanjiang Zeng; et al. (CATENA, 2023)

Developmental dynamics of the single nucleus regulatory landscape of pig hippocampus - Siyu Yang; Dong Chen; Lei Xie; Xiaoxiao Zou; Yanyuan Xiao; Lin Rao; Tianxiong Yao; Qing Zhang; Liping Cai; Fei Huang; Bin Yang; Lusheng Huang (Science China Life Sciences, 2023)

A review on recent advances in LED-based non-thermal technique for food safety: current applications and future trends - Xinpeng Yu; Peng Zheng; Yuan Zou; Zhiwei Ye; Tao Wei; Junfang Lin; Liqiong Guo; Hyun-Gyun Yuk; Qianwang Zheng (Critical Reviews in Food Science and Nutrition, 2023)

Targeted isolation of ursane-type triterpenoids from Tragopogon porrifolius based on Feature-Based Molecular Networking - Hong-bing Sun; Hai-fei Zou; Bing Xia; Yu-cheng Gu; Wen-lin Wu; Yan Zhou (Phytochemistry Letters, 2023)

Hydroxylamine enhanced the degradation of diclofenac in Cu(II)/peracetic acid system: Formation and contributions of CH3C(O)O•, CH3C(O)OO•, Cu(III) and •OH - Jianying Wu; Jing Zou; Jinbin Lin; Sheng Li; Siying Chen; Xiaobin Liao; Jingxin Yang; Baoling Yuan; Jun Ma (Journal of Hazardous Materials, 2023)

Enhanced arsenic(III) sequestration via sulfidated zero-valent iron in aerobic conditions: Adsorption and oxidation coupling processes - Haiming Cai; Xiaodong Du; Ziting Lin; Xueqin Tao; Mengyao Zou; Jingyong Liu; Lijuan Zhang; Zhi Dang; Guining Lu (Journal of Hazardous Materials, 2023)

Uncovering the prevalence and drivers of antibiotic resistance genes in soils across different land-use types - Jie Wu; Shumin Guo; Haiyan Lin; Kejie Li; Zhutao Li; Jinyang Wang; William H. Gaze; Jianwen Zou (Journal of Environmental Management, 2023)

A Bayesian network-GIS probabilistic model for addressing human disturbance risk to ecological conservation redline areas - Jing Liu; Xiaojuan Xu; Changxin Zou; Naifeng Lin; Kun Zhang; Nan Shan; Hanwen Zhang; Renzhi Liu (Journal of Environmental Management, 2023)

Anaerobic fermentation of aerobic granular sludge: Insight into the effect of granule size and sludge structure on hydrolysis and acidification - Jinte Zou; Lei Cai; Jianrui Lin; Ruyi Wang; Jun Li; Mingsheng Jia (Journal of Environmental Management, 2023)

Crack instability in deep coal seam induced by the coupling of mining unloading and gas driving and transformation of failure mode - Ting Liu; Mingyang Li; Quanle Zou; Jianfeng Li; Minghua Lin; Baiquan Lin (International Journal of Rock Mechanics and Mining Sciences, 2023)

Oat bran prevents high-fat-diet induced muscular dysfunction, systemic inflammation and oxidative stress through reconstructing gut microbiome and circulating metabolome - Rui Dong; Kejie Peng; Lin Shi; Qianwen Niu; Hamad Rafique; Yuan Liu; Li Yuan; Liang Zou; Lu Li; Maria Cristina Messia; Xinzhong Hu (Food Research International, 2023)

Constructing zinc single-atom catalysts for the direct electron-transfer mechanism in peroxymonosulfate activation to degrade sulfamethoxazole efficiently - Yanan Xiao; Jiahui Hu; Xiao-yan Li; Yubin Zou; Yin Li; Lin Lin; Bing Li (Chemical Engineering Journal, 2023)

Catalytic fast co-pyrolysis of Douglas Fir and low-density polyethylene with nanocellulose-derived carbon catalyst for enhancing selectivity of hydrogen in syngas and mono-aromatic hydrocarbon in bio-oil products - Rongge Zou; Chenxi Wang; Moriko Qian; Ryan Lei; Yunfeng Zhao; Qingfa Zhang; Erguang Huo; Xiao Kong; Xiaona Lin; Lu Wang; Xuesong Zhang; Austin Gluth; et al. (Chemical Engineering Journal, 2023)

A pruned feed-forward neural network (pruned-FNN) approach to measure air pollution exposure - Xi Gong; Lin Liu; Yanhong Huang; Bin Zou; Yeran Sun; Li Luo; Yan Lin (Environmental Monitoring and Assessment, 2023)

Macroalgae culture–induced carbon sink in a large cultivation area of China - Yingying Wang; Weifeng Yang; Yihua Cai; Ziming Fang; Xiufeng Zhao; Qinghua Zhang; Hao Yuan; Na Lin; Chenyi Zou; Minfang Zheng (Environmental Science and Pollution Research, 2023)

Associations of metal mixtures with thyroid function and potential interactions with iodine status: results from a cross-sectional study in MEWHC - Xiaoting Ge; Junxiu He; Sencai Lin; Yu Bao; Yuan Zheng; Hong Cheng; Haiqing Cai; Xiuming Feng; Wenjun Yang; Sihan Hu; Lin Wang; Qijing Liao; et al. (Environmental Science and Pollution Research, 2023)

Three new compounds with their anti-glioma effects from the roots of Arnebia guttata Bunge - Yu-Mei Yan; Lin-Jun Zou; Min-Hui Li; Zhao-Cui Sun; Min Zhang; Xu-Dong Xu; Chun-Hong Zhang (Natural Product Research, 2023)

Effects of faba beans (Vicia faba L.) on growth performance, textural quality and physiological indices of tilapia (Oreochromis niloticus) - Qingqing Li; Yao Huang; Xingqian Zhang; Zhendong Qin; Cuiyun Zou; Xiaohong Tan; Xi Xie; Shaowen Liang; Li Lin (Aquaculture, 2023)

TERT transcription and translocation into mitochondria regulate benzo[a]pyrene/BPDE-induced senescence and mitochondrial damage in mouse spermatocytes - Haonan Cui; Wang Yang; Shijun He; Zili Chai; Lihong Wang; Guowei Zhang; Peng Zou; Lei Sun; Huan Yang; Qing Chen; Jinyi Liu; Jia Cao; et al. (Toxicology and Applied Pharmacology, 2023)

Metformin improves sheep sperm cryopreservation via vitalizing the AMPK pathway - Xing Zhang; Song-Mao Guo; Da-Wei Zhu; Yu Li; Fei Wen; Ming Xian; Zhang-Tao Hu; Qian-Long Zou; Li-Kun Zhang; Yu-Lin Chen; Jian-Hong Hu (Theriogenology, 2023)

The Toarcian Oceanic Anoxic Event in a shelf environment (Eastern Tethys): Implications for weathering and redox conditions - Ying Nie; Xiugen Fu; Jintong Liang; Hengye Wei; Zhengan Chen; Fei Lin; Shengqiang Zeng; Yunhao Wu; Yi Zou; Ahmed Mansour (Sedimentary Geology, 2023)

Evolution of sedimentary dynamic process/pattern in the Quanzhou Bay under impact of Typhoon Matmo (2014) - Shangshang Yang; Yunhai Li; Yunpeng Lin; Meng Liu; Xiaochun Zou; Liang Wang; Binxin Zheng; Xijie Yin; Jia He; Fangfang Shu (Regional Studies in Marine Science, 2023)

Real world emission characteristics of Chinese fleet and the current situation of underestimated ship emissions - Lei Yang; Qijun Zhang; Zongyan Lv; Jingbo Zhao; Chao Zou; Ning Wei; Zhenyu Jia; Yanjie Zhang; Fei Fu; Jianhua Lv; Lin Wu; Ting Wang; et al. (Journal of Cleaner Production, 2023)

Heavy vehicles’ non-exhaust exhibits competitive contribution to PM2.5 compared with exhaust in port and nearby areas - Tiange Fang; Ting Wang; Chao Zou; Quanyou Guo; Jianhua Lv; Yanjie Zhang; Lin Wu; Jianfei Peng; Hongjun Mao (Environmental Pollution, 2023)

A one- and three-dimensional coupled model and simulation investigation for the large-scale oil-heating type Mg-based hydrogen storage tank - Xi Lin; Cheng-long Yin; Li Ren; Yinghui Li; Zi Li; Qiuyu Zhang; Zhigang Hu; Jianxin Zou (Chemical Engineering Journal, 2023)

Periodate activation by atomically dispersed Mn on carbon nanotubes for the production of iodate radicals and rapid degradation of sulfadiazine - Jiahui Hu; Yubin Zou; Yin Li; Zehui Yu; Yutian Bao; Lin Lin; Bing Li; Xiao-yan Li (Chemical Engineering Journal, 2023)

Characteristics of digested sludge-derived biochar for promoting methane production during anaerobic digestion of waste activated sludge - Shengye Duan; Junguo He; Xiaodong Xin; Lin Li; Xiang Zou; Yijie Zhong; Jie Zhang; Xinxin Cui (Bioresource Technology, 2023)

Soil carbon-fixing bacterial communities respond to plant community change in coastal salt marsh wetlands - Qihang Liao; Chao Lu; Feng Yuan; Qinya Fan; Hongyu Chen; Lin Yang; Penghua Qiu; Ziyue Feng; Chenglong Wang; Xinqing Zou (Applied Soil Ecology, 2023)

A dual fragment triggered DNA ladder nanostructure based on logic gate and dispersion-to-localization catalytic hairpin assembly for efficient fluorescence assay of SARS-CoV-2 and H1N1 - Chen Zhou; Yujing Chuai; Chiliang Lin; Dongsheng Wang; Qiuju Wang; Haimin Zou (Analytica Chimica Acta, 2023)

Characterizing wind-induced reconfiguration of coaxial branched tree - Pengfei Lin; Gang Hu; K.T. Tse; Jie Song; Anthony Kwan Leung; Zhenliang Jiang; Lianghao Zou (Agricultural and Forest Meteorology, 2023)

Experimental and numerical study on 2-DOF wind-induced vibration and energy harvesting of triangular prism - Qunfeng Zou; Lin Ding; Tian Song; Jingyu Ran; Li Zhang (Ocean Engineering, 2023)

Mechanisms of autophagy and endoplasmic reticulum stress in the reversal of platinum resistance of epithelial ovarian cancer cells by naringin - Jun Zhu; Shixin Lin; Xia Zou; Xintong Chen; Yanlan Liu; Xiaorong Yang; Jun Gao; Hong Zhu (Molecular Biology Reports, 2023)

Migraine, chronic kidney disease and kidney function: observational and genetic analyses - Wenqiang Zhang; Li Zhang; Luo Yang; Chenghan Xiao; Xueyao Wu; Peijing Yan; Huijie Cui; Chao Yang; Jingwei Zhu; Xuan Wu; Mingshuang Tang; Yutong Wang; et al. (Human Genetics, 2023)
Epidemiological studies demonstrate an association between migraine and chronic kidney disease (CKD), while the genetic basis underlying the phenotypic association has not been investigated. We aimed to help avoid unnecessary interventions in individuals with migraine through the investigation of phenotypic and genetic relationships underlying migraine, CKD, and kidney function. We first evaluated phenotypic associations using observational data from UK Biobank ( N = 255,896). We then investigated genetic relationships leveraging genomic data in European ancestry for migraine ( N case / N control = 48,975/540,381), CKD ( N case / N control = 41,395/439,303), and two traits of kidney function (estimated glomerular filtration rate [eGFR, N = 567,460] and urinary albumin-to-creatinine ratio [UACR, N = 547,361]). Observational analyses suggested no significant association of migraine with the risk of CKD (HR = 1.13, 95% CI = 0.85–1.50). While we did not find any global genetic correlation in general, we identified four specific genomic regions showing significant for migraine with eGFR. Cross-trait meta-analysis identified one candidate causal variant (rs1047891) underlying migraine, CKD, and kidney function. Transcriptome-wide association study detected 28 shared expression–trait associations between migraine and kidney function. Mendelian randomization analysis suggested no causal effect of migraine on CKD (OR = 1.03, 95% CI = 0.98–1.09; P = 0.28). Despite a putative causal effect of migraine on an increased level of UACR (log-scale-beta = 0.02, 95% CI = 0.01–0.04; P = 1.92 × 10 −3 ), it attenuated to null when accounting for both correlated and uncorrelated pleiotropy. Our work does not find evidence supporting a causal association between migraine and CKD. However, our study highlights significant biological pleiotropy between migraine and kidney function. The value of a migraine prophylactic treatment for reducing future CKD in people with migraine is likely limited.

Taxonomic and Morpho-Functional Photosynthetic Patterns of 18 Intertidal Macroalgal Species in the Guangdong–Hong Kong–Macao Greater Bay Area, China - Quan He; Linqing Liu; Yujie Qin; Qiang Lin; Guangyan Ni; Binbin Chen; Zengling Ma; Dinghui Zou; Gang Li (Journal of Marine Science and Engineering, 2023)
Macroalgae provide food for microbial, meio- and macro-faunal communities in coastal ecosystems, thus mediating nutrient dynamics and functions in these ecosystems. Because of this vital role, it is important to clarify physiological information about macroalgae as it reflects their growth potential in the field. In this study, we examined the biomass, pigment content, and photosynthetic O2 evolution rate versus irradiance curves of 18 macroalgal species from the intertidal zone of the Guangdong–Hong Kong–Macao Greater Bay Area, China, and investigated their photosynthetic patterns in relation to phyla characteristics, morphology, and growth locations. The results showed that green algae had the highest maximum photosynthetic O2 evolution rate (Pmax), light utilization efficiency (α), and dark respiration (Rd) among the three macroalgal phyla; the sheet-like macroalgal species had the highest Pmax, α, and Rd among the four morphological categories. The macroalgal species in the upper intertidal zone showed higher Pmax and α and lower saturation irradiance (EK) and compensation irradiance (EC) than those species in the lower intertidal location. The PCA results showed that the biomass of sheet-like macroalgal species was positively correlated with factor PC1 (50.34%), and that of finely branched species was negatively correlated with factor PC2 (25.17%). In addition, our results indicate that the light absorption and utilization capabilities of macroalgae could determine whether they could dominate the intertidal zone and that their photosynthetic characteristics could be used as a potential indicator of their biomass distribution in the Greater Bay Area.

Ambient air pollution and incidence, progression to multimorbidity and death of hypertension, diabetes, and chronic kidney disease: A national prospective cohort - Gan Wu; Miao Cai; Chongjian Wang; Hongtao Zou; Xiaojie Wang; Junjie Hua; Hualiang Lin (Science of The Total Environment, 2023)

Using quantum chemistry theory to elucidate the mechanism for treating sulfonamide antibiotic wastewater by progressive freezing - Zhang Yan; Liu Tong-shuai; Wang Xiao-zhuang; Liu Yu-can; Zhao Chen; Lin Hao; Zou Yi-hong (Journal of Water Process Engineering, 2023)

SERS determination of hydroxy-α-sanshool in spicy hotpot seasoning: The strategy to restrain the interference of capsaicin and its mechanism - Di Zhang; Yushan Fan; Xiaoxia Sun; Xiaoou Wei; Zitao Lin; Xinai Zhang; Jiyong Shi; Maurizio Battino; Yunyun Gong; Bolin Shi; Xiaobo Zou (Food Chemistry, 2023)

Experimental study, finite element simulation and theoretical analysis on failure mechanism of steel–concrete-steel (SCS) composite deep beams with UHPC - Youzhu Lin; Jiachuan Yan; Zefang Wang; Chaoying Zou (Engineering Structures, 2023)

A smartphone-assisted “all-in-one” paper chip for one-pot noninvasive detection of salivary glucose level - Qian Lin; Jiaqi Huang; Yiling Zhang; Miaomiao Chen; Yuzhi Xu; Xiaoyong Zou; Si-Yang Liu; Zong Dai (Chemical Engineering Journal, 2023)

High-strength, high-toughness regenerated cellulose/graphene oxide nanofluidic membrane with highly oriented and charged nanochannels for wearable sweat-monitoring systems - Jie Zou; Zewan Lin; Zhanhong Yuan; Binglin Zhou; Xiaotong Fu; Dongdong Ye (Chemical Engineering Journal, 2023)

Elucidating the chemical structures of petroleum resin using solid-state 13C NMR - Tian Liang; Xiao-Hui Lin; Yan-Rong Zou; Zhao-Wen Zhan; Ping'’an Peng (Chemical Geology, 2023)

Alternative splicing affects synapses in the hippocampus of offspring after maternal fructose exposure during gestation and lactation - Yuchen Zou; Qing Guo; Yidan Chang; Yongyong Zhong; Lin Cheng; Wei Wei (Chemico-Biological Interactions, 2023)

Dynamic soil arching in piled embankment under train load of high-speed railways - Tingting Niu; Yule Yang; Qianli Ma; Jiuqun Zou; Bin Lin (Earthquake Engineering and Engineering Vibration, 2023)

Effects of high NaHCO3 alkalinity on growth, tissue structure, digestive enzyme activity, and gut microflora of grass carp juvenile - Jian Wen; Song-lin Chen; Wen-ya Xu; Guo-dong Zheng; Shu-ming Zou (Environmental Science and Pollution Research, 2023)

Bi-Temporal change detection of high-resolution images by referencing time series medium-resolution images - Ming Hao; Chaoyun Yang; Huijing Lin; Lanlan Zou; Shu Liu; Hua Zhang (International Journal of Remote Sensing, 2023)

Parental food neophobia, feeding practices, and preschooler’s food neophobia: A cross-sectional study in China - Cuiting Yong; Xiaoni Kuang; Yan Liu; Caihong Xiang; Yue Xi; Jiaqi Huo; Jiajing Liang; Hanshaung Zou; Qian Lin (Appetite, 2023)

Hydrogen sulfide antagonizes formaldehyde-induced ferroptosis via preventing ferritinophagy by upregulation of GDF11 in HT22 cells - Yu-Hui Tang; Lei Wu; Hong-Lin Huang; Pan-Pan Zhang; Wei Zou; Xiao-Qing Tang; Yi-Yun Tang (Toxicology, 2023)

Development and optimization of LED systems for surface fungal decontamination of fresh produce - Xinpeng Yu; Weihong Deng; Ziqian Zhang; Yuan Zou; Tao Wei; Junfang Lin; Liqiong Guo; Hyun-Gyun Yuk; Zhiwei Ye; Qianwang Zheng (Postharvest Biology and Technology, 2023)

Synergistic structure of LiFeO2 and Fe2O3 layers with electrostatic shielding effect to suppress surface lattice oxygen release of Ni-rich cathode - Youqi Chu; Yongbiao Mu; Lingfeng Zou; Jie Cheng; Shibo Xi; Qichang Pan; Meisheng Han; Hongqiang Wang; Qingyu Li; Fenghua Zheng; Qing Zhang; Lin Zeng (Chemical Engineering Journal, 2023)

Countering beta-cypermethrin: partitioning roles of the insect gut and its bacteria - Li Bai; Xiao-Lin Cai; Man-Yu Li; Fu-Xiao Wang; Chuan-Shan Zou; Jun-Sheng Zhang; Ming-Yu Xie; Feng-Hui Qi; Tian-Zhong Jing (Journal of Pest Science, 2023)

Predicting Drug Synergy and Discovering New Drug Combinations Based on a Graph Autoencoder and Convolutional Neural Network - Huijun Li; Lin Zou; Jamal A. H. Kowah; Dongqiong He; Lisheng Wang; Mingqing Yuan; Xu Liu (Interdisciplinary Sciences: Computational Life Sciences, 2023)

Different cold tolerances among three strains of large yellow croaker: related to antioxidant defense and energy metabolism - Lin Zeng; Yong-Hong Wang; Chun-Xiang Ai; Hui Zhang; Yu-Cong Huang; Wei-Guang Zou (Fish Physiology and Biochemistry, 2023)

Diffusion mechanism of deep shale gas and its carbon isotope fractionation: a combined simulated and mathematical analysis - Yu Zou; Guojian Wang; Cheng Tao; Rui Zhou; Shangqing Zhang; Dongna Liu; Xiaohui Lin; Xuying Zheng (Geosciences Journal, 2023)

Analysis of short-term and local scale variations in fish community structure in Dachen Island waters - Xiaopeng Cheng; Zhenhua Wang; Shouyu Zhang; Xu Zhao; Jun Lin; Hong Huang; Yihui Chen; Qindong Zou (Frontiers in Marine Science, 2023)
Understanding the changes in community structure of fishery resources in island reef waters is crucial for effective fishery resource management, as these waters constitute a critical link in maintaining the sustainable development of offshore fishery resources. The study analyzed the structure of the fish community in the waters surrounding Dachen Island by using data collected during four voyage surveys conducted between September 2020 and April 2021. The study utilized co-occurrence network analysis, multiple regression trees, and functional diversity analysis to investigate the short-term and local scale changes in fish community structure. The results showed that the fish community in the waters adjacent to Dachen Island can be categorized into two groups: annual and stage-use species. The stage-use species include Scoliodon laticaudus , Trichiurus lepturus , Tetraodontidae , and others, which are used during the summer and autumn stages of bait migration. Additionally, Dasyatidae and others, which used during the winter and spring stages of reproductive migration. Furthermore, the study found that the habitats dominated by nearshore rocky habitats and distant deep habitats formed the local scale variation in community structure in island waters. The integrated analysis of species α-diversity and functional diversity provided a basis for understanding the mechanisms of biodiversity action. Our study aims to provide a theoretical framework for the development of fishery resource management strategies based on the life cycle of fish, and to serve as a reference for the prioritization of key protection areas for fishery resources in island and reef environments. Overall, the study’s findings can promote the understanding of community structure dynamics in island waters. Additionally, these findings can offer valuable insights into the restoration of habitats and the implementation of marine ranching activities in Dachen Island. Moreover, the outcomes can serve as a theoretical foundation for the development of appropriate management and conservation strategies for fisheries resources.

Influencing pathways and toxicity changes of pre-ozonation on carcinogenic NDEA formation from greenhouse gas adsorbent DEAPA in subsequent disinfection processes - Tianze Liu; Xiaobin Liao; Xinna Lin; Jing Yu; Huan Qi; Zhibin Jiang; Jing Zou; Qingsong Li (Science of The Total Environment, 2023)

Exposure to acrylamide induces zygotic genome activation defects of mouse embryos - Si-Le Wu; Jia-Qian Ju; Yi-Ming Ji; Hao-Lin Zhang; Yuan-Jing Zou; Shao-Chen Sun (Food and Chemical Toxicology, 2023)

Ag quantum dots decorated ultrathin g-C3N4 nanosheets for boosting degradation of pharmaceutical contaminants: Insight from interfacial electric field induced by local surface plasma resonance - Zhenzhou Wang; Danqi Wang; Fang Deng; Xinggang Liu; Xibao Li; Xubiao Luo; Yanzhi Peng; Jian Zhang; Jianping Zou; Lin Ding; Longshuai Zhang (Chemical Engineering Journal, 2023)

Evaluating the performance of a novel ventilated embankment structure in warm permafrost regions by numerical simulation - Zhanyuan Zhu; Zonghang He; Fei Luo; Bin Luo; Chenxuan Tang; Zuyin Zou; Zihong Guo; Weimin Xiao; Xiangang Jiang; Lin Li (Cold Regions Science and Technology, 2023)

Hygrothermal performance optimization of lightweight steel-framed wall assemblies in hot–humid regions using orthogonal experimental design and a validated simulation model - Qiaosheng Zhan; Yiqiang Xiao; Lei Zhang; Zhenghao Lin; Yukai Zou; Wei Liao (Building and Environment, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

An Empirical Study on Water-Induced Shear Weakening Behaviors of Rough-Walled Sandstone Joints - Guohua Zhang; Bowen Zhang; Junpeng Zou; Feng Xiong; Zhiping Lin; Zhanrong Zhang (Rock Mechanics and Rock Engineering, 2023)

Cross-sectional rainfall observation on the central-western Tibetan Plateau in the warm season: System design and preliminary results - Kun Yang; Yingying Chen; Lazhu; Changhui Zhan; Xiaoyan Ling; Xu Zhou; Yaozhi Jiang; Xiangnan Yao; Hui Lu; Xiaogang Ma; Lin Ouyang; Weihao Pan; et al. (Science China Earth Sciences, 2023)

Arbuscular mycorrhizal fungi increase the interspecific competition between two forage plant species and stabilize the soil microbial network during a drought event: Evidence from the field - Xionghui Liao; Jie Zhao; Lin Xu; Li Tang; Jiangnan Li; Wei Zhang; Jun Xiao; Dan Xiao; Peilei Hu; Yunpeng Nie; Dongsheng Zou; Kelin Wang (Applied Soil Ecology, 2023)

Evaluation method of rowing performance and its optimization for UAV-based shot seeding device on rice sowing - Wei Liu; Zhiyan Zhou; Xuelang Xu; Qingyu Gu; Shuaishuai Zou; Weizhuo He; Xiwen Luo; Junhao Huang; Jianqin Lin; Rui Jiang (Computers and Electronics in Agriculture, 2023)

Potential determinants affecting the growth of China’s ocean economy: An input-output structural decomposition analysis - Li Zheng; Hongyang Zou; Xiaofeng Duan; Zhongguo Lin; Huibin Du (Marine Policy, 2023)

Understanding the 0 + + and 2 + + charmonium(-like) states near 3.9 GeV - Teng Ji; Xiang-Kun Dong; Miguel Albaladejo; Meng-Lin Du; Feng-Kun Guo; Juan Nieves; Bing-Song Zou (Science Bulletin, 2023)

Full-scale experimental study on dynamic behaviors of a three-cable network with a pretensioned cross-tie - Lin Chen; Lei Qin; Fangdian Di; Limin Sun; Yiqing Zou; Zhiquan Huang (Engineering Structures, 2023)

Click-crosslinked in-situ hydrogel improves the therapeutic effect in wound infections through antibacterial, antioxidant and anti-inflammatory activities - Xiong-Xin Lei; Chen-Yu Zou; Juan-Juan Hu; Yan-Lin Jiang; Xiu-Zhen Zhang; Long-Mei Zhao; Tao He; Qing-Yi Zhang; Ya-Xing Li; Jesse Li-Ling; Hui-Qi Xie (Chemical Engineering Journal, 2023)

Study on the mechanism of acid modified H-Beta zeolite acidic sites on the catalytic pyrolysis of Kraft lignin - Qiuxia Zou; Hongshen He; Jie Xie; Shibo Han; Weijie Lin; Ajoy Kanti Mondal; Fang Huang (Chemical Engineering Journal, 2023)

A novel 4-O-endosulfatase with high potential for the structure-function studies of chondroitin sulfate/dermatan sulfate - Lin Wei; Yingying Xu; Min Du; Ying Fan; Ruyi Zou; Xiangyu Xu; Qingdong Zhang; Yu-Zhong Zhang; Wenshuang Wang; Fuchuan Li (Carbohydrate Polymers, 2023)

Valorization of lignin through reductive catalytic fractionation of fermented corn stover residues - Wen-Zheng Yin; Ling-Ping Xiao; Shuang-Lin Zou; Wen-Xin Li; Hongliang Wang; Run-Cang Sun (Bioresource Technology, 2023)

The diversity of mycorrhiza‐associated fungi and trees shapes subtropical mountain forest ecosystem functioning - Ya‐Huang Luo; Liang‐Liang Ma; Sebastian Seibold; Marc W. Cadotte; Kevin S. Burgess; Shao‐Lin Tan; Lin‐Jiang Ye; Wei Zheng; Jia‐Yun Zou; Zhi‐Fa Chen; De‐Tuan Liu; Guang‐Fu Zhu; et al. (Journal of Biogeography, 2023)
Aim Mycorrhiza play key roles for ecosystem structure and functioning in forests. However, how different mycorrhizal types influence mountain forest biodiversity–ecosystem functioning (BEF) relationships are largely unknown. We evaluate how the diversity of distinct mycorrhiza‐associated fungi and trees shapes forest carbon storage along elevational gradients. Location Gaoligong Mountains within Hengduan Mountains, Southwest China. Taxon Seed plants and mycorrhizal fungi. Methods We used the data from 31 subtropical forest plots along elevational gradients on two aspects (east and west) of the mountain. We quantified species richness of trees and symbiotic fungi and assigned both to their mycorrhizal type (arbuscular mycorrhiza [AM], ectomycorrhiza [EcM] and ericoid mycorrhiza [ErM]). We then examined the diversity effects of mycorrhiza‐associated fungi and trees on above‐ground carbon stored in trees and organic carbon stored in soils. Results Species richness was highest for AM trees (79.5%), followed by ErM trees (13.4%) and then EcM trees (7.1%). Species richness of AM‐associated trees and fungi decreased with increasing elevation, while ErM‐associated trees and fungi showed an opposite trend. EcM‐associated diversity followed a hump‐shaped relationship with elevation. Positive relationships between diversity and above‐ground carbon were detected in all three mycorrhizal associations, but despite low species number, canopy‐dominating EcM trees comprised 64.4% of the amount of above‐ground carbon. Furthermore, community‐weighted means of height exhibited positive correlations with forest above‐ground carbon, indicating that positive selection effects occur. Soil organic carbon was positively related to EcM‐associated fungi diversity, above‐ground carbon mass and soil nitrogen availability, with the latter having strongest direct effects. Main Conclusions The distributions of forest biodiversity and carbon storage can be modulated by distinct mycorrhizal fungi and trees. Moreover, future global changes (e.g. climate warming, intensifying nitrogen deposition) could alter the mycorrhizal‐mediated BEF relationships in mountain forests.

Isopimaric acid, an ion channel regulator, regulates calcium and oxidative phosphorylation pathways to inhibit breast cancer proliferation and metastasis - Jiacheng Li; Xiaozhen Liu; Lin Chen; Xinping Zhu; Zhihong Yu; Liyao Dong; Xinyun Zhao; Hongling Zou; Qin Wei; Yongcai Feng; Yongqiang Zhu; Kequn Chai; et al. (Toxicology and Applied Pharmacology, 2023)

Ecological engineering induced carbon sinks shifting from decreasing to increasing during 1981–2019 in China - Xiaojuan Xu; Jing Liu; Fusheng Jiao; Kun Zhang; Xin Ye; Haibo Gong; Naifeng Lin; Changxin Zou (Science of The Total Environment, 2023)

Ambient air pollution associated with incidence and progression trajectory of cardiometabolic diseases: A multi-state analysis of a prospective cohort - Hongtao Zou; Shiyu Zhang; Miao Cai; Zhengmin (Min) Qian; Zilong Zhang; Lan Chen; Xiaojie Wang; Lauren D. Arnold; Steven W. Howard; Haitao Li; Hualiang Lin (Science of The Total Environment, 2023)

Theoretical models and reliability assessment of steel-UHPC-steel composite beams in offshore structures - Youzhu Lin; Jiachuan Yan; Zefang Wang; Chaoying Zou (Ocean Engineering, 2023)

Chymosin pretreatment accelerated papain catalysed hydrolysis for decreasing casein antigenicity by exposing the cleavage site at tyrosine residues - Jianhua Zeng; Junzhe Zou; Jinlong Zhao; Kai Lin; Lanwei Zhang; Huaxi Yi; Pimin Gong (Food Chemistry, 2023)

Rapid detection of Staphylococcus aureus in food safety using an RPA-CRISPR-Cas12a assay - Liyun Lin; Guangcai Zha; Huagui Wei; Yuzhong Zheng; Peikui Yang; Yaqun Liu; Mouquan Liu; Zhonghe Wang; Xianghui Zou; Hui Zhu; Qiulan Luo; JinQuan Li; et al. (Food Control, 2023)

Enhancement of water barrier and antimicrobial properties of chitosan/gelatin films by hydrophobic deep eutectic solvent - Haitao Wen; Daobang Tang; Yaosheng Lin; Jinhao Zou; Zhongyi Liu; Pengfei Zhou; Xuping Wang (Carbohydrate Polymers, 2023)

Water and heat coupling processes and its simulation in frozen soils: Current status and future research directions - Guojie Hu; Lin Zhao; Ren Li; Hotaek Park; Xiaodong Wu; Youqi Su; Georg Guggenberger; Tonghua Wu; Defu Zou; Xiaofan Zhu; Wenxin Zhang; Yifan Wu; et al. (CATENA, 2023)

Purinergic signaling: a potential therapeutic target for depression and chronic pain - Yuting Zou; Runan Yang; Lin Li; Xiumei Xu; Shangdong Liang (Purinergic Signalling, 2023)

Transcriptome profiling reveals the roles of pigment formation mechanisms in yellow Paeonia delavayi flowers - Hongzhu Zou; Lin Zhou; Lulu Han; JiHang Lv; YingHua Jia; Yan Wang (Molecular Genetics and Genomics, 2023)
The yellow colour of ornamental varieties of tree peony originated from Paeonia delavayi . However, but P. delavayi and Paeonia suffruticosa belong to different subgroups, so hybridization is difficult and results in a long breeding cycle. However, no comprehensive transcriptomic profiling has focused on the colour formation mechanisms of yellow tree peony petals. Analysing the colour formation mechanism of yellow petals in P. delavayi is very important for directional molecular breeding. In this study, the transcriptional map of yellow pigment development in petals was used to analyse the mechanism of petal colour formation. We analysed the genes related to the metabolism of flavonoids and carotenoids and the transcription factors (TFs) involved in P. delavayi var. lutea (pure yellow individual) yellow pigment development using transcriptome sequence profiling. Transcriptome sequence profiles revealed three and four differentially expressed transcripts (DETs) involved in flavonoid biosynthesis and carotenoid biosynthesis, respectively. An analysis of DETs in the flavonoid pathway showed that chalcone synthase ( CHS ) and chalcone 2´-glucosyltransferases (THC 2’GT ) act in synergy to synthesize isosalipurposide (ISP). CHS and flavonol synthase ( FLS ) synergistically synthesize quercetin and kaempferol. DEG analysis of the carotenoid pathway revealed that phytoene synthase ( PSY ), carotenoid isomerase ( CRTISO ) and β-carotene hydroxylases ( CHYB ) play a key role in regulating lutein formation, and carotenoid cleavage dioxygenase ( CCD ) plays an important role in the degradation of carotenoids. These two pathways may be regulated by TF families such as bHLH , ARF , and MYB . The results of the transient overexpression of genes showed that CHS and CHI are regulated by PdMYB2 . In this study, the molecular mechanism of ISP synthesis was analysed in depth, and the complete metabolic pathway of carotenoids in Paeonia L. was reported for the first time. By studying the formation mechanism of yellow pigment in P. delavayi petals, a breeding strategy for improving flavonol and carotenoid contents and reducing anthocyanin synthesis by genetic engineering was suggested.

Enhanced degradation of emerging contaminants by percarbonate/Fe(II)-ZVI process: case study with nizatidine - Mingxin Huo; Deqiang Zou; Yingzi Lin; Yi Lou; Gen Liu; Siwen Li; Lei Chen; BaoLing Yuan; Qingyu Zhang; Ao Hou (Environmental Science and Pollution Research, 2023)

Polysaccharide extracted from pomelo fruitlets attenuate hepatic lipid accumulation in hybrid groupers (Epinephelus lanceolatus♂ × Epinephelus fuscoguttatus♀) - Cuiyun Zou; Yuke Fang; Nuoyi Lin; Gengsheng Xiao; Li Lin; Huifan Liu (Frontiers in Marine Science, 2023)
Introduction Pomelo is one of the most consumed fruits due to its distinct flavor and sour taste, while large quantities of pomelo fruitlets discard during cultivation and most of them are disposed of as wastes. Such an issue has led to some research on how to make a high value-added reutilization of these fruitlets. Therefore, it was aimed to determine the structural characteristics of the polysaccharide of pomelo fruitlets and evaluate its attenuating effect on the hepatic lipid accumulation in hybrid groupers ( Epinephelus lanceolatus♂ × Epinephelus fuscoguttatus♀ ). Methods and results In this research, YZ-0.5A is a 15,332 Da NaCl-soluble polysaccharide extracted from pomelo fruitlet which was characterized to mainly contain galactose and galacturonic acid and its putative structure was proven to be →2,4)- α-L-Rhap-(1→4)-α-D-GalAp-(1→4)-α-D-GalAp-(1→ with 3 branches. In vivo study, five isolipidic diets (containing 15% lipid) were fed to the groupers with an initial weight of 13.46 ± 0.08 g for 8 weeks, of which the dietary level of YZ-0.5A was 0 mg/kg (control), 150 mg/kg, 300 mg/kg, 600 mg/kg and 1200 mg/kg respectively. We found that the treatment of YZ-0.5A, especially 600 mg/kg, exerted an improved effect on the excessive lipid accumulation in grouper fed with a high-fat diet. In vitro , three graded concentrations of YZ-0.5A (75, 150 or 300 μg/ml) were added to the grouper primary hepatocytes respectively after incubation with 20% lipid emulsion (2 ml/L). The signs of recovery on morphological features observed under examined by histological evaluation supported the lipid lowering effect of YZ0.5-A. Further investigation showed that YZ0.5-A mitigated lipid emulsion-induced irregular lipid deposition by regulating various lipometabolism-related indicators, thereby alleviating oxidative stress and apoptosis. Discussion Overall results exhibited the therapeutic potential of YZ0.5-A and elucidated its underlying mechanism in the fish with excessive lipid deposition, which first suggested the feasibility of reprocessing discarded pomelo fruitlet as medicine in aquaculture.

Evaluating traffic emission control policies based on large-scale and real-time data: A case study in central China - Chao Zou; Lin Wu; Yanan Wang; Shida Sun; Ning Wei; Bin Sun; Jingwei Ni; Jing He; Qijun Zhang; Jianfei Peng; Hongjun Mao (Science of The Total Environment, 2023)

Potential risk of eutrophication in the deepest lake of Southwest China: Insights from phosphorus enrichment in bottom water - You-ai Duan; Xin-sheng Chen; Ying Huang; Yan Zhang; Ping Wang; Xue-xin Duan; Xian-yan Qin; Ye-ai Zou; Zheng-miao Deng; Qi-lin Zhao (Journal of Contaminant Hydrology, 2023)

Origin of clay in granite intrusive contact zone and its influence on tunnel deformation and instability - Guo-Hua Zhang; Bo-Wen Zhang; Fei Tan; Zhong-Hou Liu; Jun-Peng Zou; Zhong-Zhi Xie; Jin-Quan Wu; Zhi-Ping Lin; Zhan-Rong Zhang (Engineering Geology, 2023)

Typhoon-induced destruction and reconstruction of the coastal current system on the inner shelf of East China Sea - Wenqi Chi; Fangfang Shu; Yuting Lin; Yunhai Li; Fusheng Luo; Jia He; Zhijie Chen; Xiaochun Zou; Binxin Zheng (Continental Shelf Research, 2023)

Moisture-Induced reversible structure conversion of Zero-Dimensional organic cuprous bromide hybrids for multiple photoluminescent anti-Counterfeiting, information encryption and rewritable luminescent paper - Ye Tian; Hui Peng; Qilin Wei; Yanxi Chen; Jingjing Xia; Wenchao Lin; Chengyu Peng; Xuefei He; Bingsuo Zou (Chemical Engineering Journal, 2023)

NIR-responsive hollow germanium nanospheres mediate photothermal/photodynamic therapy and restrain immunosuppression to cooperatively eradicate primary and metastatic tumors - Qilin Li; Huiling Fan; Yunruo Xu; Miaodeng Liu; Jia Liu; Luming Xu; Meizhen Zou; Qian Cheng; Yan Zhang; Tao Liang; Lin Shi; Xianluo Hu; et al. (Chemical Engineering Journal, 2023)

Self-repairing thermal energy storage gels demonstrating superior thermophysical properties and wearability towards personal thermal management in static and dynamic modes - Yingying Luo; Hongjiao Wu; Junpeng Qiao; Jiaming Zhang; Kai Liu; Liqing Zou; Ying Chen; Pengcheng Lin (Chemical Engineering Journal, 2023)

Aligned regenerated cellulose-based nanofluidic fibers with ultrahigh ionic conductivity and underwater stability for osmotic energy harvesting - Binglin Zhou; Jie Zou; Zewan Lin; Zhanhong Yuan; Xingzhen Qin; Pan Chen; Dongdong Ye (Chemical Engineering Journal, 2023)

Identifying the activity origin of silver catalysts induced by interfacial electron localization for regioselective C O bond hydrogenation - Jinglin Zou; Xinping Duan; Xu Liu; Lele Huang; Xiaoying Liu; Jiachang Zuo; Weizhou Jiao; Haiqiang Lin; Linmin Ye; Youzhu Yuan (Chemical Engineering Journal, 2023)

Integration of adsorption and simultaneous heterogeneous catalytic oxidation by defective CoFe2O4 activated peroxymonosulfate for efficient As(III) removal: Performance and new insight into the mechanism - Ziqun Lin; Fang Deng; Wei Ren; Zhongbing Wang; Xiao Xiao; Penghui Shao; Jianping Zou; Xubiao Luo (Chemical Engineering Journal, 2023)

Single-atom Mn anchored on N-doped graphene oxide for efficient adsorption-photocatalytic degradation of sulfanilamide in water: Electronic interaction and mineralization pathway - Honghong Lyu; Pin Li; Jingchun Tang; Weixin Zou; Pengfei Wang; Bin Gao; Lin Dong (Chemical Engineering Journal, 2023)

Catalytic activity enhancement by P and S co-doping of a single-atom Fe catalyst for peroxymonosulfate-based oxidation - Yin Li; Jiahui Hu; Yubin Zou; Lin Lin; Hebin Liang; Huaxin Lei; Bing Li; Xiao-yan Li (Chemical Engineering Journal, 2023)

Research on type I kerogen molecular simulation and docking between kerogen and saturated hydrocarbon molecule during oil generation - Tian Liang; Zhao-Wen Zhan; Yan-Rong Zou; Xiao-Hui Lin; Yun Shan; Ping'’an Peng (Chemical Geology, 2023)

Cholesterol homeostasis regulated by ABCA1 is critical for retinal ganglion cell survival - Jialiang Yang; Yuhong Chen; Tongdan Zou; Bai Xue; Fang Yang; Xiangzhou Wang; Yibo Huo; Boyun Yan; Yuxia Xu; Shiyu He; Yi Yin; Jing Wang; et al. (Science China Life Sciences, 2023)

Differential responses of soil nirS- and nirK-type denitrifying microbial communities to long-term application of biogas slurry in a paddy soil - Zhaoming Chen; Jinchuan Ma; Yinxiu Liu; Jun Zhao; Junwei Ma; Qiaogang Yu; Ping Zou; Hui Lin; Qiang Wang (Applied Soil Ecology, 2023)

Programmable CRISPR-Cas12a and self-recruiting crRNA assisted dual biosensing platform for simultaneous detection of lung cancer biomarkers hOGG1 and FEN1 - Xia Cheng; Xinyi Xia; Dandan Ren; Qiutong Chen; Guanhong Xu; Fangdi Wei; Jing Yang; Lin Wang; Qin Hu; Jianjun Zou; Yao Cen (Analytica Chimica Acta, 2023)

Validation and accuracy analysis of wind products from scatterometer onboard the HY-2B satellite - Sheng Yang; Bo Mu; Haoqiang Shi; Chaofei Ma; Wu Zhou; Juhong Zou; Mingsen Lin (Acta Oceanologica Sinica, 2023)

Two new cycloartane triterpenoid glycosides from the rhizomes of Actaea vaginata - Shunqin Zeng; Xiangyuan Li; Zixuan Zhao; Yan Lin; Yindi Zhu; Guoxu Ma; Xiaohong Zhao; Xudong Xu; Meichun Wu; Haifeng Wu; Qiongyu Zou; Yongtao Li (Natural Product Research, 2023)

Ambient air pollution, bone mineral density and osteoporosis: Results from a national population-based cohort study - Yin Yang; Rui Li; Miao Cai; Xiaojie Wang; Haopeng Li; Yinglin Wu; Lan Chen; Hongtao Zou; Zilong Zhang; Haitao Li; Hualiang Lin (Chemosphere, 2023)

Mitigation of protein fouling by magnesium ions and the related mechanisms in ultrafiltration process - Hui Zou; Jiahui Huang; Meijia Zhang; Hongjun Lin; Jiaheng Teng; Zhengyi Huang (Chemosphere, 2023)

Comparative transcriptome analysis of early sexual differentiation in the male and female gonads of common carp (Cyprinus carpio) - Mei Wang; Lin Chen; Zhixiong Zhou; Junzhu Xiao; Baohua Chen; Peihong Huang; Chengyu Li; Yaguo Xue; Ruoting Liu; Yulin Bai; Mengzhen Yan; Shuimu Hu; et al. (Aquaculture, 2023)

Transcriptomics and metabolomics together reveal the underlying mechanism of heroin hepatotoxicity - Yingbiao Yue; Lei Zou; Jie Tao; Lin Yin; Zhenrong Xie; Yu Xia; Zunyue Zhang; Kunhua Wang; Mei Zhu (Toxicology, 2023)

Damage stratigraphy as a controlling mechanism of earthquakes distribution and fault patterns - Zonghu Liao; Lin Zhang; Huayao Zou; Fang Hao; Ze'ev Reches (Tectonophysics, 2023)

Can biochar application improve the net economic benefits of tea plantations? - Haiyan Lin; Shumin Guo; Zhaoqiang Han; Shuwei Liu; Jinyang Wang; Jianwen Zou (Science of The Total Environment, 2023)

A constant parameter time domain model for dynamic modelling of multi-body system with strong hydrodynamic interactions - Meiyan Zou; Mingsheng Chen; Ling Zhu; Lin Li; Wenhua Zhao (Ocean Engineering, 2023)

Extract of Ginkgo biloba leaves attenuates neurotoxic damages in rats and SH-SY5Y cells exposed to a high level of fluoride - Jie Xiang; Yan-Lin Ma; Jian Zou; Xiao-Xiao Zeng; Xiao Xiao; Yan-Long Yu; Yang-Ting Dong; Long-Yan Ran; Xiao-Lan Qi; Wei Hong; Yan-Hui Gao; Zhi-Zhong Guan (Journal of Trace Elements in Medicine and Biology, 2023)

Diverse metavolcanic sequences in the Cambrian accretionary complex at the Pamir Syntax: Implications for tectonic evolution from Proto-Tethys to Paleo-Tethys - Xiao-Qiang Liu; Chuan-Lin Zhang; Haibo Zou; Xian-Tao Ye (Journal of Asian Earth Sciences, 2023)

Two venom serpins from the parasitoid wasp Microplitis mediator inhibit the host prophenoloxidase activation and antimicrobial peptide synthesis - Lizhen Zhou; Ruijuan Wang; Zhe Lin; Suke Shi; Caihua Chen; Haobo Jiang; Zhen Zou; Zhiqiang Lu (Insect Biochemistry and Molecular Biology, 2023)

Soil moisture dynamics near a gully head in relation to the trigger of collapse in granite red soil slope in southern China - Ziqiang Zou; Yu Tao; Yuhao Gao; Zixuan Liu; Wenkai Li; Zhengchao Tian; Lirong Lin; Yangbo He; Jiazhou Chen (Geomorphology, 2023)

Insight into the molecular-level details of αs1 casein interactions with IgG: Combining with LC-MS/MS and molecular modelling techniques - Jianhua Zeng; Kai Lin; Xiaoqian Zhang; Junzhe Zou; Lanwei Zhang; Pimin Gong; Jinlong Zhao; Chunhua Han; Yuhai Liu; Huaxi Yi; Tongjie Liu (Food Chemistry, 2023)

Constructing efficient CuO -CeO2 catalyst for NO reduction by CO: New insights into the structure–activity relationship - Wei Tan; Yandi Cai; Shaohua Xie; Juntian Xu; Kaili Ma; Kailong Ye; Lu Ma; Steven N. Ehrlich; Weixin Zou; Fei Gao; Lin Dong; Fudong Liu (Chemical Engineering Journal, 2023)

Triggered amplification of gene theranostics with high accuracy and efficacy using metallo-nanoassemblies - Jialing Hu; Zhiqiao Zou; Fengye Mo; Xue Lin; Yun Zhao; Tianhui Shi; Fuan Wang; Xiaoqing Liu (Chemical Engineering Journal, 2023)

A High-efficiency blue-LED-excitable NIR-II-emitting MgO:Cr3+,Ni2+ phosphor for future broadband light source toward multifunctional NIR spectroscopy applications - Bo-Mei Liu; Xiao-Xuan Guo; Lu-Yu Cao; Lin Huang; Rui Zou; Zhi Zhou; Jing Wang (Chemical Engineering Journal, 2023)

K+ and CeO2 nanoparticles modified OMS-2 nanorods for enhanced activity and stability of photocatalytic toluene oxidation: K+ charge modulation and mechanistic investigation - Pingping Yu; Nan Li; Weixin Zou; Xiaoqian Wei; Jiawei Ji; Li Han; Yandi Cai; Wei Tan; Bin Gao; Lin Dong (Chemical Engineering Journal, 2023)

Photoacoustic/fluorescence dual-modality cyanine-based probe for real-time imaging of endogenous cysteine and in situ diagnosis of cervical cancer in vivo - Xiang Zou; Yuping Zhao; Weiying Lin (Analytica Chimica Acta, 2023)

The biological transformation of ammonium and urea in a eutrophic estuarine system in Southern China - Jin-Ming Tang; Min Nina Xu; Yuxuan Lin; Huangxin Chen; Haoquan Jin; Li-Li Han; Wenbin Zou; Shuh-Ji Kao (Frontiers in Marine Science, 2022)
Estuaries channel large amounts of anthropogenic nitrogen (N) from continents to the offshore where productivity is widely limited by N and phosphorus. Ammonium and urea, two reduced forms of anthropogenic N commonly observed, are the preferred substrates for various microorganisms (e.g., uptake by phytoplankton or bacteria and oxidation by nitrifier). Yet, it remains underexplored how they transform and their concentrations vary during transport in the estuary which may influence the offshore microbial community. We applied 15 N isotope tracer incubation techniques to determine the two main bio-consumption processes, i.e., uptake and oxidation, of ammonium and urea, in the dark for the Jiulong River Estuary, a eutrophic estuary in southeastern China. Results showed that light penetration depth ranged from 0.8-3.3 m leaving 76% of estuary water bodies to stay in dark situations throughout a day. Ammonia oxidation, which favors dark conditions, dominates the estuarine regenerated-N cycle, showing the rank: ammonia oxidation > ammonium uptake >> urea uptake ≈ urea oxidation. By compiling the reported case studies, we found the relatively low ratio of urea oxidation to ammonia oxidation was accompanied by a relatively high ammonium concentration. Microorganisms’ high preference for ammonium over urea may lead to an inhibitory-like phenomenon. An analogous effect was evident by the increased urea uptake at downstream when ammonium was down to a few µM. The obstructed urea utilization resulted in 10 times longer lifetime for urea relative to ammonium (surface: 19 ± 9 days; bottom 12 ± 7 days). Such an inhibitory-like effect allows urea to be preserved in the estuary and allows urea to be transported farther offshore to stimulate microorganisms capable of utilizing urea, which may have significant impacts on offshore ecology.

Detection by environmental surveillance and genomic characterization of H5N8 highly pathogenic avian influenza virus from a poultry meat market in Beijing, China, 2021–22 - Shujuan Cui; Lin Zou; Yimeng Liu; Jiachen Zhao; Guilan Lu; Weixian Shi; Yang Pan; Xiaomin Peng; Daitao Zhang; Peng Yang; Quanyi Wang (Veterinary Research Communications, 2022)

Pinocembrin Inhibits P2X4 Receptor–Mediated Pyroptosis in Hippocampus to Alleviate the Behaviours of Chronic Pain and Depression Comorbidity in Rats - Runan Yang; Jingjian Yang; Zijing Li; Ruichen Su; Lifang Zou; Lin Li; Xiumei Xu; Guilin Li; Shuangmei Liu; Shangdong Liang; Changshui Xu (Molecular Neurobiology, 2022)

An association study on the risk, glucocorticoids effectiveness, and prognosis of systemic lupus erythematosus: insight from mitochondrial DNA copy number - Zhen Li; Qi-Qun Zong; Chun-Xia Zhai; Guang-Hui Yu; Wan-Qin Hu; Yu-Hua Wang; Lin-Lin Wang; Zi-Ye Yan; Ting-Yu Zhang; Ying Teng; Shuang Liu; Jing Cai; et al. (Immunologic Research, 2022)

Optimized Mo-doped IrOx anode for efficient degradation of refractory sulfadiazine - Xiang Shao; Chenglong Ma; Lin Zhu; Chongjie Zou; Limei Cao; Ji Yang (Environmental Science and Pollution Research, 2022)

Coupling Relationship of Geomorphic Evolution and Marine Hydrodynamics in the Stage-Specific Development of Urban Bays: A Modelling Case Study in Quanzhou Bay (1954–2017), China - Xianbiao Xiao; Yunhai Li; Junjian Tang; Fusheng Luo; Fangfang Shu; Liang Wang; Jia He; Xiaochun Zou; Wenqi Chi; Yuting Lin; Binxin Zheng (Journal of Marine Science and Engineering, 2022)
With the development of social economy and human activities, the geomorphology and hydrodynamic conditions of coasts have been dramatically changed, causing serious environmental pollution and resource depletion. Taking Quanzhou Bay as an example, this study combined geomorphologic change with a hydrodynamic model to simulate the change in tidal currents in different periods. The results show a change in the coastline was the main cause of hydrodynamic change during the industrialization reform. During the past 70 years, the tidal prism decreased year by year, and the average velocity of the tidal current in the channel decreased by 33.7% and 30.8% at flood and ebb tide, respectively. In the early stages of industrialization, reclamation land was used in a single way. The tidal prism decreased by 22.2% and 29.8% in the spring and neap tide, respectively. In the middle and later stages, the tidal current velocity increased, and reclamation land was used in a variety of ways. In modern society, the reclamation land-use type was unitary. Based on this research, we show the influence of human activities on the evolution of the bay’s geomorphology and provide suggestions for the management of the bay.

Study on Particle Size Distribution Characteristics in Urban Roadside Microenvironment Using an ELPI+ - Xiaozhen Fang; Lin Wu; Qijun Zhang; Jing Zhang; Zhiwen Yang; Chao Zou; Chao Ma; Yanjie Zhang; Hongjun Mao (Water, Air, & Soil Pollution, 2022)

Temporal and spatial distribution characteristics of drought and flood considering the influence of underlying surface in Hainan Island, tropical areas of China - Changqing Ye; Yi Zou; Yanhu He; Youwen Lin; Dan Li; Lirong Zhu (Theoretical and Applied Climatology, 2022)

Identification of a 5-gene-risk score model for predicting luminal A-invasive lobular breast cancer survival - Yi-Huan Chen; Tao-Feng Zhang; Yi-Yuan Liu; Jie-Hua Zheng; Wei-Xun Lin; Yao-Kun Chen; Jie-Hui Cai; Juan Zou; Zhi-Yang Li (Genetica, 2022)

Streptomyces akebiae sp. nov., a novel actinomycete isolated from rhizosphere soil of Akebia trifoliate - Ping Mo; Kaiqin Li; Jinhua Zhou; Fumin Zhou; Yazhi Chen; Xiaojia Lin; Xiaoyu Liu; Kerui Huang; Wansheng Zou; Jian Gao (Antonie van Leeuwenhoek, 2022)

The consistent background color preference highlights the personality in the lined seahorse, Hippocampus erectus - Siping Li; Xin Liu; Tingting Lin; Dong Zhang; Xiong Zou (Frontiers in Marine Science, 2022)
Background color in aquaculture has been paid more attention due to the effect on fish growth, survival, health, and reproduction. In the present study, we evaluated the background color preference of the lined seahorse ( Hippocampus erectus ) and its relationship with personality. Preference was assessed over 10 consecutive days through allowing the lined seahorse to freely choose six different colored compartments, i.e., white, red, green, black, yellow, and blue backgrounds. To minimize the spurious preference response, the individual preference index (PI) was applied to calculate the preference intensity of the background colors. Preference reliability was further verified by a binary choice test through the choice for the most preferred or non-preferred color. Preference consistency under stress situation was assessed by a “knock-at-the-door” test as confining the seahorse in a transparent circle after a 30-s air exposure and measuring the proportion of knock toward different colored backgrounds. The personality was conjointly analyzed by new environment test and novel object test. Overall, the lined seahorse showed a general preference for white and blue while avoidance of black and red backgrounds at either unstressed or stressed situations. The shyer the seahorse was, the more preference for white background it displayed. Thus, white and blue background colors are recommended for culturing the lined seahorse. Furthermore, white color preference is a potential indicator in personality study of the lined seahorse.

Residual analysis of QoI fungicides in multiple (six) types of aquatic organisms by UPLC-MS/MS under acutely toxic conditions - Hong Li; Shuai Hu; Fengshou Sun; Qi Sun; Ning Wang; Beixing Li; Nan Zou; Jin Lin; Wei Mu; Xiuyu Pang (Environmental Science and Pollution Research, 2022)

Knockdown of lncRNA MIAT attenuated lipopolysaccharide-induced microglial cells injury by sponging miR-613 - Jia Li; Chang-Lin Zou; Zhi-Ming Zhang; Feng Xue (Mammalian Genome, 2022)

Multitrophic diversity and biotic associations influence subalpine forest ecosystem multifunctionality - Ya‐Huang Luo; Marc W. Cadotte; Jie Liu; Kevin S. Burgess; Shao‐Lin Tan; Lin‐Jiang Ye; Jia‐Yun Zou; Zhong‐Zheng Chen; Xue‐Long Jiang; Juan Li; Kun Xu; De‐Zhu Li; et al. (Ecology, 2022)
Biodiversity across multiple trophic levels is required to maintain multiple ecosystem functions. Yet it remains unclear how multitrophic diversity and species interactions regulate ecosystem multifunctionality. Here, combining data from 9 different trophic groups (including trees, shrubs, herbs, leaf mites, small mammals, bacteria, pathogenic fungi, saprophytic fungi, and symbiotic fungi) and 13 ecosystem functions related to supporting, provisioning, and regulating services, we used a multitrophic perspective to evaluate the effects of elevation, diversity, and network complexity on scale‐dependent subalpine forest multifunctionality. Our results demonstrated that elevation and soil pH significantly modified species composition and richness across multitrophic groups and influenced multiple functions simultaneously. We present evidence that species richness across multiple trophic groups had stronger effects on multifunctionality than species richness at any single trophic level. Moreover, biotic associations, indicating the complexity of trophic networks, were positively associated with multifunctionality. The relative effects of diversity on multifunctionality increased at the scale of the larger community compared to a scale accounting for neighboring interactions. Our results highlight the paramount importance of scale‐ and context‐dependent multitrophic diversity and interactions for a better understanding of mountain ecosystem multifunctionality in a changing world.

Hydrodynamic effects of large-scale suspended mussel farms: Field observations and numerical simulations - Wei Zhong; Jun Lin; Qingping Zou; Ying Wen; Wei Yang; Guanlin Yang (Frontiers in Marine Science, 2022)
The hydrodynamic effects of the largest suspended mussel farms in the East China Sea near Gouqi Island, was investigated using a high-resolution 3D ocean model and field observations. To capture the 3D farm effects on hydrodynamics, an additional depth dependent momentum sink term was introduced in the model. The model results compared well with the field observations. The present model and observational results indicate that the presence of farms reduces the flow by more than 79%, 55%, and 34% in the upper, middle, and bottom layers at the farm center, respectively. According to the harmonic analysis of predicted current, mussel farms reduce the magnitude of the semidiurnal tidal current and also alter the magnitude and direction of the diurnal tidal current. The blockage by the farm weakens the Eulerian residual tidal current within the farm in the NE-SW direction, while strengthens that at the edge of the farm in the SE-NW direction. Cross sections, Sec1 and Sec2 are perpendicular to these two major residual currents and intercept with the center of the farm from SE to NW and from NE to SW respectively. The farm effect on the total water flux over a month through the Sec2 displays a semi-lunar periodic oscillation and is one order of magnitude smaller than that at Sec1. An asymmetry tidal current was observed in the farm north of Gouqi Island. The field observation of vertical profiles of current suggests that the thickness of surface canopy boundary layer can reach 5 m upstream from the farm during flood tide, increases gradually downstream up to 10 m under the cumulative influences of the farm. And a wake zone was observed downstream from the farm during flood tide. Better understanding of farm-induced hydrodynamic effects provides insight into how to optimize farm layouts based on local hydrodynamics, to maximize farm productivity and minimize environmental impacts.

Fusing XGBoost and SHAP Models for Maritime Accident Prediction and Causality Interpretability Analysis - Cheng Zhang; Xiong Zou; Chuan Lin (Journal of Marine Science and Engineering, 2022)
In order to prevent safety risks, control marine accidents and improve the overall safety of marine navigation, this study established a marine accident prediction model. The influences of management characteristics, environmental characteristics, personnel characteristics, ship characteristics, pilotage characteristics, wharf characteristics and other factors on the safety risk of maritime navigation are discussed. Based on the official data of Zhejiang Maritime Bureau, the extreme gradient boosting (XGBoost) algorithm was used to construct a maritime accident classification prediction model, and the explainable machine learning framework SHAP was used to analyze the causal factors of accident risk and the contribution of each feature to the occurrence of maritime accidents. The results show that the XGBoost algorithm can accurately predict the accident types of maritime accidents with an accuracy, precision and recall rate of 97.14%. The crew factor is an important factor affecting the safety risk of maritime navigation, whereas maintaining the equipment and facilities in good condition and improving the management level of shipping companies have positive effects on improving maritime safety. By explaining the correlation between maritime accident characteristics and maritime accidents, this study can provide scientific guidance for maritime management departments and ship companies regarding the control or management of maritime accident prevention.

Long-term soil temperature dynamics of the Kunlun Pass permafrost region on the Qinghai-Tibetan Plateau - Guojie Hu; Lin Zhao; Tonghua Wu; Xiaodong Wu; Ren Li; Xiaofan Zhu; Defu Zou; Junming Hao; Wangping Li (Theoretical and Applied Climatology, 2022)

Differential responses of bacterial communities in coral tissue and mucus to bleaching - Yiyang Zou; Yu Chen; Lin Wang; Si Zhang; Jie Li (Coral Reefs, 2022)

Identification of the Largest SCA36 Pedigree in Asia: with Multimodel Neuroimaging Evaluation for the First Time - Yue Xie; Zhao Chen; Zhe Long; Rui-Ting Chen; Yi-Zheng Jiang; Ming-Jie Liu; Lin-Liu Peng; Hui-Rong Peng; Na Wan; Guangdong Zou; Chun-Rong Wang; Yu-Ting Shi; et al. (The Cerebellum, 2022)

Investigation on long-term progressive deformation of engineering slope based on comprehensive monitoring - Shi-shu Zhang; Song-feng Guo; Sheng-wen Qi; Feng-jiao Tang; Jin-shan Hu; Xiao-ping Zhao; Cong-yan Ran; Xin Wang; Yu Zou; Xiao-lin Huang; Bo-wen Zheng; Ning Liang (Journal of Mountain Science, 2022)

Photosynthesis-Related Proteins Play Crucial Role During Senescence Stage in Flue-Cured Tobacco Plants: A Combine iTRAQ-PRM Study - Conglian He; Shubin Sun; Yun Tang; Chenggang He; Pengfei Li; Tianyang Xu; Gaokun Zhao; Congming Zou; Zhonglong Lin; Yi Chen (Journal of Plant Growth Regulation, 2022)

Effect of freeze–thaw cycles on volumetric and water retention property of a clay under three compaction conditions - Jianguo Lin; Weilie Zou; Kewei Fan; Haoze Jia; Guitao Zhao (Arabian Journal of Geosciences, 2022)

Fate of heavy metals and bacterial community composition following biogas slurry application in a single rice cropping system - Qiang Wang; Zhaoming Chen; Jun Zhao; Junwei Ma; Qiaogang Yu; Ping Zou; Hui Lin; Jinchuan Ma (Journal of Soils and Sediments, 2022)

Simultaneous detection of ten kinds of insecticide residues in honey and pollen using UPLC-MS/MS with graphene and carbon nanotubes as adsorption and purification materials - Xiuyu Pang; Chenyu Li; Chuanjiang Zang; Lei Guan; Peng Zhang; Chunxiang Di; Nan Zou; Beixing Li; Wei Mu; Jin Lin (Environmental Science and Pollution Research, 2022)

Quantitative synthetic MRI reveals grey matter abnormalities in children with drug-naïve attention-deficit/hyperactivity disorder - Shu Su; Yingqian Chen; Yan Dai; Liping Lin; Long Qian; Qin Zhou; Mengsha Zou; Hongyu Zhang; Meina Liu; Xianhong Xiang; Zhiyun Yang (Brain Imaging and Behavior, 2022)

Pre- and postharvest measures used to control decay and mycotoxigenic fungi in potato ( Solanum tuberosum L.) during storage - Jia Liu; Zhiqiang Sun; Yuping Zou; Wenhua Li; Fangyun He; Xiaoya Huang; Chenglin Lin; Qingnian Cai; Michael Wisniewski; Xuehong Wu (Critical Reviews in Food Science and Nutrition, 2022)

Coupling Relationship of Human Activity and Geographical Environment in Stage-Specific Development of Urban Coastal Zone: A Case Study of Quanzhou Bay, China (1954–2020) - Xianbiao Xiao; Yunhai Li; Fangfang Shu; Liang Wang; Jia He; Xiaochun Zou; Wenqi Chi; Yuting Lin; Binxin Zheng (Frontiers in Marine Science, 2022)
Owing to the development of the social economy, the geographical environment and ocean utilization patterns of urban coastal zones have changed. This change, in turn, has influenced the socio-economic development of urban coastal zones. Based on the Geographic Information System technology, the area, coastline length, and shoreland use function of reclamation areas were obtained from the geographic charts (1954–2020) and remote sensing data (1988–2017) of Quanzhou Bay. In this study, we analyzed the geomorphologic change process and the relationship between land use patterns and economic development in Quanzhou Bay from the perspectives of hydrodynamics, sediments, and human activity. Our results indicated that over the past 70 years, the bay area has reduced by 21.5%. The length of the coastline decreased from 208.36 km in 1959 to 149.11 km in 1988, whereas the shape index of the bay (SIB) decreased from 3.09 to 2.41 during the same period. Between 1988 and 2017, the coastline increased to 162.91 km, causing the SIB to increase to 2.72. The artificial index of the bay increased from 0.28 in 1959 to 0.90 in 2017. The intensity of bay the development (IBD) first increased from 0.27 in 1959 to 0.77 in 2006. During the transition to a more modern society (2006 to present), the IBD slightly decreased to 0.73 in 2017. Affected by human activity, the transformation of the reclaimed land in Quanzhou Bay can be divided into four stages that are closely linked to the economic development in the region. In the early industrialization period, reclaimed land in the region was used for agricultural production, whereas in the mid-industrialization period, it was gradually transformed into a combination of industrial (29.8%) and agricultural (56.1%) lands. In the later period of industrialization, the reclaimed land was gradually converted into urban industrial and port lands. Finally, with further refinement and upgrading of economic and industrial structures, the socio-economic and environmental benefits from coastal reclamation projects have been increasing, whereas the proportion of economic benefits (in the total benefits) has been decreasing. The results of this study can provide decision-making references for the optimization of utilization patterns and the economic development of reclamation lands in coastal areas.

Genome-wide evolution of MAPKs family and their expression in response to bacterial infection in seahorse Hippocampus erectus - Kai Wang; Xin Wang; Qiang Zou; Han Jiang; Rongrong Zhang; Yanan Tian; Lele Zhang; Qiang Lin (Journal of Oceanology and Limnology, 2021)

Untargeted metabolomic analysis of urine samples for diagnosis of inherited metabolic disorders - Hao Liu; Jiang Zhu; Qiu Li; Dongjuan Wang; Kexing Wan; Zhaojian Yuan; Juan Zhang; Lin Zou; Xiaoyan He; Jingkun Miao (Functional & Integrative Genomics, 2021)

Seagrass (Zostera marina) promotes nitrification potential and selects specific ammonia oxidizers in coastal sediments - Xianbiao Lin; Pengfei Zheng; Songbao Zou; Feifei Sun; Xiaoli Zhang; Jun Gong (Journal of Soils and Sediments, 2021)

Quercetin Attenuates High-Fat Diet-Induced Excessive Fat Deposition of Spotted Seabass (Lateolabrax maculatus) Through the Regulatory for Mitochondria and Endoplasmic Reticulum - Yan-Zou Dong; Tian Xia; Ji-Bin Lin; Ling Wang; Kai Song; Chun-Xiao Zhang (Frontiers in Marine Science, 2021)
This study aimed to investigate the effects of quercetin (QUE) on fat deposition and the underlying mechanism. Fish were fed four test diets: normal fat diet (NFD), high-fat diet (HFD), and HFD supplemented with 0.5 or 1.0 g/kg quercetin (QUE0.5 or QUE1.0). The results showed that HFD feeding resulted in poor growth and feed utilization while QUE treatment reversed this. The fat contents of serum and liver were increased by HFD and QUE supplementation significantly decreased fat content. Furthermore, gene expressions and ultrastructure observation showed that mitochondrial biogenesis and mitophagy were inhibited and endoplasmic reticulum stress (ERS) in the HFD group. QUE can activate the biogenesis and autophagy of mitochondria and suppress ERS, which is related to its fat-lowering effect.

Energy consumption, air pollution, and public health in China: based on the Two-Stage Dynamic Undesirable DEA model - Hang Lin; Huangxin Chen; Lin Zhang; Youjia Luo; Yi Shi; Wenjie Zou (Air Quality, Atmosphere & Health, 2021)

Whole brain volume and cortical thickness abnormalities in Wilson’s disease: a clinical correlation study - Yukun Song; Lin Zou; Jing Zhao; Xiangxue Zhou; Yingqian Huang; Haishan Qiu; Haiwei Han; Zhiyun Yang; Xunhua Li; Xiaoying Tang; Jianping Chu (Brain Imaging and Behavior, 2021)

Human papillomavirus prevalence among men who have sex with men in China: a systematic review and meta-analysis - Yiguo Zhou; Yi-Fan Lin; Lei Gao; Jianghong Dai; Ganfeng Luo; Lanying Li; Tanwei Yuan; Peiyang Li; Yuewei Zhan; Yanxiao Gao; Huachun Zou (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Why pendulum symmetry is absent from the cymose partial inflorescences of Cannaceae? Insights into the essential characteristic of cincinni - Xueyi Tian; Qianxia Yu; Canjia Lin; Tong Zhao; Pu Zou; Jingping Liao (Journal of Plant Research, 2021)

New insights into the fine-scale history of western–eastern admixture of the northwestern Chinese population in the Hexi Corridor via genome-wide genetic legacy - Hongbin Yao; Mengge Wang; Xing Zou; Yingxiang Li; Xiaomin Yang; Ailin Li; Hui-Yuan Yeh; Peixin Wang; Zheng Wang; Jingya Bai; Jianxin Guo; Jinwen Chen; et al. (Molecular Genetics and Genomics, 2021)

The effect of conservation tillage in managing climate change in arid and semiarid areas—a case study in Northwest China - Lin Dong; Tong Si; Yu-e Li; Xiao-Xia Zou (Mitigation and Adaptation Strategies for Global Change, 2021)

sgRNACNN: identifying sgRNA on-target activity in four crops using ensembles of convolutional neural networks - Mengting Niu; Yuan Lin; Quan Zou (Plant Molecular Biology, 2021)

Phylogeny, recombination, and invasiveness of group B Streptococcus revealed by genomic comparisons of its global strains - Enze Lin; Shengmei Zou; Yue Wang; Chien-Chung Lee; Cheng-Hsun Chiu; Ye Feng (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Ecological Conservation Redline will promote harmony between humans and nature in the future - Yan Wang; Jixi Gao; Changxin Zou; Delin Xu; Naifeng Lin; Kun Zhang; Lixia Wang (Ambio, 2021)

First Detection and Molecular Identification of Entamoeba in Yaks from China - Mei Ren; Fan Yang; Jing-min Gou; Pin-xue Wang; Min Zou; Xiao-hong Zhong; Qing Lin (Acta Parasitologica, 2021)

The contrasting effects of thermodynamic and dynamic processes on East Asian summer monsoon precipitation during the Last Glacial Maximum: a data-model comparison - Yong Sun; Haibin Wu; Masa Kageyama; Gilles Ramstein; Laurent Z. X. Li; Ning Tan; Yating Lin; Bo Liu; Weipeng Zheng; Wenchao Zhang; Liwei Zou; Tianjun Zhou (Climate Dynamics, 2021)
The Last Glacial Maximum (LGM; 21 ka BP) was the most recent glacial period when the global ice sheet volume was at a maximum. Therefore, the LGM can be used to investigate atmospheric dynamics under a climate that differed significantly from the present. This study quantitatively compares pollen records of boreal summer (June–July–August) precipitation with the PMIP3 LGM simulations. The data-model comparison shows an overall agreement on a drier than pre-industrial East Asian summer monsoon (EASM) climate. Nevertheless, 17 out of 55 records show a regional precipitation increase that is also simulated over the additional land mass area due to sea level drop. The thermodynamic and dynamic responses are analyzed to explain a drier LGM EASM as a combination of these two antagonistic mechanisms. Relatively low atmospheric moisture content was the main thermodynamic control on the lower LGM (relative to pre-industrial levels) EASM precipitation amounts in both the reconstructions and the models. In contrast, two dynamic processes in relation to stationary eddy activity act to increase EASM precipitation regionally in records and simulations, respectively. Precipitation increase in records is explained by dynamic enhancement of the horizontal moisture transport, while dynamic enhancement of the vertical moisture transport leads to simulated precipitation increase over the specific region where landmass was exposed during LGM along continental coastlines of China due to significant drop in sea level (relative to pre-industrial levels). Overall, the opposing effects of thermodynamic and dynamic processes on precipitation during the LGM provide a means to reconcile the spatial heterogeneity of recorded precipitation changes in sign, although data-model comparison suggests that the simulated dynamic wetting mechanism is too weak relative to the thermodynamic drying mechanism over data-model disagreement regions.

Low ambient temperature increases hospital re-admissions for systemic lupus erythematosus in humid subtropical region: a time series study - Qian Wu; Zhiwei Xu; Yi-Lin Dan; Peng Wang; Yan-Mei Mao; Chan-Na Zhao; Yan-Feng Zou; Dong-Qing Ye; Wenbiao Hu; Hai-Feng Pan (Environmental Science and Pollution Research, 2021)

Structural and functional brain signatures of endurance runners - Long Cao; Yuanchao Zhang; Ruiwang Huang; Lunxiong Li; Fengguang Xia; Liye Zou; Qian Yu; Jingyuan Lin; Fabian Herold; Stephane Perrey; Patrick Mueller; Milos Dordevic; et al. (Brain Structure and Function, 2021)

One new sterpurane sesquiterpene from cultures of the basidiomycete Pholiota nameko - Wan-Rong Niu; Cong-Liang Guo; Deng-Ji Lou; Rui-Ting Li; Qiao Xiang; Yu-Lin Zou; Xiu-Ming Cui; Xiao-Yan Yang (Natural Product Research, 2020)

Phase-field modeling of hydraulic fracture network propagation in poroelastic rocks - Lin Ni; Xue Zhang; Liangchao Zou; Jinsong Huang (Computational Geosciences, 2020)
Modeling of hydraulic fracturing processes is of great importance in computational geosciences. In this paper, a phase-field model is developed and applied for investigating the hydraulic fracturing propagation in saturated poroelastic rocks with pre-existing fractures. The phase-field model replaces discrete, discontinuous fractures by continuous diffused damage field, and thus is capable of simulating complex cracking phenomena such as crack branching and coalescence. Specifically, hydraulic fracturing propagation in a rock sample of a single pre-existing natural fracture or natural fracture networks is simulated using the proposed model. It is shown that distance between fractures plays a significant role in the determination of propagation direction of hydraulic fracture. While the rock permeability has a limited influence on the final crack topology induced by hydraulic fracturing, it considerably impacts the distribution of the fluid pressure in rocks. The propagation of hydraulic fractures driven by the injected fluid increases the connectivity of the natural fracture networks, which consequently enhances the effective permeability of the rocks.

Regional differences of air pollution in China: comparison of clustering analysis and systematic clustering methods of panel data based on gray relational analysis - Huangxin Chen; Lin Zhang; Wenjie Zou; Qi Gao; Hongyang Zhao (Air Quality, Atmosphere & Health, 2020)

Preliminary results of mixed afforestation experiment of Betula alnoides Buch.-Ham. ex D. Don in Southern Fujian China - Bihua Chen; Bijiang Fang; Guobiao Chen; Yuqing Lin; Xinhua Dai; Yinzhen Liao; Xiaolong Hong; Qinggen Chen; Yongjian Lin; Juan Zhang; Jie Zeng; Junjie Guo; et al. (Vegetos, 2020)

China’s ecological conservation redline: A solution for future nature conservation - Jixi Gao; Yan Wang; Changxin Zou; Delin Xu; Naifeng Lin; Lixia Wang; Kun Zhang (Ambio, 2020)

MiR-615 Regulates NSC Differentiation In Vitro and Contributes to Spinal Cord Injury Repair by Targeting LINGO-1 - Hongfu Wu; Lu Ding; Yuhui Wang; Tang-Bin Zou; Tao Wang; Wenjin Fu; Yong Lin; Xiaomin Zhang; Kangzhen Chen; Yutian Lei; Caitang Zhong; Chuanming Luo (Molecular Neurobiology, 2020)

A novel putative betapartitivirus isolated from the plant-pathogenic fungus Rhizoctonia solani - Yi Chen; Jia En Su; Xi Yun Qin; Zhi Yong Fan; Xiao Hai Zhang; Qing Yu; Zhen Yuan Xia; Cong Ming Zou; Gao Kun Zhao; Zhong Long Lin (Archives of Virology, 2020)

A compartmental approach to isosteviol’s disposition in Sprague-Dawley rats - Ayorinde ADEHIN; Keai Sinn TAN; Chengjuan ZOU; Zhiqiang LU; Yue LIN; Dongfang WANG; Qing CHENG; Wen TAN (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

Effect of Slot Inclination Angle and Borehole-Slot Ratio on Mechanical Property of Pre-cracked Coal: Implications for ECBM Recovery Using Hydraulic Slotting - Quanle Zou; Han Liu; Zhiheng Cheng; Tiancheng Zhang; Baiquan Lin (Natural Resources Research, 2020)

Hydrogen sulfide is a crucial element of the antioxidant defense system in Glycine max–Sinorhizobium fredii symbiotic root nodules - Hang Zou; Ni-Na Zhang; Xue-Yuan Lin; Wei-Qin Zhang; Jian-Hua Zhang; Juan Chen; Ge-Hong Wei (Plant and Soil, 2020)

Correction to: Whole Exome Sequencing Identifies Two Novel Mutations in the Reticulon 4–Interacting Protein 1 Gene in a Chinese Family with Autosomal Recessive Optic Neuropathies - Xiao-Huan Zou; Xin-Xin Guo; Hui-Zhen Su; Chong Wang; En-Lin Dong; Ning Wang; Wan-Jin Chen; Qi-Jie Zhang (Journal of Molecular Neuroscience, 2020)

Combined GWAS and QTL analysis for dissecting the genetic architecture of kernel test weight in maize - Xiaoxiang Zhang; Zhongrong Guan; Lei Wang; Jun Fu; Yinchao Zhang; Zhaoling Li; Langlang Ma; Peng Liu; Yanling Zhang; Min Liu; Peng Li; Chaoying Zou; et al. (Molecular Genetics and Genomics, 2020)

Fruit detection in natural environment using partial shape matching and probabilistic Hough transform - Guichao Lin; Yunchao Tang; Xiangjun Zou; Jiabing Cheng; Juntao Xiong (Precision Agriculture, 2020)

Color-, depth-, and shape-based 3D fruit detection - Guichao Lin; Yunchao Tang; Xiangjun Zou; Juntao Xiong; Yamei Fang (Precision Agriculture, 2020)

Impacts of irrigation methods on greenhouse gas emissions/absorptions from vegetable soils - Xuhong Ye; Hongdou Liu; Xichao Zhang; Jianhui Ma; Bing Han; Wen Li; Hongtao Zou; Yulong Zhang; Xiangui Lin (Journal of Soils and Sediments, 2020)

Development of Climate and Earth System Models in China: Past Achievements and New CMIP6 Results - Tianjun Zhou; Ziming Chen; Liwei Zou; Xiaolong Chen; Yongqiang Yu; Bin Wang; Qing Bao; Ying Bao; Jian Cao; Bian He; Shuai Hu; Lijuan Li; et al. (Journal of Meteorological Research, 2020)

Origins of Beta Amyloid Differ Between Vascular Amyloid Deposition and Parenchymal Amyloid Plaques in the Spinal Cord of a Mouse Model of Alzheimer’s Disease - Qiuju Yuan; Xiaodong Liu; Yan-Fang Xian; Ying Tang; Juntao Zou; Xie Zhang; Pengyun Huang; Wutian Wu; You-qiang Song; Zhi-Xiu Lin (Molecular Neurobiology, 2020)

Association between long-term occupational manganese exposure and bone quality among retired workers - Defu Li; Xiaoting Ge; Zhenfang Liu; Lulu Huang; Yanting Zhou; Peng Liu; Lian Qin; Suzhen Lin; Chaoqun Liu; Qingzhi Hou; Longman Li; Hong Cheng; et al. (Environmental Science and Pollution Research, 2020)

Soil microbial activity and community composition as influenced by application of pig biogas slurry in paddy field in southeast China - Zhaoming Chen; Qiang Wang; Junwei Ma; Stephen Chapman; Ping Zou; Jing Ye; Qiaogang Yu; Wanchun Sun; Hui Lin; Lina Jiang (Paddy and Water Environment, 2020)

l-Arginine alleviates heat stress-induced intestinal epithelial barrier damage by promoting expression of tight junction proteins via the AMPK pathway - Zhaofei Xia; Liqing Huang; Peng Yin; Fenghua Liu; Yanhan Liu; Zhenbiao Zhang; Jiabao Lin; Wenshu Zou; Chunxiao Li (Molecular Biology Reports, 2019)
Heat stress (HS) and secondary restricted blood flow to the intestines cause dysfunction of the intestinal epithelial barrier. Tight junctions (TJs) are essential to maintain intestinal integrity. l -Arginine has beneficial effects on gut functions. However, the underlying mechanisms remain largely unknown. This study tested the hypothesis that l -arginine regulates the TJ network by activating AMP-activated protein kinase (AMPK) signaling, which in turn improves intestinal barrier functions under HS. IEC-6 cells and rat small intestines were used as experiment models of heat stress. AICAR and dorsomorphin were used to activate and inhibit the AMPK pathway, respectively. Cell proliferation, apoptosis, differential gene expression and KEGG pathway analysis, intestinal paracellular permeability, intestinal morphology, and expression of HSP and TJ proteins, and p-AMPK were determined. l -Arginine promoted cell proliferation and reduced apoptosis after heat exposure at an optimal concentration of 5 mmol. Transcriptome sequencing analysis revealed that differentially expressed genes associated with the HSP family and TJs were elevated by l -arginine. According to KEGG pathway analysis, l -arginine activated the AMPK signaling pathway. In vivo, intestinal damage resulted in obvious morphological changes as well as apoptosis with TUNEL and caspase-3 staining under HS and dorsomorphin treatments. Furthermore, HS and dorsomorphin increased the serum D-lactate concentration, diamine oxidase activity, and mRNA expression level of MLCK ( P < 0.05). In contrast, l -arginine and AICAR treatments reduced intestinal injury, maintained intestinal permeability, and increased the villus/crypt ratio under hyperthermia. l -Arginine had the same effect as AICAR both in vitro and in vivo, namely increasing p-AMPK protein expression. l -Arginine and AICAR also upregulated the mRNA expression level of HSP70 and HSP90, and downregulated mRNA expression of MLCK ( P < 0.05). The protein expression levels of TJ proteins ZO-1 and claudin-1 were suppressed by heat stroke and dorsomorphin, but enhanced by l -arginine and AICAR. Our findings indicate that activation of AMPK signaling by l -arginine is associated with improved intestinal mucosal barrier functions by enhancing the expression of TJs in rat small intestines and IEC-6 cells during HS.

Deletion of Gcw13 represses autophagy in Pichia pastoris cells grown in methanol medium with sufficient amino acids - Chengjuan Zou; Pan Wang; Shuli Liang; Ying Lin (Biotechnology Letters, 2019)

Integrated analysis of quantitative proteome and transcriptional profiles reveals abnormal gene expression and signal pathway in bladder cancer - Songbai Liao; Minglin Ou; Liusheng Lai; Hua Lin; Yaoshuang Zou; Yonggang Yu; Xuede Li; Yong Dai; Weiguo Sui (Genes & Genomics, 2019)

A Novel Event Detection Model for Water Distribution Systems Based on Data-Driven Estimation and Support Vector Machine Classification - Xiang-Yun Zou; Yi-Li Lin; Bin Xu; Zi-Bo Guo; Sheng-Ji Xia; Tian-Yang Zhang; An-Qi Wang; Nai-Yun Gao (Water Resources Management, 2019)

Genetic dissection of stalk lodging-related traits using an IBM Syn10 DH population in maize across three environments (Zea mays L.) - Yanling Zhang; Tianhu Liang; Min Chen; Yinchao Zhang; Tao Wang; Haijian Lin; Tingzhao Rong; Chaoying Zou; Peng Liu; Michael Lee; Guangtang Pan; Yaou Shen; et al. (Molecular Genetics and Genomics, 2019)

Greater than the sum of the parts: how the species composition in different forest strata influence ecosystem function - Ya‐Huang Luo; Marc W. Cadotte; Kevin S. Burgess; Jie Liu; Shao‐Lin Tan; Jia‐Yun Zou; Kun Xu; De‐Zhu Li; Lian‐Ming Gao (Ecology Letters, 2019)
The mechanisms underpinning forest biodiversity‐ecosystem function relationships remain unresolved. Yet, in heterogeneous forests, ecosystem function of different strata could be associated with traits or evolutionary relationships differently. Here, we integrate phylogenies and traits to evaluate the effects of elevational diversity on above‐ground biomass across forest strata and spatial scales. Community‐weighted means of height and leaf phosphorous concentration and functional diversity in specific leaf area exhibited positive correlations with tree biomass, suggesting that both positive selection effects and complementarity occur. However, high shrub biomass is associated with greater dissimilarity in seed mass and multidimensional trait space, while species richness or phylogenetic diversity is the most important predictor for herbaceous biomass, indicating that species complementarity is especially important for understory function. The strength of diversity‐biomass relationships increases at larger spatial scales. We conclude that strata‐ and scale‐ dependent assessments of community structure and function are needed to fully understand how biodiversity influences ecosystem function.

Development of polymorphic microsatellite markers for tree peony Paeonia delavayi (Paeoniaceae) using ddRAD-seq data - Shao-Lin Tan; Peter M. Hollingsworth; Han-Tao Qin; Lin-Jiang Ye; Jia-Yun Zou; Lian-Ming Gao (Molecular Biology Reports, 2019)

Whole Exome Sequencing Identifies Two Novel Mutations in the Reticulon 4–Interacting Protein 1 Gene in a Chinese Family with Autosomal Recessive Optic Neuropathies - Xiao-Huan Zou; Xin-Xin Guo; Hui-Zhen Su; Chong Wang; En-Lin Dong; Ning Wang; Wan-Jin Chen; Qi-Jie Zhang (Journal of Molecular Neuroscience, 2019)

Quantifying the carbon source of pedogenic calcite veins in weathered limestone: implications for the terrestrial carbon cycle - Lin Zou; Lin Dong; Meng Ning; Kangjun Huang; Yongbo Peng; Shujian Qin; Honglin Yuan; Bing Shen (Acta Geochimica, 2019)

Geochemical Appraisal of Chemical Weathering and Metal Contamination in Coastal Surface Sediments, Off Northwest Hainan Island, the Gulf of Tonkin - Dawei Liu; Baozhi Lin; Selvaraj Kandasamy; Huawei Wang; Qianqian Liu; Wenbin Zou; Aimei Zhu; Jianjun Zou; Jiann-Yuh Lou; Xuefa Shi (Frontiers in Marine Science, 2019)

Evaluation of the integrated multi-satellite retrievals for global precipitation measurement over the Tibetan Plateau - Lu Ma; Lin Zhao; Li-ming Tian; Li-ming Yuan; Yao Xiao; Le-le Zhang; De-fu Zou; Yong-ping Qiao (Journal of Mountain Science, 2019)

Nodulation and Genomic Capacity of a Novel High-Latitude Bradyrhizobium japonicum HLNEAU001 - Yan Shi; Jianyi Li; Jinhui Wang; Rongsheng Zhu; Shuping Li; Qingying Li; Lin Chen; Jingyi Zhu; Jianan Zou; Jieqi Wang; Huilin Chang; Chao Ma; et al. (Journal of Soil Science and Plant Nutrition, 2019)

Relationship between warfarin dosage and international normalized ratio: a dose–response analysis and evaluation based on multicenter data - Ling Xue; Yuzhen Zhang; Cheng Xie; Ling Zhou; Linsheng Liu; Haiyan Zhang; Lianhong Xu; Hongtao Song; Meiqin Lin; Hanfan Qiu; Junrong Zhu; Yubing Zhu; et al. (European Journal of Clinical Pharmacology, 2019)

Carbon and nitrogen accumulation and interspecific competition in two algae species, Pyropia haitanensis and Ulva lactuca, under ocean acidification conditions - Binbin Chen; Lidong Lin; Zengling Ma; Tiantian Zhang; Weizhou Chen; Dinghui Zou (Aquaculture International, 2019)

Expression of the intrarenal angiotensin receptor and the role of renin-angiotensin system inhibitors in IgA nephropathy - Zheng Zhang; Shi-min Jiang; Ye-ping Ma; Pei-lin Dai; Yi-ning Wang; Gu-ming Zou; Hong-mei Gao; Yue Yang; Wen-ge Li (Molecular and Cellular Biochemistry, 2019)

The research progress in mechanism and influence of biosorption between lactic acid bacteria and Pb(II): A review - Derong Lin; Ran Ji; Dan Wang; Mengshi Xiao; Jingjing Zhao; Jinpeng Zou; Yutong Li; Tao Qin; Baoshan Xing; Yuan Chen; Peng Liu; Zhijun Wu; et al. (Critical Reviews in Food Science and Nutrition, 2019)

The synthesized transporter K16APoE enabled the therapeutic HAYED peptide to cross the blood-brain barrier and remove excess iron and radicals in the brain, thus easing Alzheimer’s disease - Zhenyou Zou; Qiqiong Shen; Yanxia Pang; Xin Li; Yongfeng Chen; Xinjuan Wang; Xinhua Luo; Zhongmin Wu; Zhaosheng Bao; Juanli Zhang; Jiawei Liang; Lingjia Kong; et al. (Drug Delivery and Translational Research, 2019)

Sigma-1 receptor protects against endoplasmic reticulum stress-mediated apoptosis in mice with cerebral ischemia/reperfusion injury - Xuemei Zhao; Lin Zhu; Danyang Liu; Tianyan Chi; Xuefei Ji; Peng Liu; Xuexue Yang; Xinxin Tian; Libo Zou (Apoptosis, 2019)

RETRACTED ARTICLE: Tetraspanin 1 inhibits TNFα-induced apoptosis via NF-κB signaling pathway in alveolar epithelial cells - Lawei Yang; Yahong Wang; Zhanchun Pan; Shenglan Gao; Bao’an Zou; Ziying Lin; Dehui Feng; Changmei HuangFu; Gang Liu (Inflammation Research, 2018)

Triterpenoid saponins from the buds of Lonicera similis - Xiao Zhang; Li-Hua Zou; Yu-Lin He; Cheng Peng; Li Guo; Liang Xiong (Natural Product Research, 2018)

Mining for genes encoding proteins associated with NopL of Sinorhizobium fredii HH103 using quantitative trait loci in soybean (Glycine max Merr.) recombinant inbred lines - Yanjiao Zhang; Xueying Liu; Lin Chen; Ying Fu; Changyu Li; Zhaoming Qi; Jianan Zou; Rongsheng Zhu; Shuping Li; Wei Wei; Jinhui Wang; Huilin Chang; et al. (Plant and Soil, 2018)

Co-Delivery of Ciprofloxacin and Colistin in Liposomal Formulations with Enhanced In Vitro Antimicrobial Activities against Multidrug Resistant Pseudomonas aeruginosa - Shaoning Wang; Shihui Yu; Yuwei Lin; Peizhi Zou; Guihong Chai; Heidi H. Yu; Hasini Wickremasinghe; Nivedita Shetty; Junhong Ling; Jian Li; Qi Zhou (Pharmaceutical Research, 2018)

Occurrence of cucumber mosaic virus subgroup II and its genetic diversity in Sichuan, southwest of China - Chunyan Fei; Zhenpeng Xu; Lijuan Chen; Wenshan Zou; Rui Lv; Honghui Lin; Dehui Xi (Journal of Plant Pathology, 2018)

Combined ultrasound with Fenton treatment for the degradation of carcinogenic polycyclic aromatic hydrocarbons in textile dying sludge - Jian-Hao Zhang; Hai-Yuan Zou; Xun-An Ning; Mei-Qing Lin; Chang-Min Chen; Tai-Cheng An; Jian Sun (Environmental Geochemistry and Health, 2018)

Candidemia in Adults at a Tertiary Hospital in China: Clinical Characteristics, Species Distribution, Resistance, and Outcomes - Shaoming Lin; Ruilan Chen; Song Zhu; Huijun Wang; Lianfang Wang; Jian Zou; Jingdong Yan; Xiangdong Zhang; Dimitrios Farmakiotis; Xiaojiang Tan; Eleftherios Mylonakis (Mycopathologia, 2018)

Calpain inhibition attenuates bleomycin-induced pulmonary fibrosis via switching the development of epithelial-mesenchymal transition - Yuan Liu; Bing Liu; Gu-qin Zhang; Jing-feng Zou; Meng-lin Zou; Zhen-shun Cheng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2018)

BDNF/TrkB Pathway Mediates the Antidepressant-Like Role of H2S in CUMS-Exposed Rats by Inhibition of Hippocampal ER Stress - Le Wei; Li-Yuan Kan; Hai-Ying Zeng; Yi-Yun Tang; Hong-Lin Huang; Ming Xie; Wei Zou; Chun-Yan Wang; Ping Zhang; Xiao-Qing Tang (NeuroMolecular Medicine, 2018)

Auxin is Involved in Lateral Root Formation Induced by Drought Stress in Tobacco Seedlings - Chengdong Wang; Yang Zhao; Pengyuan Gu; Fuyu Zou; Lin Meng; Wenjing Song; Yinju Yang; Shusheng Wang; Yali Zhang (Journal of Plant Growth Regulation, 2018)

Eriodictyol protects against Staphylococcus aureus-induced lung cell injury by inhibiting alpha-hemolysin expression - He Xuewen; Ouyang Ping; Yuan Zhongwei; Yin Zhongqiong; Fu Hualin; Lin Juchun; He Changliang; Shu Gang; Yuan Zhixiang; Song Xu; Zou Yuanfeng; Li Lixia; et al. (World Journal of Microbiology and Biotechnology, 2018)

A routine operational backscattering coefficient regrouping algorithm for a HY-2A scatterometer - Juhong Zou; Mingsen Lin; Bin Zou; Maohua Guo; Yi Zhang (Acta Oceanologica Sinica, 2018)

Tobacco alpha-expansin EXPA4 plays a role in Nicotiana benthamiana defence against Tobacco mosaic virus - Li-Juan Chen; Wen-Shan Zou; Guo Wu; Hong-Hui Lin; De-Hui Xi (Planta, 2018)

Xanthoceraside modulates NR2B-containing NMDA receptors at synapses and rescues learning-memory deficits in APP/PS1 transgenic mice - Lin Zhu; Lei Yang; Xuemei Zhao; Danyang Liu; Xiaoli Guo; Peng Liu; Tianyan Chi; Xuefei Ji; Libo Zou (Psychopharmacology, 2018)

Fusion of sea surface wind vector data acquired by multi-source active and passive sensors in China sea - Juhong Zou; Minsen Lin; Bin Zou; Maohua Guo; Songxue Cui (International Journal of Remote Sensing, 2017)

Nanoparticle-encapsulated emodin decreases diabetic neuropathic pain probably via a mechanism involving P2X3 receptor in the dorsal root ganglia - Lin Li; Xuan Sheng; Shanhong Zhao; Lifang Zou; Xinyao Han; Yingxin Gong; Huilong Yuan; Liran Shi; Lili Guo; Tianyu Jia; Shuangmei Liu; Bing Wu; et al. (Purinergic Signalling, 2017)

Comorbidity Burden of Dementia: A Hospital-Based Retrospective Study from 2003 to 2012 in Seven Cities in China - Qing-Hua Wang; Xin Wang; Xian-Le Bu; Yan Lian; Yang Xiang; Hong-Bo Luo; Hai-Qiang Zou; Jie Pu; Zhong-He Zhou; Xiao-Ping Cui; Qing-Song Wang; Xiang-Qun Shi; et al. (Neuroscience Bulletin, 2017)

Calcification response of Pleurochrysis carterae to iron concentrations in batch incubations: implication for the marine biogeochemical cycle - Xiang Zou; Shiyong Sun; Sen Lin; Kexuan Shen; Faqin Dong; Daoyong Tan; Xiaoqin Nie; Mingxue Liu; Jie Wei (Frontiers of Earth Science, 2017)

A new cycloartane triterpenoid glycoside from Souliea vaginata - Hai-Feng Wu; Xin Liu; Yin-Di Zhu; Jing Zhou; Ying-Ying Gong; Guo-Xu Ma; Xu-Dong Xu; Yi-Lin Liu; Zheng-Hong Luo; Di-Zhao Chen; Qiong-Yu Zou; Zi-Jian Zhao (Natural Product Research, 2017)

The effects of different irrigation regimes on nitrous oxide emissions and influencing factors in greenhouse tomato fields - Bing Han; Xuhong Ye; Wen Li; Xichao Zhang; Yulong Zhang; Xiangui Lin; Hongtao Zou (Journal of Soils and Sediments, 2017)

Brg1 inhibits E-cadherin expression in lung epithelial cells and disrupts epithelial integrity - Ting Wang; Wenjing Zou; Chao Niu; Fengxia Ding; Yaping Wang; Shuang Cai; Hua Zhu; Daiyin Tian; Jihong Dai; Enmei Liu; Qing Lu; Zhou Fu; et al. (Journal of Molecular Medicine, 2017)

Development and Application of Urban High Temporal-Spatial Resolution Vehicle Emission Inventory Model and Decision Support System - Yi Zhang; Lin Wu; Chao Zou; Boyu Jing; Xiaoyu Li; Tim Barlow; Turpin Kevin; Michel André; Yao Liu; Peipei Ren; Gongdong Wang; Hongjun Mao (Environmental Modeling & Assessment, 2017)

Construction and Identification of the RNAi Recombinant Lentiviral Vector Targeting Human DEPDC7 Gene - Zhijun Liao; Xinrui Wang; Dexin Lin; Quan Zou (Interdisciplinary Sciences: Computational Life Sciences, 2017)

Effects of genetic variants of the bovine WNT8A gene on nine important growth traits in beef cattle - Yong-Zhen Huang; Yong Zou; Qing Lin; Hua He; Li Zheng; Zi-Jing Zhang; Yong-Long Dang; Chu-Zhao Lei; Xian-Yong Lan; Xing-Shan Qi; Hong Chen (Journal of Genetics, 2017)

Eburicoic acid from Laetiporus sulphureus (Bull.:Fr.) Murrill attenuates inflammatory responses through inhibiting LPS-induced activation of PI3K/Akt/mTOR/NF-κB pathways in RAW264.7 cells - Junzhi Wang; Pan Zhang; Haibo He; Xinxin Se; Wenjun Sun; Beiyan Chen; Lin Zhang; Ximing Yan; Kun Zou (Naunyn-Schmiedeberg's Archives of Pharmacology, 2017)

The Interaction of Mitochondrial Biogenesis and Fission/Fusion Mediated by PGC-1α Regulates Rotenone-Induced Dopaminergic Neurotoxicity - Kaige Peng; Likui Yang; Jian Wang; Feng Ye; Guorong Dan; Yuanpeng Zhao; Ying Cai; Zhihong Cui; Lin Ao; Jinyi Liu; Zhongmin Zou; Yan Sai; et al. (Molecular Neurobiology, 2017)

A meta‐analysis of fertilizer‐induced soil NO and combined NO +N 2 O emissions - Shuwei Liu; Feng Lin; Shuang Wu; Cheng Ji; Yi Sun; Yaguo Jin; Shuqing Li; Zhaofu Li; Jianwen Zou (Global Change Biology, 2017)
Soils are among the important sources of atmospheric nitric oxide ( NO ) and nitrous oxide (N 2 O), acting as a critical role in atmospheric chemistry. Updated data derived from 114 peer‐reviewed publications with 520 field measurements were synthesized using meta‐analysis procedure to examine the N fertilizer‐induced soil NO and the combined NO +N 2 O emissions across global soils. Besides factors identified in earlier reviews, additional factors responsible for NO fluxes were fertilizer type, soil C/N ratio, crop residue incorporation, tillage, atmospheric carbon dioxide concentration, drought and biomass burning. When averaged across all measurements, soil NO ‐N fluxes were estimated to be 4.06 kg ha −1 yr −1 , with the greatest (9.75 kg ha −1 yr −1 ) in vegetable croplands and the lowest (0.11 kg ha −1 yr −1 ) in rice paddies. Soil NO emissions were more enhanced by synthetic N fertilizer (+38%), relative to organic (+20%) or mixed N (+18%) sources. Compared with synthetic N fertilizer alone, synthetic N fertilizer combined with nitrification inhibitors substantially reduced soil NO emissions by 81%. The global mean direct emission factors of N fertilizer for NO ( EF NO ) and combined NO +N 2 O ( EF c ) were estimated to be 1.16% and 2.58%, with 95% confidence intervals of 0.71–1.61% and 1.81–3.35%, respectively. Forests had the greatest EF NO (2.39%). Within the croplands, the EF NO (1.71%) and EF c (4.13%) were the greatest in vegetable cropping fields. Among different chemical N fertilizer varieties, ammonium nitrate had the greatest EF NO (2.93%) and EF c (5.97%). Some options such as organic instead of synthetic N fertilizer, decreasing N fertilizer input rate, nitrification inhibitor and low irrigation frequency could be adopted to mitigate soil NO emissions. More field measurements over multiyears are highly needed to minimize the estimate uncertainties and mitigate soil NO emissions, particularly in forests and vegetable croplands.

A new diphenyl ether derivative from Mirabilis himalaica - Si-Yu Zhou; Guo-Wei Wang; Yan-Lin Zou; Li-Qing Deng; Ming-Xu Liu; Zhi-Hua Liao; Xiao-Zhong Lan; Min Chen (Natural Product Research, 2017)

First complete genome sequence of parainfluenza virus 5 isolated from lesser panda - Jun-Qiong Zhai; Shao-Lun Zhai; Tao Lin; Jian-Kui Liu; He-Xing Wang; Bing Li; He Zhang; Shu-Zhan Zou; Xia Zhou; Meng-Fan Wu; Wu Chen; Man-Lin Luo (Archives of Virology, 2017)

Heat shock transcription factor 1 protects against pressure overload-induced cardiac fibrosis via Smad3 - Ning Zhou; Yong Ye; Xingxu Wang; Ben Ma; Jian Wu; Lei Li; Lin Wang; Dao Wen Wang; Yunzeng Zou (Journal of Molecular Medicine, 2017)

Magnetic EDTA functionalized CoFe2O4 nanoparticles (EDTA-CoFe2O4) as a novel catalyst for peroxymonosulfate activation and degradation of Orange G - Lin Deng; Zhou Shi; Zhiyan Zou; Shiqing Zhou (Environmental Science and Pollution Research, 2017)

Celastrol, produced by Tripterygium wilfordii Hook F. enhances defense response in cucumber seedlings against diverse environmental stresses - Li-jun Zhu; Xing-guang Deng; Li-juan Zou; Peng-xu Li; Jun-qiang Wu; Da-wei Zhang; Honghui Lin (Journal of Plant Biology, 2017)

Effect of rice planting on the nutrient accumulation and transfer in soils under plastic greenhouse vegetable-rice rotation system in southeast China - Qiang Wang; Jianming Xu; Hui Lin; Ping Zou; Lina Jiang (Journal of Soils and Sediments, 2017)

Sonic Hedgehog Signaling Affected by Promoter Hypermethylation Induces Aberrant Gli2 Expression in Spina Bifida - Xiao-Lin Lu; Li Wang; Shao-Yan Chang; Shao-Fang Shangguan; Zhen Wang; Li-Hua Wu; Ji-Zhen Zou; Ping Xiao; Rui Li; Yi-Hua Bao; Z-Y Qiu; Ting Zhang (Molecular Neurobiology, 2016)

Simulation of Water Quality under Different Reservoir Regulation Scenarios in the Tidal River - Tao Jiang; Ming Zhong; Ying-jie Cao; Long-jian Zou; Bo Lin; Ai-ping Zhu (Water Resources Management, 2016)

Cracking Process and Stress Field Evolution in Specimen Containing Combined Flaw Under Uniaxial Compression - Ting Liu; Baiquan Lin; Wei Yang; Quanle Zou; Jia Kong; Fazhi Yan (Rock Mechanics and Rock Engineering, 2016)

Advanced glycation endproducts in 35 types of seafood products consumed in eastern China - Jing Wang; Zhenxing Li; Ramesh Tushar Pavase; Hong Lin; Long Zou; Jie Wen; Liangtao Lv (Journal of Ocean University of China, 2016)

Radial propagation of magnetospheric substorm-injected energetic electrons observed using a BD-IES instrument and Van Allen Probes - QiuGang Zong; YiXin Hao; Hong Zou; SuiYan Fu; XuZhi Zhou; Jie Ren; LingHua Wang; ChongJing Yuan; ZhiYang Liu; XiangHong Jia; Lin Quan; Ying Liu; et al. (Science China Earth Sciences, 2016)

Major mutation events in structural genes of peste des petits ruminants virus through serial passages in vitro - Xiaodong Wu; Fuxiao Liu; Lin Li; Yanli Zou; Shan Liu; Zhiliang Wang (Virus Genes, 2016)

Mapping the vegetation distribution of the permafrost zone on the Qinghai-Tibet Plateau - Zhi-wei Wang; Qian Wang; Lin Zhao; Xiao-dong Wu; Guang-yang Yue; De-fu Zou; Zhuo-tong Nan; Guang-yue Liu; Qiang-qiang Pang; Hong-bing Fang; Tong-hua Wu; Jian-zong Shi; et al. (Journal of Mountain Science, 2016)

Biological and pathological activities of interleukin-22 - Mirna Perusina Lanfranca; Yanwei Lin; Jingyuan Fang; Weiping Zou; Timothy Frankel (Journal of Molecular Medicine, 2016)

Long-term variations of estimated global solar radiation and the influencing factors in Hunan province, China during 1980–2013 - Ling Zou; Aiwen Lin; Lunche Wang; Xiangao Xia; Wei Gong; Hongji Zhu; Zhenzhen Zhao (Meteorology and Atmospheric Physics, 2016)

Proanthocyanidins accelerate the germination of cucumber (Cucumis sativus L.) seeds - Li-jun Zhu; Xing-guang Deng; Li-juan Zou; Jun-qiang Wu; Da-wei Zhang; Hong-hui Lin (Journal of Plant Biology, 2016)

Correlation between the germline methylation status in ERβ promoter and the risk in prostate cancer: a prospective study - Lihui Wang; Pan Zhang; Xiannan Meng; Xiang Chen; Zou Xiang; Xiaoqian Lin; Ye Liu; Weidong Gan; Xiaodong Han; Dongmei Li (Familial Cancer, 2016)

High Sensitivity Bacillus thuringiensis Cry1Ac Protein Detections Using Fluorescein Diacetate Nanoparticles - Cui Liu; Zhen Zhou; Linling Zou; Yuan-Cheng Cao; Jun’An Liu; Yongjun Lin (Journal of Fluorescence, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Sporogenesis and gametogenesis in Chinese chinquapin (Castanea henryi (Skam) Rehder & Wilson) and their systematic implications - Xiaoming Fan; Deyi Yuan; Jing Tang; Xiaoming Tian; Lin Zhang; Feng Zou; Xiaofeng Tan (Trees, 2015)

Synthesis and biological evaluation of novel platinum complexes of imidazolyl-containing bisphosphonates as potential anticancer agents - Ling Qiu; Gaochao Lv; Yang Cao; Liping Chen; Hui Yang; Shineng Luo; Meifen Zou; Jianguo Lin (JBIC Journal of Biological Inorganic Chemistry, 2015)

Differences in ozone photochemical characteristics between the megacity Nanjing and its suburban surroundings, Yangtze River Delta, China - Junlin An; Jianan Zou; Junxiu Wang; Xu Lin; Bin Zhu (Environmental Science and Pollution Research, 2015)

Crack propagation patterns and energy evolution rules of coal within slotting disturbed zone under various lateral pressure coefficients - Lin Bai-quan; Liu Ting; Zou Quan-le; Zhu Chuan-jie; Yan Fa-zhi; Zhang Zhen (Arabian Journal of Geosciences, 2015)

iMem-Seq: A Multi-label Learning Classifier for Predicting Membrane Proteins Types - Xuan Xiao; Hong-Liang Zou; Wei-Zhong Lin (The Journal of Membrane Biology, 2015)

Endoplasmic Reticulum Protein 29 Protects Axotomized Neurons from Apoptosis and Promotes Neuronal Regeneration Associated with Erk Signal - Yun-Hui Zhang; Visar Belegu; Yu Zou; Fang Wang; Bao-Jiang Qian; Ran Liu; Ping Dai; Wei Zhao; Fa-Bao Gao; Lei Wang; Li-Mei Cao; John W. McDonald; et al. (Molecular Neurobiology, 2015)

Effect of Excessive Potassium Iodide on Rat Aorta Endothelial Cells - Man Zhang; Xiaoyan Zou; Xinying Lin; Jianchao Bian; Huicui Meng; Dan Liu (Biological Trace Element Research, 2015)

Recent Developments and Future Perspectives of Anaerobic Baffled Bioreactor for Wastewater Treatment and Energy Recovery - Gefu Zhu; Ran Zou; Ajay Kumar Jha; Xu Huang; Lin Liu; Chaoxiang Liu (Critical Reviews in Environmental Science and Technology, 2015)

P2X7 receptor of rat dorsal root ganglia is involved in the effect of moxibustion on visceral hyperalgesia - Shuangmei Liu; Qingming Shi; Qicheng Zhu; Ting Zou; Guilin Li; An Huang; Bing Wu; Lichao Peng; Miaomiao Song; Qin Wu; Qiuyu Xie; Weijian Lin; et al. (Purinergic Signalling, 2015)

ATP5b and β2-microglobulin are predictive markers for the prognosis of patients with gallbladder cancer - Jianning Sun; Zhu-lin Yang; Xiongying Miao; Qiong Zou; Jinghe Li; Lufeng Liang; Guixiang Zeng; Senlin Chen (Journal of Molecular Histology, 2015)

Satellite data assimilation of upper-level sounding channels in HWRF with two different model tops - Xiaolei Zou; Fuzhong Weng; Vijay Tallapragada; Lin Lin; Banglin Zhang; Chenfeng Wu; Zhengkun Qin (Journal of Meteorological Research, 2015)

Effects of combined application of organic and inorganic fertilizers plus nitrification inhibitor DMPP on nitrogen runoff loss in vegetable soils - Qiaogang Yu; Junwei Ma; Ping Zou; Hui Lin; Wanchun Sun; Jianzhen Yin; Jianrong Fu (Environmental Science and Pollution Research, 2015)

The caspase-8 shRNA-modified mesenchymal stem cells improve the function of infarcted heart - Yeyou Liang; Qiuxiong Lin; Jiening Zhu; Xiaohong Li; Yongheng Fu; Xiao Zou; Xiaoying Liu; Honghong Tan; Chunyu Deng; Xiyong Yu; Zhixin Shan; Weiwei Yuan (Molecular and Cellular Biochemistry, 2014)

miR-210 over-expression enhances mesenchymal stem cell survival in an oxidative stress environment through antioxidation and c-Met pathway activation - JianFeng Xu; ZheYong Huang; Li Lin; MingQiang Fu; YanHua Gao; YunLi Shen; YunZeng Zou; AiJun Sun; JuYing Qian; JunBo Ge (Science China Life Sciences, 2014)

An adaptive noise attenuation method for edge and amplitude preservation - Han-Peng Cai; Zhen-Hua He; Ya-Lin Li; Guang-Ming He; Wen Zou; Dong-Jun Zhang; Pu Liu (Applied Geophysics, 2014)

Accuracy analysis of PPDF-based method to parameterize aerosol scattering effect - MingMin Zou; LiangFu Chen; JinHua Tao; Lin Su; Meng Fan; Ying Zhang; Dong Han (Science China Earth Sciences, 2014)

Identification and expression of the elongator protein 2 (Ajelp2) gene, a novel regeneration-related gene from the sea cucumber Apostichopus japonicus - Yanli Mei; Feng Yao; Yang Wu; Bing Chu; Cheng Cheng; Yan Liu; Xuejie Li; Xiangyang Zou; Lin Hou (Molecular Biology Reports, 2014)

3D topographic correction of the BSR heat flow and detection of focused fluid flow - Tao He; Hong-Lin Li; Chang-Chun Zou (Applied Geophysics, 2014)

Expression and roles of As-NUPR1 protein from Artemia sinica during embryo development and in response to salinity stress - Rui Zhang; Feng Yao; Cheng Cheng; Yifei Chen; Ying Lv; Zengrong Li; Na Zhao; Ting Wang; Wenting Xin; Xiangyang Zou; Lin Hou (Molecular Biology Reports, 2014)

Cloning and expression analysis of the gene encoding fibrinogen-like protein A, a novel regeneration-related protein from Apostichopus japonicus - Yang Wu; Feng Yao; Yanli Mei; Bing Chu; Cheng Cheng; Yan Liu; Xuejie Li; Xiangyang Zou; Lin Hou (Molecular Biology Reports, 2014)

ACE2 and FZD1 are prognosis markers in squamous cell/adenosquamous carcinoma and adenocarcinoma of gallbladder - Jinghe Li; Zhu-lin Yang; Xuebao Ren; Qiong Zou; Yuan Yuan; Lufeng Liang; Meigui Chen; Senlin Chen (Journal of Molecular Histology, 2014)

Methane and nitrous oxide emissions from direct-seeded and seedling-transplanted rice paddies in southeast China - Shuwei Liu; Yaojun Zhang; Feng Lin; Ling Zhang; Jianwen Zou (Plant and Soil, 2014)

Cloning and expression patterns of the brine shrimp (Artemia sinica) glycogen phosphorylase (GPase) gene during development and in response to temperature stress - Na Zhao; Ming Hou; Ting Wang; Yifei Chen; Ying Lv; Zengrong Li; Rui Zhang; Wenting Xin; Xiangyang Zou; Lin Hou (Molecular Biology Reports, 2014)

Kinetics of manganese transport and gene expressions of manganese transport carriers in Caco-2 cell monolayers - Xiaoli Li; Jingjing Xie; Lin Lu; Liyang Zhang; Lingyan Zhang; Yaxue Zou; Qiuyue Wang; Xugang Luo; Sufen Li (BioMetals, 2013)

Genomic comparison of Salmonella typhimurium DT104 with non-DT104 strains - Er-Ying Zhao; Hong-Xia Bao; Le Tang; Qing-Hua Zou; Wei-Qiao Liu; Da-Ling Zhu; Jessica Chin; Ying-Ying Dong; Yong-Guo Li; Feng-Lin Cao; Cornelis Poppe; Kenneth E. Sanderson; et al. (Molecular Genetics and Genomics, 2013)

Identification and characterization of P GCW14 : a novel, strong constitutive promoter of Pichia pastoris - Shuli Liang; Chengjuan Zou; Ying Lin; Xuanwei Zhang; Yanrui Ye (Biotechnology Letters, 2013)

Epidemiology and full genome sequence analysis of H1N1pdm09 from Northeast China - Xiaoyan Li; Mei Kong; Jinying Chen; Xu Su; Ming Zou; Liru Guo; Lin Li; Jianqing Ding (Virus Genes, 2013)

Subnuclear distribution of SSX regulates its function - Jiaochen Wang; Huali Wang; Wei Hou; Haijing Liu; Yongxin Zou; Hong Zhang; Lin Hou; Michael A. McNutt; Bo Zhang (Molecular and Cellular Biochemistry, 2013)

Transgenic expression of an insect diapause-specific peptide (DSP) in Arabidopsis resists phytopathogenic fungal attacks - Tingquan Wu; Yongfang Chen; Weida Chen; Shenghao Zou; Yongqing Zhang; Yu’e Lin; Zhaojun Liang; Dingzhong Tang (European Journal of Plant Pathology, 2013)

Temporal and spatial variations of global solar radiation over the Qinghai–Tibetan Plateau during the past 40 years - Ren Li; Lin Zhao; Tonghua Wu; Yongjian Ding; Yufei Xin; Defu Zou; Yao Xiao; Yongliang Jiao; Yanhui Qin; Linchan Sun (Theoretical and Applied Climatology, 2013)

A method to estimate concentrations of surface-level particulate matter using satellite-based aerosol optical thickness - JinHua Tao; MeiGen Zhang; LiangFu Chen; ZiFeng Wang; Lin Su; Cui Ge; Xiao Han; MingMin Zou (Science China Earth Sciences, 2013)

Impacts of Dung Combustion on the Carbon Cycle of Alpine Grassland of the North Tibetan Plateau - Zengrang Xu; Shengkui Cheng; Lin Zhen; Ying Pan; Xianzhou Zhang; Junxi Wu; Xiuping Zou; G. C. Dhruba Bijaya (Environmental Management, 2013)

Expression of cellulase genes in Saccharomyces cerevisiae via δ-integration subject to auxotrophic markers - Lin Liu; Cheng Liu; Shaolan Zou; Huajun Yang; Jiefang Hong; Yuanyuan Ma; Minhua Zhang (Biotechnology Letters, 2013)

Immunohistochemical Expression of RAGE and Its Ligand (S100A9) in Cervical Lesions - Xuejie Zhu; Lanying Jin; Shuangwei Zou; Qi Shen; Wenxiao Jiang; Wenjing Lin; Xueqiong Zhu (Cell Biochemistry and Biophysics, 2013)

A docking-based receptor library of antibiotics and its novel application in predicting chronic mixture toxicity for environmental risk assessment - Xiaoming Zou; Xianghong Zhou; Zhifen Lin; Ziqing Deng; Daqiang Yin (Environmental Monitoring and Assessment, 2013)

Expression patterns of As-ClC gene of Artemia sinica in early development and under salinity stress - Qiaozhi Zhang; Ming Hou; Qiuying Li; Lulu Han; Zhe Yuan; Jian Tan; Bin Du; Xiangyang Zou; Lin Hou (Molecular Biology Reports, 2013)

Common genetic variation in CYP1B1 is associated with concentrations of T4, FT3 and FT4 in the sera of polycystic ovary syndrome patients - Shien Zou; Qing Sang; Huan Wang; Ruizhi Feng; Qiaoli Li; Xinzhi Zhao; Qinghe Xing; Li Jin; Lin He; Lei Wang (Molecular Biology Reports, 2013)

Influence of CYP2C19 loss-of-function variants on the antiplatelet effects and cardiovascular events in clopidogrel-treated Chinese patients undergoing percutaneous coronary intervention - Jian-Jun Zou; Hong-Guang Xie; Shao-Liang Chen; Jie Tan; Ling Lin; Ying-Ying Zhao; Hai-Mei Xu; Song Lin; Juan Zhang; Guang-Ji Wang (European Journal of Clinical Pharmacology, 2013)

Upregulation of microRNA-372 associates with tumor progression and prognosis in hepatocellular carcinoma - Hao Gu; Xiaodong Guo; Lin Zou; Haiyan Zhu; Jinhui Zhang (Molecular and Cellular Biochemistry, 2013)

Two new triterpenoid saponins from Caragana microphylla seeds - Cheng-Jian Zheng; Gui-Lin Jin; Jing-Ping Zou; Yi-Ping Jiang; Pei-Xin Sun; Lu-Ping Qin (Journal of Natural Medicines, 2013)

High density lipoprotein cholesterol promotes the proliferation of bone-derived mesenchymal stem cells via binding scavenger receptor-B type I and activation of PI3K/Akt, MAPK/ERK1/2 pathways - Jianfeng Xu; Juying Qian; Xinxing Xie; Li Lin; Jianying Ma; Zheyong Huang; Mingqiang Fu; Yunzeng Zou; Junbo Ge (Molecular and Cellular Biochemistry, 2012)

Lipoxin A4 Inhibits 5-Lipoxygenase Translocation and Leukotrienes Biosynthesis to Exert a Neuroprotective Effect in Cerebral Ischemia/Reperfusion Injury - Le Wu; Sen Miao; Lin-Bing Zou; Ping Wu; Hua Hao; Ke Tang; Pan Zeng; Jing Xiong; Hong-Hua Li; Qiang Wu; Lei Cai; Du-Yun Ye (Journal of Molecular Neuroscience, 2012)

Beta-amyloid induced changes in A-type K+ current can alter hippocampo-septal network dynamics - Xin Zou; Damien Coyle; KongFatt Wong-Lin; Liam Maguire (Journal of Computational Neuroscience, 2012)

Molecular characterization of β-lactam-resistant Escherichia coli isolated from Fu River, China - Li-Kou Zou; Li-Wen Li; Xin Pan; Guo-Bao Tian; Yan Luo; Qi Wu; Bei Li; Lin Cheng; Jiu-Jing Xiao; Su Hu; Yang Zhou; Yu-Juan Pang (World Journal of Microbiology and Biotechnology, 2012)

Cloning and the expression pattern of Spätzle gene during embryonic development and bacterial challenge in Artemia sinica - Lu-ping Zheng; Lin Hou; Miao Yu; Xiang Li; Xiang-yang Zou (Molecular Biology Reports, 2012)

Proteomic Analysis of Osmotic Stress-Responsive Proteins in Sugarcane Leaves - Gui Zhou; Li-Tao Yang; Yang-Rui Li; Cheng-Lin Zou; Li-Ping Huang; Li-Hang Qiu; Xing Huang; Manoj Kumar Srivastava (Plant Molecular Biology Reporter, 2012)

Molecular cloning and its expression of trachealess gene (As-trh) during development in brine shrimp, Artemia sinica - Jia-Qing Wang; Lin Hou; Nan Yi; Riu-Feng Zhang; Xiang-Yang Zou; Qin Xiao; Ran Guo (Molecular Biology Reports, 2012)

Cloning and characterization of β-catenin gene in early embryonic developmental stage of Artemia sinica - Xiang Li; Lin Hou; Jian Ma; Yudong Liu; Luping Zheng; Xiangyang Zou (Molecular Biology Reports, 2012)

ADAM17 regulates prostate cancer cell proliferation through mediating cell cycle progression by EGFR/PI3K/AKT pathway - Ping Lin; Xicai Sun; Tian Feng; Haifeng Zou; Ying Jiang; Zijun Liu; Dandan Zhao; Xiaoguang Yu (Molecular and Cellular Biochemistry, 2012)

Effect of temperature on development and reproduction of Neoseiulus barkeri (Acari: Phytoseiidae) fed on Aleuroglyphus ovatus - Bin Xia; Zhiwen Zou; Pengxin Li; Peng Lin (Experimental and Applied Acarology, 2012)

Magma mixing of granites at Lianghe: In-situ zircon analysis for trace elements, U-Pb ages and Hf isotopes - Feng Cong; ShiLiang Lin; GuangFu Zou; ZaiHui Li; Tao Xie; ZhiMin Peng; Ting Liang (Science China Earth Sciences, 2011)

Impact of simulated microgravity on microvascular endothelial cell apoptosis - Chun-Yan Kang; Lin Zou; Ming Yuan; Yang Wang; Tian-Zhi Li; Ye Zhang; Jun-Feng Wang; Yan Li; Xiao-Wei Deng; Chang-Ting Liu (European Journal of Applied Physiology, 2011)

Molecular and morphological evidences reveal a cryptic species in the Vinaceous Rosefinch Carpodacus vinaceus (Fringillidae; Aves) - Hsu‐Chun Wu; Rong‐Chien Lin; Hsin‐Yi Hung; Chia‐Fen Yeh; Jui‐Hua Chu; Xiao‐Jun Yang; Chiou‐Ju Yao; Fa‐Sheng Zou; Cheng‐Te Yao; Shou‐Hsien Li; Fu‐Min Lei (Zoologica Scripta, 2011)
Wu, H.‐C., Lin, R.‐C., Hung, H.‐Y., Yeh, C.‐F., Chu, J.‐H., Yang, X.‐J., Yao, C.‐J., Zou, F.‐S., Yao, C.‐T., Li, S.‐H. & Lei, F.‐M. (2011). Molecular and morphological evidences reveal a cryptic species in the Vinaceous Rosefinch Carpodacus vinaceus (Fringillidae; Aves). — Zoologica Scripta, 40 , 468–478. The Vinaceous Rosefinch ( Carpodacus vinaceus ) is endemic in East Asia with two recognized subspecies – C. v. vinaceus , distributed along the eastern edge of the Tibetan Plateau and the Himalayas, and C. v. formosanus , restricted to Taiwan’s Central Mountain Range. As reflected in a controversial taxonomic history, this vastly disjunctive distribution pattern suggests that the subspecies, having been isolated from each other for a long time, might have diverged, challenging the current taxonomic treatment and calling for possible species delimitation. Sequences of two mitochondrial fragments (mtDNA) and two Z‐linked nuclear loci (zDNA) were used to reconstruct the intraspecific phylogeny of C. vinaceous . The mtDNA tree shows that the two subspecies of the vinaceous rosefinch form two exclusively monophyletic clades. All but one zDNA sequences from the nominate subspecies and C. v. formosanus also formed exclusively monophyletic clades (the exceptional zDNA sequence from C. v. vinaceous formed a weakly supported clade with two outgroup species). Moreover, by conducting quantitative comparisons of morphometric traits and male plumage coloration, we found that the two subspecies exhibit distinguishable morphological differences. All the evidence therefore suggests that C. v. formosanus is a cryptic species and that its taxonomic status should be restored to full species. Molecular dating suggests that the two sibling rosefinches split 1.7 ± 0.2 million years ago, providing a point estimate for the historical connectivity of biota between eastern Tibet‐Himalayas and montane Taiwan.

A residue in the TRPM2 channel outer pore is crucial in determining species-dependent sensitivity to extracellular acidic pH - Jie Zou; Wei Yang; David J. Beech; Lin-Hua Jiang (Pflügers Archiv - European Journal of Physiology, 2011)

Molecular cloning and expression analysis of a F-type lectin gene from Japanese sea perch (Lateolabrax japonicus) - Lihua Qiu; Liansheng Lin; Keng Yang; Hanhua Zhang; Jianzhu Li; Falin Zou; Shigui Jiang (Molecular Biology Reports, 2011)

Seroprevalence of Mycoplasma hyopneumoniae in pigs in subtropical southern China - Y. He; M. J. Xu; D. H. Zhou; F. C. Zou; R. Q. Lin; C. C. Yin; X. H. He; R. Liang; M. Liang; X. Q. Zhu (Tropical Animal Health and Production, 2011)

Fbxw8 is involved in the proliferation of human choriocarcinoma JEG-3 cells - Ping Lin; Jiejun Fu; Binjiahui Zhao; Feng Lin; Haifeng Zou; Leiyu Liu; Cheng Zhu; Hongmei Wang; Xiaoguang Yu (Molecular Biology Reports, 2011)

Mesenchymal stem cells require integrin β1 for directed migration induced by osteopontin in vitro - Chengyu Zou; Guanbin Song; Qing Luo; Lin Yuan; Li Yang (In Vitro Cellular & Developmental Biology - Animal, 2011)

Overexpression of PPARγ can down-regulate Skp2 expression in MDA-MB-231 breast tumor cells - Jie Meng; Yun Ding; Aiguo Shen; Meijuan Yan; Fei He; Huoyan Ji; Lin Zou; Yonghua Liu; You Wang; Xiaowei Lu; Huimin Wang (Molecular and Cellular Biochemistry, 2010)

Effect of decabromodiphenyl ether (BDE 209) on soil microbial activity and bacterial community composition - Wei Zhu; Lu Liu; Peng Zou; Lin Xiao; Liuyan Yang (World Journal of Microbiology and Biotechnology, 2010)

Transgenic Amorphophallus konjac expressing synthesized acyl-homoserine lactonase (aiiA) gene exhibit enhanced resistance to soft rot disease - Huifang Ban; Xinli Chai; Yongjun Lin; Ying Zhou; Donghai Peng; Yi Zhou; Yulan Zou; Ziniu Yu; Ming Sun (Plant Cell Reports, 2009)

The timing of re-institution of good blood glucose control affects apoptosis and expression of Bax and Bcl-2 in the retina of diabetic rats - Xin-Yuan Gao; Hong-Yu Kuang; Wei Zou; Xiao-Min Liu; Hong-Bin Lin; Yi Yang (Molecular Biology Reports, 2009)

A negative regulator encoded by a rice WRKY gene represses both abscisic acid and gibberellins signaling in aleurone cells - Zhong-Lin Zhang; Margaret Shin; Xiaolu Zou; Jianzhi Huang; Tun-hua David Ho; Qingxi J. Shen (Plant Molecular Biology, 2009)

Differential expression of ubiquitin-conjugating enzyme E2r in the developing ovary and testis of penaeid shrimp Marsupenaeus japonicus - Bingling Shen; Ziping Zhang; Yilei Wang; Guodong Wang; Yun Chen; Peng Lin; Shuhong Wang; Zhihua Zou (Molecular Biology Reports, 2009)

Adenovirus-mediated wild-type p53 gene transfer in combination with bronchial arterial infusion for treatment of advanced non-small-cell lung cancer, one year follow-up - Yong-song Guan; Yuan Liu; Qing Zou; Qing He; Zi La; Lin Yang; Ying Hu (Journal of Zhejiang University-SCIENCE B, 2009)

Cloning, characterization and TBT exposure response of CuZn superoxide dismutase from Haliotis diversicolor supertexta - Kefeng Zhang; Guodong Wang; Zhihua Zou; Xiwei Jia; Shuhong Wang; Peng Lin; Yun Chen; Ziping Zhang; Yilei Wang (Molecular Biology Reports, 2009)

Human mesenchymal stem cells-like cells as cellular vehicles for delivery of immunotoxin in vitro - Chang-chen Hu; Yi-quan Ke; Xin-lin Sun; Xiao-dan Jiang; Ru-xiang Xu; Jun Lv; Yu-sheng Wang; Ying-qian Cai; Ling-sha Qin; Yu-xi Zou (Biotechnology Letters, 2009)

Global decomposition experiment shows soil animal impacts on decomposition are climate‐dependent - DIANA H. WALL; MARK A. BRADFORD; MARK G. ST. JOHN; JOHN A. TROFYMOW; VALERIE BEHAN‐PELLETIER; DAVID E. BIGNELL; J. MARK DANGERFIELD; WILLIAM J. PARTON; JOSEF RUSEK; WINFRIED VOIGT; VOLKMAR WOLTERS; HOLLEY ZADEH GARDEL; et al. (Global Change Biology, 2008)
Climate and litter quality are primary drivers of terrestrial decomposition and, based on evidence from multisite experiments at regional and global scales, are universally factored into global decomposition models. In contrast, soil animals are considered key regulators of decomposition at local scales but their role at larger scales is unresolved. Soil animals are consequently excluded from global models of organic mineralization processes. Incomplete assessment of the roles of soil animals stems from the difficulties of manipulating invertebrate animals experimentally across large geographic gradients. This is compounded by deficient or inconsistent taxonomy. We report a global decomposition experiment to assess the importance of soil animals in C mineralization, in which a common grass litter substrate was exposed to natural decomposition in either control or reduced animal treatments across 30 sites distributed from 43°S to 68°N on six continents. Animals in the mesofaunal size range were recovered from the litter by Tullgren extraction and identified to common specifications, mostly at the ordinal level. The design of the trials enabled faunal contribution to be evaluated against abiotic parameters between sites. Soil animals increase decomposition rates in temperate and wet tropical climates, but have neutral effects where temperature or moisture constrain biological activity. Our findings highlight that faunal influences on decomposition are dependent on prevailing climatic conditions. We conclude that (1) inclusion of soil animals will improve the predictive capabilities of region‐ or biome‐scale decomposition models, (2) soil animal influences on decomposition are important at the regional scale when attempting to predict global change scenarios, and (3) the statistical relationship between decomposition rates and climate, at the global scale, is robust against changes in soil faunal abundance and diversity.

Cloning and infection response of tumour‐necrosis factor alpha in large yellow croaker Pseudosciaena crocea (Richardson) - F. J. Xie; Z. P. Zhang; P Lin; S. H Wang; Z. H Zou; Y. L. Wang (Journal of Fish Biology, 2008)
In this article, reverse transcriptase polymerase chain reaction (RT‐PCR) and real‐time PCR were used to clone the tumour‐necrosis factor alpha (TNF‐α) gene of the large yellow croaker Pseudosciaena crocea (Richardson) and to analyse its response to bacterial infection. The full‐length cDNA of TNF‐α contained a 5′‐untranslated region (5′‐UTR) of 68 bp, followed by an open reading frame (ORF) of 759 bp and a 3′‐UTR of 512 bp. The ORF was capable of encoding 252 amino acids with an estimated molecular mass of 28 kDa. In the 3′‐UTR, there were two putative endotoxin‐responsive motifs and five mRNA instability motifs. The deduced peptide had a transmembrane domain and a TNF‐α family signature. Multiple sequence alignments indicated that P. crocea TNF‐α shares relatively high similarity with both teleost and mammalian TNF‐α. Phylogenetic analysis showed that teleost TNF‐α was located independently in a different branch compared with mammalian TNF‐α. Real‐time PCR analysis demonstrated that the expression of TNF‐α in the head kidney of the P. crocea injected with Vibrio parahaemolyticus was most significantly higher than that of the control group at 2 and 4 days. In blood, at 2 days post‐injection, TNF‐α expression was significantly higher than that of the control group, while at 4 days post‐injection, it was most significantly higher than that of the control group.

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Cloning and characterization of a novel albinism-related zinc finger protein gene in Japanese flounder - Jiaqing Wang; Lin Hou; Xiangyang Zou; Feng Yao; Xiaoyan Li; Xintao Zhao; Ruifeng Zhang; Lijuan Jiang; Wenjing Sun; Jialu An (Fish Physiology and Biochemistry, 2007)

One new triterpenoid saponin from Lysimachia davurica - Lin Zhang; Jingkui Tian; Lizhen Xu; Zhongmei Zou; Shilin Yang (Natural Product Research, 2007)

A new labdane type diterpenoid from Trollius ledebouri - Jian-Hua Zou; Jun-Shan Yang; Liang Zhou; Geng Lin (Natural Product Research, 2006)

Impact of suspended particles and enhancement techniques on ultraviolet disinfection of a secondary effluent - Jianling Wang; Lin Wang; Baozhen Wang; Jinsong Zhang; Qixian Zou (Journal of Ocean University of China, 2006)

Molecular cloning and characterization of AAAS-V2, a novel splice variant of human AAAS - Xin Li; Chaoneng Ji; Jiefeng Gu; Jian Xu; Zhe Jin; Liyun Sun; Xianqiong Zou; Yun Lin; Ruping Sun; Peng Wang; Shaohua Gu; Yumin Mao (Molecular Biology Reports, 2005)

Ground-based remote sensing of LWC in cloud and rainfall by a combined dual-wavelength radar-radiometer system - Lin Hai; Xin Miaoxin; Wei Chong; Hao Yaokui; Zou Shouxiang (Advances in Atmospheric Sciences, 1985)